Structural differences of starch-proteolyzed peptide complexes dictate in vitro fermentation behavior: Selective regulation of gut microbiota composition and short-chain fatty acid production - Xiang Huang; Hui Yang; Rong Feng; Yue Li; Song Zhu; Dejian Huang (Food Hydrocolloids, 2027)

Origin and evolution of granites in the world-class Gejiu Sn-Cu-polymetallic ore district: Implications for mineralization and tectonic setting - Guangjie Li; Yongqing Chen; Xu Zhu; Rong Yang (Journal of Geochemical Exploration, 2026)

High-yield hydrogen production via dolomite/ilmenite synergistic catalytic gasification in a fluidized bed reactor - Shaosheng Fang; Panting Li; Dongfang Li; Shaoxiang Pu; Rong Yang; Aoyang Zhang; Xing Zhu; Hairui Yang; Man Zhang; Hua Wang (Fuel, 2026)

RNA-binding protein BICC1 promotes gastric cancer progression via the PRRX1-MAPK signaling axis - Yuanxin Xing; Rong Fan; Xiuzhen Jiang; Wenshuai Zhu; Fubo Jing; Xiaoli Ma; Yunshan Wang; Yanfei Jia (Functional & Integrative Genomics, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

First report of Fusarium weifangense, F. puerense and F. asiaticum causing leaf spot disease on Morus alba L. in China - Mei Lei; Rong Xiao; Lixia Zhang; Yu Tian; Zhongrong Zheng; Zehui Zhao; Tingting Zhao; Zhu Li; Haixia Ding (Crop Protection, 2026)

Fault activity-induced topographic evolution in the Eastern Himalayan Syntaxis - Zhenhui Zhu; Junfeng Gong; Jiakang Huang; Yuntao Tian; Hanqiao Zheng; Sha Chen; Shuang Bian; Rong Yang; Xuhua Shi; Hanlin Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ecosystem-specific patterns in soil dissolved organic matter (DOM) biodegradability: Validated by a multi-property persistence index for linking DOM and soil organic matter intrinsic characteristics - Shanyi Tian; Sihua Zhu; Songbo Yao; Hui Jiang; Jitao Lv; Rong Huang; Tongwen Zhang; Xiaolei Su; Yongguang Yin; Tao Jiang; Dingyong Wang (Journal of Environmental Sciences, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

In situ formation of chemically integrated and mechanically interlocked interphases enables robust epoxy-copper adhesion - Ting Xin; Zeyu Zheng; Zuo Li; Yue Wu; Yang Liu; Binbin Zhou; Jibao Lu; Xiaoliang Zeng; Fan Yang; Gang Li; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

Combined regulation of CO2 and nutrients on carbon fixation and emission of Microcystis aeruginosa: physiological and transcriptomic insights - Jiao Ran; Guo Li; Lijing Wang; Binghui Zheng; Ensheng Zhu; Rong Xiang; Shanyuan Xue; Zheng Zheng (Water Research, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Spearman rank analysis and dynamic contact stress concentration model of Brazilian splitting fracture behavior of coal samples under impact load - Kong Xiangguo; Rong Zhihao; Ma Yankun; Lin Haifei; Xiao Peng; He Di; Ji Pengfei; Zhu Yanhui (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Robust retrieval of inland water nitrogen and phosphorus: De-biasing satellite-in situ matchups and integrating environmental constraints - Xihua Wang; Xingyu Zhu; Y. Jun Xu; Yongjiu Feng; Rong Huang; Chenyi Shi; Chengming Luo; Boyang Mao; Shunqing Jia; Qinya Lv; Zejun Liu; Xuming Ji; et al. (Journal of Water Process Engineering, 2026)

Molecular insights into the transformation of dissolved organic matter from refinery wastewater in receiving water: Photochemical and photo-microbial effects - Leqi Wang; Lei He; Zhuoyu Li; Haifeng Rong; Yifei Zhu; Zelin Niu; Chunmao Chen; Qinghong Wang (Journal of Environmental Chemical Engineering, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Simultaneous removal of nitrate and phosphate by steel slag biofilter: Optimization of system performance by material ratio - Zhenxiang Liu; Shunan Zhang; Feng Liu; Huixiang Zhu; Lisha Duan; Huailian Rong (Journal of Environmental Chemical Engineering, 2026)

The poisoning mechanism of N2O reductive catalysts and anti-interference modification/regeneration technology - Wu Pengfei; Guan Bin; Zhu Lei; Zhu Tiankui; Chang Shiying; Ma Jiangli; Wang Rong; Yang Dongxia; Shu Kaiyou; Zhuang Zhongqi; Chen Junyan; Gao Junjie; et al. (Journal of Environmental Chemical Engineering, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Integrated network toxicology, transcriptomics, and metabolomics revealed the potential mechanisms of aluminum-induced testicular injury - Siyu Liao; Liqing Huang; Yusi Zhou; Xin Zhang; Shaofeng Huang; Linjun Yu; Shiman Zhu; Wei Chen; Rong Wang; Haimei Qin (Food and Chemical Toxicology, 2026)

Evolutionary agroecology: Passive responses to light competition increase yield in wheat - Yong-He Zhu; Yuan Li; Rong-Rong Wang; Jacob Weiner; Feng-Min Li (Field Crops Research, 2026)

Associations of serum lithium, nickel, cobalt, and manganese with chronic kidney disease among Chinese older adults: Mediating role of lipid metabolism and moderating effect of lifestyle - Yan Wang; Qingping Liu; Wenyuan Zhu; Xiaoqing Ma; Tao Zhang; Mengqi Zou; Mengruo Wang; Lei Bao; Yaxian Pang; Tao Jing; Rong Zhang (Environmental Pollution, 2026)

Electromechanically reconfigurable graphene-hydrogel sensor with stress-buffering interface for multi-functional sensing - Yi Wang; Chenling Wu; Yixiao Li; Kun Zheng; Tong Li; Yutao Song; Chan Ye; Zheng Fang; Chenxin Zhu; Ming Zhang; Rong Yang; Lei Liao (Chemical Engineering Journal, 2026)

Temporal changes of soil erodibility and its driving factors in long-term sugarcane continuous cropping systems - Juan Wei; Tieguang He; Yu Zhu; Lirong Su; Huiping Ou; Yingying Deng; Mengge Yang; Jinlong Chang; Yuliang Liao; Qingbiao Rong; Yuhan Huang (CATENA, 2026)

Molecular mechanism of anammox granular sludge disintegration caused by polyethylene terephthalate micro/nanoplastics: a new perspective based on quorum sensing - Chaofan Xie; Dongyue Li; Jun Li; Jiarui Li; Muchen Yin; Yanshuo Wu; Chi Zhang; Rong Luo; Yuxi Zhu; Zehao Zhang; Zhaoming Zheng; Yongzhen Peng (Bioresource Technology, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Knockout of Resilin-like genes results in diminished wing size in silkworm moths - Tingting Tian; Chunxia Xiao; Haonan Dong; Qinglang Wang; Jia Fang; Zhonghui Dong; Yiran Zhu; Qingyu Rong; Yong Hou (Journal of Insect Physiology, 2026)

Human-relevant co-exposure to 6:2 Cl-PFESA and PFHxS impairs sperm motility and blood-testis barrier integrity in male mice: Evaluation of combined effects - Lan Shi; Tianrui Gao; Zhipeng Zhu; Fan Yang; Bing Han; Jia Lv; Lin Tao; Yang Gao; Rong Hua; Huan Wu; Yichao Huang; Xiaojin He (Journal of Hazardous Materials, 2026)

Synergistic management of nitrogen-based pollutants from ammonia-fueled engines: key emission control technologies - Junjie Gao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

In situ polymerization-prepared water-stable CsPbX3/PMMA composites for water-stimulated anti-counterfeiting and bioimaging - Rong Huang; Xiaoman Xiang; Danxia Zheng; Geyu Feng; Xinyu Ge; Rongze Zhu; Peng Chen; Xueling Chang; Xiao-Chun Hang; Xiaoyang Qi; Longfei Ruan (Chemical Engineering Journal, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Callosobruchus maculatus feeding triggers multilevel defenses in cowpea seeds: from germination regulation to defensive metabolite biosynthesis - Hainuo Hong; Ming Zhang; Jiamei Geng; Qiulin Chen; Zheyi Shi; Yang Gao; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Nitrogen uptake dynamics in coastal waters of eastern Hainan, China - Nannan Gao; Renming Jia; Zuhao Zhu; Penglan Shi; Zhao Rong; Lili Han; Silin Ni; Shan Sun; Jianzhong Su; Shuh-Ji Kao; Min Xu (Acta Oceanologica Sinica, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Natural oligomeric iridoids - Shu-Xuan Wang; Ting-Zhu Ye; Shan-Rong Luo; Lie-Feng Ma; Zha-Jun Zhan (Phytochemistry, 2026)

Culture-enriched sequencing reveals river confluence sediments as high-risk reservoirs of viable multidrug-resistant pathogens - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Zhiwei Zhu (Journal of Hazardous Materials, 2026)

Discovery and engineering of a compost-derived thermophilic BHETase for enhanced depolymerization of post-consumer PET - Xiaoli Zhou; Xian Li; Yi Zang; Lian Zhou; Guangda Feng; Ming-Rong Deng; Honghui Zhu (Journal of Hazardous Materials, 2026)

Low temperature selective catalytic oxidation of ammonia reaction (NH3-SCO): Introducing Co, or Zr to improve comprehensive performance of the Ag/Al2O3 catalyst - Sikai Zhao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Hazardous Materials, 2026)

Chlorinated and brominated persistent organic pollutants in industrial thermal processes: Emission profiles and radical-mediated formation pathways - Junkai Lin; Bingcheng Lin; Zhiyuan Xu; Guohua Zhu; Rong Jin; Lyumeng Ye; Dongyao Chen; Xin Zhou; Minghui Zheng (Journal of Environmental Sciences, 2026)

Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zheng Huang (Fuel, 2026)

Cold acclimation reprograms the flavor metabolome of fresh tea leaves to enhance sensory quality: Insights from metabolomics, GC-O, and transcriptomics - Chenyu Shao; Rong Xu; Yuqi Luo; Mingyue Zhao; Ting Wu; Lihua Zhu; Siyi Xie; Qifang Jin; Lan Chen; Songyan Huang; Juan Mao; Jianan Huang; et al. (Food Research International, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

Correction to: The Cerebrovascular Reactivity Adjusted Fractional Amplitude of Low-Frequency Fluctuations Abnormalities in Middle Cerebral Artery Stenosis and Occlusive Disease - Liqing Zhang; Luoyu Wang; Xue Tang; Yidi Zhu; Rong Wang; Zhongxiang Ding (Translational Stroke Research, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Bioavailability, Migration, and Accumulation Characteristics of Heavy Metals in the Soil–Lotus Root System Adjacent to Highways - Qiang Hu; Rong-hua Qiu; Ren-chao Zhu; Manisha Parajuli; Si-jie Wen; Zi-yang Sun; Ai-hua Yu (International Journal of Environmental Research, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Sedimentary DNA and Fossil Archives Reveal Long‐Term Phytoplankton Shifts and Their Biogeochemical Influence in a Subtropical Lake - Yu Zhao; Jianan Zheng; Meifang Zhong; Wenxiu Zheng; Bo Qin; Kexin Zhu; Chenxue Zhang; Yanjie Zhao; Enlou Zhang; Eric Capo; Rong Wang (Molecular Ecology, 2026)
Understanding long‐term phytoplankton community dynamics is essential for assessing ecological resilience and informing lake management under global change. However, centennial‐scale patterns of phytoplankton dynamics remain poorly resolved due to the limited taxonomic resolution of traditional fossil‐based paleoecological approaches. In this study, a combination of sedimentary DNA (sedDNA) and subfossil diatom analysis was used to investigate changes in the phytoplankton community over the past two centuries and associated sedimentary biogeochemical responses in Lake Xiliang, a subtropical lake in the Yangtze River Basin, China. The sedDNA data captured major shifts in both eukaryotic and cyanobacterial communities, revealing distinct ecological phases linked to human activities and regional climate warming. Under near‐natural conditions with minimal human disturbance, phytoplankton communities typically exhibit low diversity and are characterized by oligotrophic taxa such as xanthophytes and Gyrosigma . After the 1930s, increases in epiphytic Staurosira and declines in tychoplanktonic Aulacoseira suggest reduced river–lake connectivity and weaker water‐column turbulence following the construction of the Jinshui Sluice, likely facilitating macrophyte expansion. In recent decades, intensified anthropogenic pressures combined with regional warming have driven a shift toward more diverse phytoplankton assemblages enriched in cyanobacteria, reflecting elevated nutrient inputs and rising temperatures. The observed associations between phytoplankton community changes and sedimentary geochemical proxies suggest that phytoplankton dynamics may not only have responded to environmental change but also contributed to sedimentary biogeochemical cycling, particularly total organic carbon accumulation and calcium‐related processes such as photosynthesis‐induced carbonate precipitation. These findings illustrate long‐term phytoplankton community dynamics and underscore the value of sedDNA for reconstructing ecological trajectories in lake ecosystems.

A Quad-Polarimetric SAR image reconstruction network and wetland classification fusing optical texture and polarization information - Yating Zhan; Yujun Wang; Ke Song; Yiming Su; Xin Rong; Gui Zhou; Yefei Zhu; Ziqiao Xu (International Journal of Remote Sensing, 2026)

Phenological stage-specific DOM transformations sustain N2 fixation during rice growth in paddy soil - Xiaomin Wang; Xueying Feng; Linhao Liang; Guozheng Gao; Meng Wu; Christina Hazard; Graeme W. Nicol; Baoli Zhu; Rong Sheng; Xiaoyuan Yan; Jun Shan (Soil Biology and Biochemistry, 2026)

Current warming exceeds medieval warm period in impact on Tibetan Plateau lake ecosystems - Jianan Zheng; Rong Wang; Yu Zhao; Kexin Zhu; Yanjie Zhao; Yuan Li; Ke Zhang; Hao Long; Ji Shen (Quaternary Science Reviews, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Corrigendum to “Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control” [Fuel 418 (2026) 138729] - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Corrigendum to “Synergistic management of nitrogen-based pollutants from ammonia-fueled engines: key emission control technologies” [JFUE_138780 (2026) 260529-018277] - Junjie Gao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Atomically dispersed Cu-doped TiO2 derived from MOF for photocatalytic hydrogen evolution - Hao Song; Hang Zhao; Xiao Yan; Xun Zhu; Rong Chen; Qiang Liao (Chemical Engineering Journal, 2026)

From gas-liquid to liquid-liquid: A programmable compartmented droplet microreactor under ambient conditions - Gaojian Chen; Duo Wei; Junhao Zhu; Rong Guo; Lingling Ge (Chemical Engineering Journal, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Uneven geographies, contested practices: The politics of knowledge production in Chinese urban studies - Rong Yang; Chen Cui; Zhenjie Yuan; Hong Zhu (Applied Geography, 2026)

Integrating environmental DNA and trawl surveys to assess seasonal dynamics of fish communities in the Oujiang River Estuary - Chen Weifeng; Ruan Huiting; Wang Wei; Xu Kaiping; Peng Xin; Zhu Rong; Lu Yumiao; Ye Shen; Lin Hungdu; Wang Chen; Zhou Xiaofeng (Frontiers in Marine Science, 2026)
Introduction Monitoring of estuarine fish biodiversity is often constrained by the inherent limitations of traditional survey methods and the complex, dynamic environmental conditions of estuarine habitats. Environmental DNA (eDNA) metabarcoding has emerged as a robust molecular tool for aquatic biodiversity assessment. Nevertheless, its complementary potential to conventional bottom trawling remains understudied in estuarine ecosystems. In this study, we integrated eDNA metabarcoding and bottom trawling to investigate the spatiotemporal dynamics of fish diversity in the Oujiang River Estuary (ORE). Methods Fish assemblage data were collected seasonally across four sampling periods at five fixed sites within the ORE. MiFish-U primers targeting the 12S rRNA gene were utilized for eDNA amplification. And twelve aquatic environmental variables were quantified to disentangle correlations between fish community structure and ambient environmental conditions. Multiple statistical approaches, including alpha diversity analysis, Principal Coordinate Analysis (PCoA) and PERMANOVA, were applied to quantify spatiotemporal shifts in fish assemblages, identify fish-environment correlations, and compare community discrepancies between the two survey methods. Results and discussion The combined approach detected a total of 100 fish species across 84 genera and 45 families. Specifically, eDNA metabarcoding identified 72 fish species, while bottom trawling captured 48 species, with only 20 species shared between the two methods. Fish assemblages exhibited distinct seasonal variations, with both survey methods revealing higher species richness during wet seasons. Temporal fluctuations in water temperature, dissolved oxygen, salinity and nutrient concentrations constituted the primary environmental drivers structuring estuarine fish assemblages, whereas spatial heterogeneity across sampling sites exerted no statistically significant influence on community composition. eDNA metabarcoding showed unique advantages in detecting pelagic, migratory, cryptic and endangered fish species, supporting effective biodiversity monitoring in topographically intricate estuarine waters. In contrast, bottom trawling provided reliable morphological identification and quantitative abundance data for demersal fish taxa, which helped resolve ambiguous species annotations derived from eDNA sequencing. In addition, seven IUCN-listed threatened fish species were documented during the field investigation. Collectively, our findings demonstrate that eDNA metabarcoding and bottom trawling serve as highly complementary, rather than mutually exclusive, tools for fish biodiversity assessment. The integration of the two methods enables a more comprehensive and accurate evaluation of estuarine fish diversity. This study validates the feasibility and efficacy of the combined monitoring framework for macrotidal estuaries and provides valuable scientific references for the ecological conservation and management of the Oujiang River Estuary as well as other similar coastal ecosystems.

Deformation and Reconstruction of Coastal Typhoon Wind Fields in Hangzhou Bay - Li Li; Jiayi Guo; Zhiguo He; Tao Feng; Yuezhang Xia; Honghua Zou; Yaping Zha; Rong Zhou; Ye Zhu; Wenjun Zhu (Journal of Marine Science and Engineering, 2026)
Coastal typhoon deformation plays a critical role in determining typhoon tracks, intensity changes, precipitation and related flooding, storm surges, and typhoon waves, and thus is highly associated with coastal disaster patterns. This study proposes a three-level framework for typhoon wind field modeling through the integration of geometric characterization with physical-informed reconstruction. At its core, an elliptical fitting method is developed based on second-order moments to quantify the structural asymmetries. This geometric fitting method is incorporated into the reconstruction method of Holland–Miyazaki, creating a physically consistent model capable of simulating typhoon deformation processes during landfall. Validation through high-resolution Weather Research and Forecasting (WRF) simulations of Typhoon Chan-hom (2015) demonstrates the framework’s effectiveness, capturing elliptical eyewall deformation with aspect ratios exceeding 1.5, primarily driven by coastal topography and surface friction interactions. The method is further validated through Typhoon Mitag (2019), with mean wind component errors below 1 m/s, the average correlation coefficients surpassing 0.9, and wind direction mean absolute errors largely below 10°. This research provides a practical framework for quantifying and characterizing the wind field deformation during typhoon landfall in coastal regions, thereby supporting ther operational forecasting and disaster reduction in vulnerable coastal regions.

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Boosting sulfamethoxazole degradation via peroxymonosulfate activation: Critical comparison of intrinsic and external nitrogen-doped biochar modulated by pore former - Zijun Zeng; Sen Wang; Anthony Umeh; Gopalan Anantha Iyengar; Houfan Wu; Hongwei Rong; Runliang Zhu; Yunfei Xi; Ravi Naidu (Journal of Hazardous Materials, 2026)

Review: From research progress to real-world marine applications of direct seawater electrolysis for hydrogen production - Yao Yao; Bin Guan; Lei Zhu; Tiankui Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Environmental Chemical Engineering, 2026)

Nitrous oxide emissions, impacts and treatment technologies: Core progress and prospects of systematic, practical and applicable studies - Luoxin Xu; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the effects of propylene glycol on the shelf-life and quality of alkaline fresh noodles - Yao-Rong Jia; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Journal of Cereal Science, 2026)

Enhanced tellurium recovery via ultrasonic-assisted alkaline leaching-electrodeposition with integrated alkali regeneration - Su Yan; Shixing Wang; Libo Zhang; Rong Zhu; Xinrui Yang; Hongliang Liu; Jianqiang Ye; Guowei Luo; Yonggang Zuo; Gengwei Zhang; Guo Lin; Likang Fu (Chemical Engineering Journal, 2026)

Exploring spinal degenerative diseases therapy targets through druggability genes: a Mendelian randomization study - Hao Qin; Mingyu Hao; Zhitan Wang; Jing Zhang; Minghao Xie; Yuhang Diao; Xiaojun Hu; Hongtao Rong; Tao Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Mapping the spatiotemporal distributions of terpenoids and coumarins in Ferula ferulaeoides stem by using MALDI-MSI - Xuerui Zhang; Fangwei Diao; Rong Guo; Zibo Wei; Kai Liao; Yun Zhu (Journal of Plant Biochemistry and Biotechnology, 2026)

Host switching and successive subculturing drive adaptive responses in Liriomyza sativae - Yang Gao; Wei He; Ming Zhang; Hai-Nuo Hong; Jin Wang; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

The TRAF6-TXNIP-NLRP3 signaling axis regulates LPS-induced pyroptosis in glomerular podocytes - Chunhua Ye; Hua Liu; Zhu Ming; Qinjun Yi; Rong Xiang; Yifu Chen (Journal of Molecular Histology, 2026)

Archaeal and Bacterial Communities and Their Relations with Hydrochemistry in Gongzhu Co, a Carbon-Poor, Nutrient-Rich Basin Lake of the Qinghai–Xizang Plateau - Minhaoxue Zou; Yujie Tao; Bohan Shi; Rong Xu; Rong Wang; Yongzhen Li; Rui Han; Derui Zhu (Current Microbiology, 2026)

A colorimetric/fluorescent/electrochemical tri-modal biosensor based on dual CRISPR/Cas12a system for detection of microRNA - Hehua Zhang; Huan Zhu; Hongmin Gao; Yang Zhou; Longbin Que; Shengzhong Rong; Hongkun Ma; Dong Chang; Hongzhi Pan (Analytica Chimica Acta, 2026)

A Galactose-Modified Light-Activatable Persulfurated Arene Fluorescent Probe for Targeted Imaging of Polarity and Viscosity in Liver Cancer Cells - Pan-Xin Ge; Yan Rong; Lu-Lu Sun; Yuqing Hu; Xianzhi Chai; Hai-Hao Han; Liangliang Zhu (Journal of Fluorescence, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Impact of human adherence level to control measures on cystic echinococcosis transmission - Xinmiao Rong; Fengyun Zhu (Mathematical Biosciences, 2026)

A Serpine1-F2-PAR1 axis facilitates apoptosis and disease severity during GCRV infection in grass carp - Yangyang Li; Liangming Chen; Bin Gui; Changchun Yu; Jinyan Lei; Yuxuan Shao; Haiping Liu; Zuoyan Zhu; Yaping Wang; Rong Huang (Fish & Shellfish Immunology, 2026)

Livestock grazing modulated the effects of flooding on ecosystem multifunctionality in the wetland of the lower Tumen River in Northeast China - Linguang Luan; Mingyue Pan; Yingqi Han; Qiong Han; Lin Yuan; Rong Liu; Weihong Zhu; Jingzhi Wang (Environmental Research, 2026)

Numerical simulation of fracture propagation and interwell frac-hit mechanism in deep shale gas infill wells - Yufeng Wang; Qiang Wang; Jinzhou Zhao; Yongquan Hu; Jianglong Wang; Juhui Zhu; Rong Wang; Xiaowei Li; Yu Yang (Engineering Geology, 2026)

Synergistic antifouling and organic removal using Fe/N co-doped biochar-modified ceramic membranes via in situ peroxymonosulfate activation - Rong Liu; Ye Zhu; Peng Ren; Jinge Fan; Yadong Wang; Mengwen Liu; Yabo Shang; Lu Xu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Chemical Engineering Journal, 2026)

Self-powered antimony oxide-coated palladium telluride/p-Silicon heterojunction DUV-MIR photodetector towards non-invasive diagnosis of diabetes - Jiayi Sun; Yuting Niu; Chen Rong; Zhikun Pang; Xinyi Han; Ningnuo Xiang; Lei Zhu; Xiaofang Li; Bo Peng; Cuicui Ling (Chemical Engineering Journal, 2026)

In vitro digestion and faecal fermentation of starch-lipid complexes with distinct crystalline forms prepared by extrusion-cooking - Chen Chao; Rong Sun; Yueming Zhu; Cuiping Wang; Jinglin Yu; Shujun Wang (Carbohydrate Polymers, 2026)

Aerosol optical depth in the Yellow River Basin during 2000-2023: Spatiotemporal variations and potential impacting factors - Rong Zhu; Youyan Jiang; Sipika Sundriyal; Bo Wang; Yulan Zhang (Atmospheric Environment, 2026)

Morphology and ultrastructure of the proventriculus in the mole cricket Gryllotalpa orientalis Burmeister, 1838 (Orthoptera: Gryllotalpidae) - Bai-Long Yang; Ling Zhu; Ya-Rong Gu; Huan Hu; Ying Miao (Arthropod Structure & Development, 2026)

Isolation, Genome Sequencing and Proteomic Analysis of a LiCl-Tolerant Bacillus rugosus E-4 Strain from East Taijinar Salt Lake on the Qinghai-Tibet Plateau - Rong Xu; Sha Du; Zihua Liu; Miaomiao Hu; Jianlan Wu; Hongxia Zhu (Current Microbiology, 2026)

Influence of winter-fallow management strategies on the stability of soil organic matter in a typical rice paddy region of southwestern China - Meihui Tian; Sihua Zhu; Bin Liu; Jitao Lv; Shanyi Tian; Rong Huang; Xiaohong Zuo; Meichun Duan; Yongguang Yin; Tao Jiang; Dingyong Wang; Xinping Chen (Agriculture, Ecosystems & Environment, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Grass carp TMEM33 promotes GCRV replication by targeting MAVS for degradation and suppressing host antiviral immune response - Qian Wang; Zichao Peng; Rong Deng; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He; Jing Lu (Marine Life Science & Technology, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Thioredoxin PgTRX acts as a protein elicitor to suppress green mold in citrus fruit via modulation of glutathione metabolism - Rong Zhu; Ou Chen; Yao Xu; Rui Huang; Wenjun Wang; Jian Ming; Kaifang Zeng (Postharvest Biology and Technology, 2026)

Aerobic biodegradation of acesulfame by sediment-enriched microbial consortia: Kinetics, pathway, and microbial mechanism - Xiaoxue Zhang; Jianwei Chen; Yuxuan Li; Rong Tang; Tianyue Zhu; Yong Yuan (Journal of Environmental Management, 2026)

The effects of water depth, temperature and seasonal water-column overturning on sediment-derived odorous volatile organic compounds of a ladder-step reservoir, Yiwu, China - Bo Gao; Junyu Ma; Jiahe Wang; Hongbin Zhu; Yangkang Fang; Qinggang Gong; Zhizheng Luo; Yi He; Rong Zhang; Cancan Jiang; Yongzhi Chi; Yanghui Xiong; et al. (Journal of Environmental Chemical Engineering, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

High-efficiency and rapid photocatalytic degradation of rhodamine B and tetracycline by BiOBr nanosheets under simulated solar light - Rong Wang; Weikun Zhu; Jiayi Hu; Siyang Liao; Cheng Chen; Baihang Chen; Shaobin Huang; Jiangyao Chen (Journal of Environmental Sciences, 2026)

An experimental insight into water-driven fracture of granite under coupled stress–temperature conditions - Taiwen Li; Lankai Liu; Rong Wang; Juhui Zhu; Zidong Fan; Xiaofang Nie; Li Ren; Qin Zhou (International Journal of Rock Mechanics and Mining Sciences, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Recent advances in biochar-based composite phase change materials - Pin Jin Ong; Reuben J. Yeo; Anqi Sng; Suxi Wang; Warintorn Thitsartarn; FuKe Wang; Junhua Kong; Rong Ji; Beng Hoon Tan; Dan Kai; Pei Wang; Jianwei Xu; et al. (Biomass and Bioenergy, 2026)

Chemical constituents from the twigs and leaves of Viburnum utile Hemsl. (Adoxaceae) and their taxonomic distribution - Dong-Mei Zhou; Lijin Jiao; Huai-Qin Liu; Bang-Quan Tang; Guo-Bo Xu; Qin-Feng Zhu; Xi-Rong Luo; Shang-Gao Liao; Ling-Ling Yu (Biochemical Systematics and Ecology, 2026)

The Cerebrovascular Reactivity Adjusted Fractional Amplitude of Low-Frequency Fluctuations Abnormalities in Middle Cerebral Artery Stenosis and Occlusive Disease - Liqing Zhang; Luoyu Wang; Xue Tang; Yidi Zhu; Rong Wang; Zhongxiang Ding (Translational Stroke Research, 2026)
This study investigated the variation characteristics of static fractional amplitude of low-frequency fluctuations (sfALFF) and dynamic fALFF (dfALFF) in Middle cerebral artery stenosis or occlusion(MCA-S) patients, and explored these two indicators alterations with cerebrovascular reactivity (CVR) correction. A total of 41 MCA-S patients and 50 matched controls underwent resting-state functional MRI and neuropsychological testing. Group differences in sfALFF/dfALFF were compared between the two groups, and the brain regions with differences in sfALFF/dfALFF with and without CVR correction were explored. Subsequently, partial correlation analysis was employed to evaluate the correlation between the abnormal brain regions and neuropsychological assessments. After CVR correction, MCA-S patients displayed increased sfALFF in Vermis_6, ipsilesional Cerebelum_8, Hippocampus, and other regions, alongside elevated dfALFF in Vermis_7, ipsilesional Hippocampus, and contralesional Cerebelum_8 ( P < 0.001). No significant correlations were found between fALFF metrics and neuropsychological scores post-Bonferroni correction. Uncorrected analyses showed group differences in sfALFF/CVR within ipsilesional Occipital_Mid and Parietal_Inf, while CVR-adjusted results revealed changes in ipsilesional Cerebelum_8 and contralesional Caudate ( P < 0.05). For dfALFF, uncorrected differences emerged in ipsilesional Postcentral, whereas CVR correction highlighted ipsilesional Temporal_Inf alterations. In summary, MCA-S patients exhibited abnormal neuronal activity associated with both sfALFF and dfALFF. With CVR correction, vascular confounding effects on the BOLD signal were partially mitigated, thereby enabling more accurate reflection of underlying neural activity alterations.

Influence of sample purity on landslide susceptibility mapping: a mutually exclusive stratified purity strategy based on the state-process consistency - Jiaying Zhu; Yuqian Yang; Shuangyun Peng; Zhiqiang Lin; Ziyi Zhu; Xianchun Pan; Xue Ding; Rong Jin (Bulletin of Engineering Geology and the Environment, 2026)
The quality and uncertainty of training samples are a critical bottleneck constraining the performance of machine learning in landslide susceptibility mapping (LSM). To address this, this study introduces a sample purity optimization framework based on state-process consistency (SPC). The framework utilizes two indices, SWCFD and CF-BE-HMD, combined with a mutually exclusive stratified purity strategy (MESPS), to systematically optimize the purity of the training samples. The framework was validated using data from Zhenxiong County, Yunnan Province, China. The results indicate that sample purity is the core variable influencing LSM model performance. The mutually exclusive sample group with the highest purity achieved AUC values of 0.92–0.93, markedly higher than those of other groups. High-purity landslide and non-landslide samples effectively suppressed the risk generalization effect caused by low-purity positive samples and overcame the risk conservatism problem induced by low-purity negative samples, resulting in clearer boundaries in the risk zonation. Therefore, only through bidirectional purification, which ensures that both positive and negative samples are highly representative, can these two extreme biases be maximally eliminated, leading to the generation of scientific, reliable, and balanced landslide susceptibility maps. This study offers a feasible solution to the sample quality bottleneck, providing a solid theoretical and empirical basis for shifting landslide modeling towards a quality-driven approach.

Chronic heat stress attenuates innate immunity and increases susceptibility to Aeromonas hydrophila in Siberian sturgeon (Acipenser baerii) - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Wei Wang; Hua Zhu (Aquaculture International, 2026)

Study on diagnosis of subclinical mastitis and identification of pathogens using electronic nose detection of cow’s milk - Fang Wang; Yujun Zhu; Enqiu Zhang; Rong Zhang; Hongwei Duan; Shuai Yang; Xianghong Du; Xingxu Zhao; Xiaofei Ma; Lihong Zhang; Junjie Hu (Computers and Electronics in Agriculture, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Establishing one-step hairy root transformation system in safflower using RUBY reporter - Rong Guo; Xuerui Zhang; Xu Jiao; Chunfeng Zhu; Jian Wei; Yun Zhu (Journal of Plant Physiology, 2026)

Metabolic depression drives discontinuous gas exchange in diapause pupae of Sericinus montelus (Lepidoptera: Papilionidae): a seasonal adaptation strategy - Quan-Hong Xiao; Rong-Wei Wu; Zhe He; Dao-Hong Zhu (Journal of Insect Physiology, 2026)

Spatiotemporal variations of chlorinated polycyclic aromatic hydrocarbons in Yellow Sea sediments: An eight-year field monitoring study - Xin Yang; Yunyong She; Qian Zhao; Dan Xu; Shenjie Li; Yueyao Yang; Guohua Zhu; Zhefu Yu; Junpeng Li; Bingcheng Lin; Minghui Zheng; Rong Jin (Journal of Hazardous Materials, 2026)

Synergistic transformation of alkylbisphenols (BPA, BPE, and BPF) mediated by ammonia-oxidizing bacteria and heterotrophic bacteria in nitrifying activated sludge - Hang Xu; Wenhui Zhang; Sicheng Zhu; Bingyu Shen; Xinyu Li; Bingqi Jiang; Lianhong Wang; Philippe F.X. Corvini; Max M. Häggblom; Rong Ji (Journal of Hazardous Materials, 2026)

Phosphate-modified attapulgite for efficient Pb(II) and Cd(II) removal: surface functionalization and adsorption mechanisms - Xinyao Zhang; Rong Yang; Wenxia Zhu; Di Meng; Xuanjie Huang; Zulin Wang; Bo Ma; Jun Yao; Wenjihao Hu (Environmental Research, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Biological and mineral amendments synergistically coordinate soil micro-food web to enhance multifunctionality - Baijing Zhu; Huaxiu Chen; Han Li; Qiang Zhu; Wenfeng Tan; Jiao Feng; Yu-Rong Liu (Applied Soil Ecology, 2026)

Rhizosphere fungal community and microbial networks shape N2O emissions and crop yield in a rice-rapeseed rotation system under varying nitrogen levels: A case study from Southwest China - Jin-meng Li; Rong Zhao; Tian-yang Ye; Cong-hua Zhu; Jin Chen; Ping Huang; Xue-qing Yang (Agriculture, Ecosystems & Environment, 2026)

Dietary fiber enhances the intestinal profile of beneficial commensal Bacteroides acidifaciens and modulates bile acid metabolism in T2DM mice - Rong Feng; Yulin Zhu; Qi Ge (Antonie van Leeuwenhoek, 2026)

Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.

Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

Butyrate supplementation in sows promotes offspring embryonic muscle development by upregulating HDAC-mediated H3K27ac levels and myogenic gene expression - Hao Zuo; Chen Li; Xiaoyu Niu; Zhibo Ma; Zhifeng Wu; Zeyang Gao; Liqian Sun; Yiming Jia; Mingfei Zhu; Litong Wang; Rong Zheng; Bo Zuo (Science China Life Sciences, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A novel strategy for controlling nitrite accumulation in fermented cabbage by regulating microbial community structure via cold plasma - Lin Zhu; Mengke Cheng; Yuan Wang; Xinyu Hu; Rong Wang; Biyue Yang; Xiang Xiao; Wei Wei (Food Control, 2026)

Microwave-assisted pyrolysis of dyeing sludge: Reaction kinetics, elemental transformation, and heavy metal migration - Dekai Fan; Rong Xiao; Wahab Nasarul; Chunbao Zhou; Yingwen Zhang; Bang Yao; Li Chao; Jianjun Dai; Gul Urooj; Yingrui Ning; Peng Zhu; Chen Chen; et al. (Chemical Engineering Journal, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Regulating coordination environment of vanadate cathode for ultralong lifespan zinc-ion batteries - Tingting Lv; Rong Li; Linyu Yang; Shuying Wang; Kunjie Zhu; Jiadong Wu; Hui Yao; Haibing Li; Kamal Toqtarhan; Hongyu Mi; Anqiang Pan (Chemical Engineering Journal, 2026)

Innovative utilization of waste printed circuit boards and coal gangue/ash for multifunctional glass-ceramics: structure-property insights via data-driven analysis - Yingwen Zhang; Lei Gao; Li Chao; Bang Yao; Dekai Fan; Chen Chen; Rong Xiao; Yingrui Ning; Peng Zhu; Urooj gul sandilo; Abeanezer Lukas Bassa; Nasarul Wahab; et al. (Chemical Engineering Journal, 2026)

Cofactor-coupled cytochrome P450 engineering enables high-level biosynthesis of asiatic acid in Saccharomyces cerevisiae - Yuan Zhu; Xiaoguang Yan; Weiguo Li; Yuan Zhong; Jianjun Qiao; Guang-Rong Zhao (Bioresource Technology, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Everything is everywhere, but everywhere is different: evidence from the phylogeography of asexual bdelloid rotifer Rotaria rotatoria species complex - Lingyun Zhu; Rong Huang; Sen Feng; Fan Gao; Meng Li; Hairong Lian; Zhizhong Li; Xinfeng Cheng; Mingbo Yin; Wei Zhang; Yilong Xi; Xianling Xiang (Hydrobiologia, 2026)

Reducing the Discrepancy in Quantifying the Temperature Dependence of Global Wetland Methane Emission - Han Hu; Ke Xue; Yishen Sun; Qing Zhu; Hans K. Carlson; Ruiwen Hu; Rong‐Xi Tan; Chao Qian; Weigen Huang; Jizhong Zhou; Jingdong Mao; Thomas W. Crowther; et al. (Global Change Biology, 2026)
Understanding the apparent temperature dependence of wetland methane emissions ( E M ) is critical for predicting climate‐carbon feedbacks, yet current estimates remain constrained by observational limitations and methodological inconsistencies. The inherent biogeographic heterogeneity of wetland ecosystems combined with sparse, unevenly distributed flux measurements introduces substantial uncertainty in characterizing spatial patterns of E M . This knowledge gap impedes accurate projections of wetland methane contributions under climate warming scenarios. Here, we develop a framework that integrates mixed‐effects models with artificial intelligence techniques to resolve scale‐dependent patterns in methane emission thermodynamics across global wetlands. Our unified framework demonstrates that only 73.6% (5th–95th quantiles: 71.8%–75.4%) of the global wetland area conforms to classical Arrhenius‐type temperature dependence. This framework can predict 69.5% (67.9%–71.1%) of the global wetlands with high confidence using the Mahalanobis distance and area of applicability tests. We quantify the weighted mean E M across high‐confidence predictable areas of 0.694 eV, with latitudinal differentiation: tropical (0.634 eV), temperate (0.678 eV), and boreal (0.745 eV) wetlands exhibit progressively stronger temperature responses. Ignoring these biogeographic variations could result in underestimation of projected end‐century methane emissions by 4.2%–13.3% across selected socioeconomic pathway scenarios. Our study refined the temperature sensitivity parameter in coupled climate‐carbon cycle models, thereby enhancing predictive accuracy of future global warming trends and informing strategic responses to climate change mitigation.

Single molecule force spectroscopy for evaluating inhibitors of SARS-CoV-2 variants of concern - Rong Zhu; Yoo Jin Oh; Peter Hinterdorfer (European Biophysics Journal, 2026)
The binding between the SARS-CoV-2 Spike protein and its cellular receptor ACE2 is essential for viral entry and infection and, therefore, represents a critical target for antiviral intervention. Single-molecule force spectroscopy (SMFS), conducted using atomic force microscopy (AFM), allows direct investigation of Spike–ACE2 interactions at the single-molecule level, providing insights into binding mechanisms not easily captured by conventional methods. This review discusses recent applications of SMFS to assess molecular inhibitors of Spike–ACE2 interactions, focusing specifically on soluble ACE2 and glycan-binding lectins (Clec4g, hCLEC4G, and engineered H84T-Banlec). These inhibitors demonstrated potent, concentration-dependent activity against multiple SARS-CoV-2 variants, including Delta and Omicron, achieving IC₅₀ values in the low nanomolar range (soluble ACE2: 0.25–0.38 nM; Clec4g/hCLEC4G: 36–58 nM; H84T-Banlec: 2.6–5.2 nM). Notably, single-molecule IC₅₀ measurements closely correlated with EC₅₀ values from cell-based assays, validating the physiological relevance and predictive capability of the SMFS method. Collectively, these findings underscore the utility of AFM-SMFS as a powerful approach for inhibitor evaluation and antiviral discovery, particularly for strategies targeting conserved structural features of the Spike protein to achieve broad-spectrum efficacy against current and emerging viral variants.

Chitosan-interpenetrated metal organic framework for targeted recovery of gold from gold-electroplating wastewater - Yihui Wu; Jiaxin Luo; Shixing Wang; Rong Zhu; Jianqiang Ye; Xinrui Yang; Xinni Tang; Guowei Luo (Water Research, 2026)

Plant-derived bioactive peptides in anti-aging applications: From molecular mechanisms to advanced delivery platforms - Xiyu Qin; Wentao Xu; Lili Qiu; Yixuan Li; Rong Liu; Longjiao Zhu; Xiaoyu Wang (Trends in Food Science & Technology, 2026)

Millennial rice cultivation shapes depth‑dependent organic carbon mineralization and microbial life strategies in saline paddy soils - Chaoyun Ying; Zhi Ma; Yue Li; Xuechi Rong; Ze Zhang; Guanjun Li; Shuang Wang; Tida Ge; Zhenke Zhu (Soil and Tillage Research, 2026)

Selective toxicity and molecular disruption induced by acetamiprid in the predator, Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae) - Naved Ahmad Ansari; Joko Pilianto; Mohd Amir; Abid Ali Soomro; Amr Abou El-Ela; Samar Mahmood; Saleem Javed; Wenwu Zhou; Zeng-Rong Zhu (Science of The Total Environment, 2026)

Intermittent blue light-dark cycles: A new strategy for enhancing triterpenoid production in medicinal Sanghuangporus vaninii - Yanjun Ma; Rong Li; Jiahui Li; Zilu Song; Fawen She; Xiaoyan Ma; Xuetai Zhu (Journal of Photochemistry and Photobiology B: Biology, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Development of green low-carbon denitrogenation process for EAF- reaction behavior and industrial performance of Ar-CH4 injection via hollow electrode - Xin Li; Guangsheng Wei; Ting Li; Shufeng Ye; Rong Zhu (Journal of Cleaner Production, 2026)

Cerium isotopic compositions of deep-sea sediments: implications for geochemical behavior of rare earth elements in the pelagic seafloor - Ganglan Zhang; Jianghao Bai; Mingyu Zhao; Pengcong Wang; Yangtao Zhu; Jun Cao; Hao Wu; Rong Xu; Gaowen He; Gangjian Wei; Yinan Deng (Geochimica et Cosmochimica Acta, 2026)

Electrochemical synthesis of H2O2 integrates reaction mechanisms, reaction media, mass-transfer effects, and device design - Lin Zhu; Rong Ma; Yixin Bai; Feng Li; Gao-feng Han; Yunfei Bu (Chemical Engineering Journal, 2026)

Corrigendum to “a sandwich-structured anisotropic conductive film with robust interfacial reliability and conductivity for functional electrical interconnections” [chemical engineering journal 505 (2025): 159721/CEJ_159721] - Yang Liu; Yan Pan; Zeyu Zheng; Hebin Zhang; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

Environmental impacts and optimization strategies for integrating carbon capture and anammox-based processes in municipal wastewater treatment under uncertain influent parameters - Rui Zhou; Ying Zhu; Qian Li; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Quantifying the effects of spatial characteristics of summer street vegetation on pedestrian thermal visual comfort and emotional well-being - Qiuchen Zhu; Hui Feng; Rong Chen; Hua Bai; Yifan Duan (Building and Environment, 2026)

Ginsenosides secreted by Panax notoginseng promotes the growth and pathogenicity of Fusarium oxysporum through enhancing antioxidant capacity - Lifen Luo; Rong Lu; Rong Yin; Guangxiang Tian; Yiwen Li; Guixiang Li; Hongwei Zhu; Jianqiang Miao; Jianjun Hao; Xili Liu; Shusheng Zhu; Min Yang (Plant and Soil, 2026)

Shear behavior of subglacial debris-clean ice interface: experimental study and constitutive modeling - Yixiang Song; Jiaheng Li; Hong Liu; Qiujie Meng; Rong Guo; Tantan Zhu; Wenzhu Ma (Bulletin of Engineering Geology and the Environment, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Wind information and electricity market design: An experiment - Chiara Lo Prete; Rong Rong; Anthony Kwasnica; Cody Hohl; Jiaxing Wu; Feng Zhu (The Electricity Journal, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Interaction of secreted protein PgSLP and citrus calmodulin-like protein CsCML27/44 in fruit disease defense - Yao Xu; Ou Chen; Rong Zhu; Rui Huang; Jian Ming; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Microbial mechanisms of biochar reducing methane emission in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Baoli Qin; Ting Yang; Rong Xu; Lingyu Zhu; Guangming Han; Leiming Wu; Siyu Li; Jianhua Bi; Shouhong Wang; Jiahong Zhang; et al. (Journal of Environmental Management, 2025)

New insights into the growth characteristics, bacterial interaction and spoilage contribution of Pseudomonas species in vacuum skin packaged beef - Jun Yang; Ge Rong; Rongrong Liang; Lixian Zhu; Yanwei Mao; Xin Luo; Yimin Zhang; Xiaoyin Yang (Food Packaging and Shelf Life, 2025)

Injectable adhesive hydrogel microspheres encapsulating VEGFA-high expression MSC exosomes for the treatment of intrauterine adhesions - Rong Ma; Zhengwei Sun; Zhihui Xu; Yuqing Jin; Yujia Zhou; Luoran Shang; Xueqiong Zhu (Chemical Engineering Journal, 2025)

Upcycling plastic waste into high-value gases via pulsed joule heating for economic and carbon benefits - Zitong Wan; Xuan Xie; Yunfeng Ma; Guohua Zhu; Rong Jin; Bingcheng Lin; Minghui Zheng (Chemical Engineering Journal, 2025)

Chameleon-inspired cellulose photonic gels toward multi-mode visual sensing and deep learning enhanced information encryption - Mengqing Luo; Jinrong Huang; Yun Wu; Qianyao Liu; Rong Yuan; Xiaohua Chang; Yutian Zhu (Chemical Engineering Journal, 2025)

A comprehensive review on tellurium extraction and recycling technologies from copper anode slime - Yuefeng Chen; Shixing Wang; Rong Zhu; Yihui Wu; Jiaxin Luo; Guowei Luo; Jian Liu; Libo Zhang (Chemical Engineering Journal, 2025)

Nanoengineered polymeric RNA nanoflowers for dual-pathway modulation and effective therapy for non-small cell lung cancer - Li Wang; Dongbin Guo; Yifei Shan; Luanbiao Sun; Rong Wang; Bingmei Wang; Jiyu Guan; Quan Liu; Runze Li; Changfeng Zhu; Yicheng Zhao (Chemical Engineering Journal, 2025)

Emerging trends in anticoagulation therapy: a bibliometric analysis of DOACs and endogenous coagulation pathway inhibitors - Zhe Zhu; Rong Huang; Hongli He; Rong Zhao; Xirui Li; Fangyan He; Dan Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Differential gene expression in the intestines of Chinese mitten crabs with three carapace colors - Qi Zhu; Maolei Wei; Xinxin Chen; Zhichao Rong; Dongran Yang; Xiaowu Chen; Xugan Wu (Molecular Biology Reports, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

RNA-binding protein HuR interacts with UFM1 mRNA to ameliorate chondrocyte inflammation, apoptosis and extracellular matrix degradation - LeXiang Li; Rong Zhou; ZhiPeng Yue; HaoBo Li; YaGuang Han; Lei Zhang; Jun Zhu (Functional & Integrative Genomics, 2025)

The high-affinity K+ transporter IbHAK5 enhances potassium ion absorption and improves root morphology in sweetpotato (Ipomoea batatas) - Rong Jin; Peng Zhao; Mengxiao Yan; Ming Liu; Weijuan Fan; Qiangqiang Zhang; Xiaoya Zhu; Jing Wang; Yongchao Yu; Jun Yang; Hongxia Wang; Zhonghou Tang (Transgenic Research, 2025)

Achnatherum inebrians tolerance to salt stress is linked with the changes of rhizosphere microbiome and root exudates - Ronggui Liu; Chao Wang; Jie Jin; Xiaoshan Zhu; Lanlan Chen; Yang Yang; Rong Zheng; Kamran Malik; Jianfeng Wang; Chunjie Li (Soil Ecology Letters, 2025)

A new model for describing black holes based on the essential relationship between electric field and gravitational field analysis - Rong-Pei Ding; Zhi-Hua Zhu (Applied Geophysics, 2025)

Long-term effects of common air pollutants and depression in middle-aged and older adults: a cohort study based in China - Qin Xiao; Qiang Zhu; Yixiao Jin; Rong Yu (Environment, Development and Sustainability, 2025)

Four new phenolic constituents from root barks of Paeonia ostii - Qian-Qian Meng; Yi Su; Shun-Yao Tong; Xing-Rong Peng; Jun-Chen Zhu; Ji-Kai Liu (Natural Product Research, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Carbon stabilization by iron plaque on rice roots: The role of oxygen loss - Liang Wei; Xuechi Rong; Hongzhao Yuan; Yongfu Li; Xiaorong Fan; Ning Ling; Zhenke Zhu; Bahar S. Razavi; Yakov Kuzyakov; Pil Joo Kim; Jianping Chen; Tida Ge (Soil Biology and Biochemistry, 2025)

A strain of mycovirus AaVV1 mediates hypovirulence of Alternaria species - Ya Rong Wang; Yi Chen; Chang Xin Li; Xiao Gang Li; Jun Zi Zhu; Jie Zhong (Pesticide Biochemistry and Physiology, 2025)

Competitive exclusion of insect parasitic fungi: Enhanced metabolite biosynthesis in Beauveria bassiana and fatty acid production in Metarhizium robertsii during host coinfection - Kexin Liu; Gen Li; Siying Wu; Yang Zhang; Rong Zhou; Cheng Lv; Xingcheng Yue; Zhuoran Zhu; Tianzi Zhou; Bo Huang; Yulong Wang (Pesticide Biochemistry and Physiology, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Quality or quantity of urban greenery: Which matters more to mental health? Evidence from housing prices in the Pearl River Delta - Qingyin Li; Rong Wu; Pengyu Zhu (Landscape and Urban Planning, 2025)

Performance evaluation of EAF dust-loaded rice straw biochar as the EAF foaming agent: Study on physicochemical properties and reduction behavior with slag - Chengjin Han; Guangsheng Wei; Qisheng Wang; Rong Zhu (Fuel, 2025)

Cloud-integrated microfluidic fluorescence sensing platform using UCNP/Fe3O4@Cu nanoprobes for simultaneous and on-site multi-pesticide residue detection with smartphone assistance - Lina Zhu; Rong Sun; Fei Gao; Gong Chen; Shuangshuang Liu; Qin Ouyang (Food Chemistry, 2025)

Fermentation-derived dihydroferulic acid from Cordyceps militaris binds AKT1 to protect intestinal epithelial health - Rong Huang; Jixing Gao; Zelin Wang; Jie Cai; Zhenjun Zhu; Qingping Wu; Juan Wang; Fen Zhang; Yu Ding (Food Bioscience, 2025)

Sustainable bipolar membranes with three-dimensional flower-like spherical MgAl-layered double hydroxides doped quaternized chitosan for accelerated water dissociation and durability - Ming Li; Jinyun Xu; Hongze Li; Xiaoqing Wang; Shijie Shang; Xiaoyan Wang; Sijia He; Yanyan Ji; Li Yang; Rong Kuang; Chenxin Hu; Wenju Zhu; et al. (Desalination, 2025)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Direct oxidation of trace methane to formaldehyde under ambient conditions by piezo-photocatalytic synergy - Qiyu Zhang; Li Rong; Yue Jiang; Zhiping Zhu; Xiaochang Lin; Yongzhen Ding; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2025)

Enhanced oxidation leaching of silver from zinc leaching residue via an electric field - Rong Zhu; Jianqiang Ye; Shixing Wang; Dawei Xiang; Yuefeng Chen; Yihui Wu; Guowei Luo; Jiaxin Luo; Chenxu Wang; Libo Zhang; Jian Liu (Chemical Engineering Journal, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Crop diversification improves productivity and soil health by regulating fungal diversity - Rui Li; Zhibin He; Peng He; Rong Yang; Dengke Ma; Yuan Li; Yangzhou Xiang; Weihao Sun; Xi Zhu; Zhixin Zhang (Soil and Tillage Research, 2025)

Multidimensional synergistic management of acid mine drainage: Constructing closed-loop technological systems bridging contamination control and resource circulation - Zhuang Ma; Lihong Zhou; Sen Wang; Shuai Zhu; Zeze Zhao; Rong Li; Tongtong Wang; Honghong Guo (Journal of Water Process Engineering, 2025)

Daily temperature fluctuations intensify the toxicokinetics and toxicodynamics of phenanthrene in Enchytraeus albidus (Oligochaeta), increasing overall toxicity risk - Naichuan Xiao; Ming Gao; Dong Zhu; Zifang Wang; Rong Huang; Lelin You; Tingting Zhang; Wencai Dai (Journal of Hazardous Materials, 2025)

Dual-nanostructured plasmonic Au-NS&NR/TiO2 for photothermal catalytic hydrogen production - Jianglin Tu; Jun Zhang; Hao Song; Xun Zhu; Dingding Ye; Yang Yang; Xiao Yan; Hong Wang; Rong Chen; Qiang Liao (Journal of Environmental Chemical Engineering, 2025)

Silica-centered crosslinking solid polymer electrolyte for sodium metal batteries - Jinfang Zhang; Rong Liu; Kexin Zhu; Wanyang Guo; Panpan Li; Huaxin Guo; Xiaofeng Li; Qingbing Xia (Chemical Engineering Journal, 2025)

Harnessing soybean okara for enhanced microbial production of indigoidine - Ziqiang Chen; Wenqing Liu; Shenyi Zhang; Yushen Song; Zixuan Zhang; Guanning Yao; Guang-Rong Zhao; Hongji Zhu; Di Zhang; Jianjun Qiao; Hui Zhao; Jiaheng Liu (Bioresource Technology, 2025)

Integrated Biofilm Modification and Transcriptional Analysis for Improving Fengycin Production in Bacillus amyloliquefaciens - Chun-Yang Cao; Zheng-Jie Hou; Ming-Zhu Ding; Geng-Rong Gao; Bin Qiao; Si-Yu Wei; Jing-Sheng Cheng (Probiotics and Antimicrobial Proteins, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

FKH domain-mediated nuclear FOXP3 suppresses gastric cancer malignancy via c-MYC/CDKN1A regulation, EMT inhibition, and PI3K/AKT signaling modulation - Yu Chen; Xia Zhao; Yuze Zhu; Ling Xu; Juanjuan Wang; Zheyi Chen; Hui Chen; Tingting Rong; Yanhui Ma; Yi Liu; Yunlan Zhou; Yingxia Zheng; et al. (Molecular and Cellular Biochemistry, 2025)

Accurate and simple determination of sediment redox capacity by a modified chemical probe method: Implications to contaminant remediation - Yuxi Lu; Rong Chen; Weijun Zhao; Peng Zhang; Shukui Zhu; Chenglong Yu; Songhu Yuan (Water Research, 2025)

Analysis of energy consumption and carbon emissions of electric arc furnace steelmaking using hydrogen-based direct reduced iron - Botao Xue; Guangsheng Wei; Biao Dong; Conejo Alberto N; Hongbin Wang; Rong Zhu (Process Safety and Environmental Protection, 2025)

Consortia of SQR9 mutant strains containing the luxS gene mutation can maintain higher functional stability than the wild type - Jingjing WANG; Lingxue MENG; Ying ZENG; Xinrui ZHU; Chuanyong TANG; Zhihui XU; Hongjun LIU; Rong LI; Qirong SHEN (Pedosphere, 2025)

Cytochrome P450-mediated biotransformation of octocrylene in Tetradesmus obliquus: Integrative insights from transcriptomics, proteomics, molecular docking, and density functional theory calculation - Jun-Jie Hu; Chang-Gui Pan; Xiang-Rong Xu; Feng-Jiao Peng; Shan Liu; Jiying Pei; Zhen-Zhu Liu; Hao Liang; Kefu Yu (Journal of Hazardous Materials, 2025)

Human activity driven spatial heterogeneity of pollutants in a highland river basin revealed by non-target screening and improved PBT evaluation: A case study from the Yalong River on the Qinghai-Tibet Plateau,China - Zhiyuan Ma; Shunlong Meng; Xin Gao; Hui Wan; Longxiang Fang; Lei Zhu; Zhonghua Li; Yuxiao Gao; Liping Qiu; Bo Rong; Chao Song (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Deciphering the preservative effects of protamine from Xinjiang Coregonus peled on grass carp (Ctenopharyngodon idellus) fillets during refrigerated storage: a perspective from the microbiome - Rong Zhang; Yanan Gao; Xiaoji Fan; Song Zhu; Tingzhang Wang; Lili Gao; Xueqin Zhao; Zhuang Ma; Yiling Fan; Dan Jiang; Shuyan Liu (International Journal of Food Microbiology, 2025)

Hydro-mechanical and homogenization behaviour of GMZ bentonite pellets/block assemblies upon hydration - Zhang-Rong Liu; Wei-Min Ye; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Geomechanics for Energy and the Environment, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

Yolk-dual shell structured dielectric-magnetic SiO2@C@void@Ni3ZnC0.7/C microspheres for boosting microwave absorption - Wei Ling; Peng Liao; Jiawei Zhu; Jianxin Wu; Caiwei Hu; Xianke Zhang; Jujun Yuan; Zuzhou Xiong; Xiurong Zhu; Chuicai Rong (Chemical Engineering Journal, 2025)

Biomembrane delivers neurotrophic factor for spinal cord injury recovery through microneedle patch - Bowen Zheng; Mingpai Ge; Jing Zhang; Tao Zhu; Yu Yi; Hongtao Rong (Chemical Engineering Journal, 2025)

The application of hyper dose drug derived cell vehicles theory in gouty arthritis: Phoenix nirvana — A non-living mesenchymal stem cell drug delivery system - Chengran Wang; Xinao Rong; Tianqi Dong; Jinqi Zhu; Fangruyue Wang; Pu Shao; Jinlan Jiang (Chemical Engineering Journal, 2025)

Enhanced atrazine mineralization using periphyton pretreated with zero-valent iron-activated peroxydisulfate - Huibin Niu; Qian Tao; Rong Zhu; Haitao Li; Yonglin Chen; Yu Hu; Zuliang Chen; Yonghong Wu; Yingping Huang; Cilai Tang (Chemical Engineering Journal, 2025)

A synergistic water-saving strategy combining stage-specific irrigation and application of exogenous thiamine enhances drought resistance of Xinjiang cotton - Fuxiang Zhao; Linjie Xia; Simin Sun; Hang Li; Yuxuan Rong; Yuxin Wang; Xuwen Wang; Xianhui Kong; Longfu Zhu; Xianlong Zhang; Yu Yu; Xiyan Yang (Plant and Soil, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Development of dCAPS markers for sdhB mutants in fungicide-resistant Botrytis cinerea isolates - Rong Zeng; Ping Gao; Lihui Xu; Ya’nan Yuan; Yufei Han; Jiaxi Tian; Yuhong Wei; Shigang Gao; Zhiwei Song; Pu Zhu; Fuming Dai (Journal of Plant Pathology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

A heterogeneous ensemble landslide susceptibility assessment method based on InSAR and geographic similarity extended landslide inventory - Youchen Zhu; Huan Chen; Deliang Sun; Xing Zhu; Qin Ji; Haijia Wen; Qiang Zhang; Rong Wu (Gondwana Research, 2025)

Dynamic performance tests and multi-parametric refinement models of high-energy dissipation viscoelastic materials for seismic performance enhancement of engineering structures - Yao-Rong Dong; Zhao-Dong Xu; Lihua Zhu; Bao-Shun Wang; Yang Yang; Yu Cheng (Engineering Structures, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Electricity generation property in portable direct formate fuel cells (DFFCs) with polyacrylamide hydrogel - Qiusen Wang; Jianmeng Pang; Yang Yang; Xun Zhu; Dingding Ye; Rong Chen; Qiang Liao (Chemical Engineering Journal, 2025)

Histopathological Insights into Demyelination and Remyelination After Spinal Cord Injury in Non-human Primates - Junhao Liu; Zucheng Huang; Kinon Chen; Rong Li; Zhiping Huang; Junyu Lin; Hui Jiang; Jie Liu; Qingan Zhu (Neuroscience Bulletin, 2025)

Parerythrobacter aurantius sp. nov., a Member of the Family Erythrobacteraceae Isolated from a Coastal Breakwater Stone - Yang Liu; Tao Pei; Juan Du; Ming-Rong Deng; Honghui Zhu (Current Microbiology, 2025)

Understanding the delayed onset of the South China Sea summer monsoon in CMIP6 models - Jie Yang; Shaobo Qiao; Xueying Wang; Rong Deng; Shankai Tang; Xian Zhu; Wenjie Dong (Climate Dynamics, 2025)

The structure and assembly of the epiphytic bacterial community of Saccharina japonica during the field cultivation period - Chun Wang; Shanshan Wang; Zhenhua Wang; Huabin Shao; Xiaojun Rong; Jie Li; Ming Zhu; Yongwei Yan (Algal Research, 2025)

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Glycoside hydrolase PgGal31A inhibits citrus blue mold via modifying cell wall components - Rong Zhu; Ou Chen; Yao Xu; Jian Huang; Huali Wang; Lili Deng; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Vanadium-bearing shale beneficiation pre-enrichment: Selective flotation separation of garnet and quartz in an acidic environment using a dodecylamine–sodium fluosilicate system - Siqin Zhu; Guohua Ye; Qi Zuo; Xuanxiong Kang; Yun Zhang; Xinyue Xiang; Yiyang Rong; Changxu Song (Minerals Engineering, 2025)

Associations between serum trace elements and biological age acceleration in the Chinese elderly: A community-based study investigating the mediating role of inflammatory markers and the moderating effect of physical activity - Yan Wang; Wenyuan Zhu; Tao Zhang; Qingping Liu; Mengqi Zou; Yujia Xie; Mengruo Wang; Tian Shuai Wang; Yaxian Pang; Tao Jing; Rong Zhang (Journal of Hazardous Materials, 2025)

Analysis of CO2 emission and energy consumption in CCUS for steel-chemical joint production - Huapeng Yang; Chao Feng; Tao Lin; Rong Zhu; Kai Dong; Guangsheng Wei; Mingwei Tu; Fuhai Liu; Ziheng Zhao; Xin Ren; Chunyang Wang (Journal of Environmental Management, 2025)

Does greater molecular diversity in soil organic matter imply greater persistence: Insights from molecular and multi-property analyses in Western China - Shanyi Tian; Sihua Zhu; Joeri Kaal; Jitao Lv; Rong Huang; Tongwen Zhang; Xiaolei Su; Yongguang Yin; Tao Jiang; Dingyong Wang (Geochimica et Cosmochimica Acta, 2025)

Sustainable production of phloretin using multi-dimensionally adjustable acidic deep eutectic solvents as multifunctional solvents for green and efficient valorization of Malus plant pruning waste - Rong Wu; Lu Zhang; Kehong Liang; Feng Zhu; Longxin Lai; Jun Cao; Pengfei Yu; Fuliang Cao; Erzheng Su (Food Bioscience, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Ultrasound-mediated FAK-targeted nano-sapper for tumor extracellular matrix remodeling to potentiate cancer immunotherapy - Rong Huang; Beibei Zhang; Ge Chen; Yingying Zhao; Ruili Wang; Haohui Zhu; Shaobo Duan; Lianfeng Mo; Zesheng Li; Xu Zhang; Lianzhong Zhang (Chemical Engineering Journal, 2025)

Enhanced ecological risks of pollutant-adsorbed engineered environmental particles to soil microorganisms - Quan Chen; Yue Zhang; Wan-Rong Zhang; Yu Huang; Min Wu; Hong-Zhe Li; Yi-Yue Zhang; Yi-Fei Wang; Dong Zhu; Philippe Frangois-Xavier Corvini; Bo Pan (Chemical Engineering Journal, 2025)

Identification of Mood Disorders Causal Genes by Integrating the Brain Proteome and Transcriptome - Rong-kun Zhu; Hong-jian Zhou; Jun Shi; Ling Ge; Yi Lin; Wen-hao Yin; Hui Zeng; Xiong-wei Wang (Molecular Neurobiology, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Carbon footprint of shrimp (Litopenaeus vannamei) cultured in recirculating aquaculture systems (RAS) in China - Fan Rong; Hui Liu; Jianxin Zhu; Gaoju Qin (Journal of Cleaner Production, 2025)

Nitrogen-doped graphene quantum dots induce the construction of a sulfur vacancy-rich CaIn2S4/NGQDs photocatalyst with a thin layer for achieving efficient photocatalytic degradation - Jialei Hui; Rong Wu; Yali Zhu; Zhilong Zhang; Shunhang Wei (Journal of Environmental Chemical Engineering, 2025)

Recent advances in low-temperature phase change materials for cold chain logistics - Xiang Yun Debbie Soo; Pin Jin Ong; Yee Kiat Zachary Lim; Suxi Wang; Warintorn Thitsartarn; FuKe Wang; Junhua Kong; Rong Ji; Nikodem Tomczak; Beng Hoon Tan; Pei Wang; Jianwei Xu; et al. (International Journal of Refrigeration, 2025)

Combining soy protein isolate and sorbitol as cryoprotectants for portuguese oysters (Crassostrea angulata) and investigating the effect on ice crystal damage - Chao-Kai Chang; Yi-Feng Kao; Huey-Jine Chai; Pei-Rong Liang; Wei-Lun Zhu; Kai Shyu; Ratna Sari Listyaningrum; Chang-Wei Hsieh (Food Chemistry, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Divergent effects of biomass-derived carbon dots application and sweetpotato planting on accumulations of soil microbial necromass carbon in Vertisol - Jing Wang; Meng Zhu; Xiaoya Zhu; Qiangqiang Zhang; Yongchao Yu; Peng Zhao; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2025)

Effects of aerobic exercise and cardiorespiratory fitness on white matter free water fraction in older adults: a 1-year randomized controlled trial - Takashi Tarumi; Junyeon Won; Tsubasa Tomoto; Norman Scheel; David C. Zhu; John Ashley; Karen M. Rodrigue; Kristen M. Kennedy; Denise C. Park; Rong Zhang (GeroScience, 2025)

Aloe gel polysaccharides and ascorbic acid promote collagen synthesis in mirror carp (Cyprinus carpio var. specularis) - Rong Zhang; Xiaowen Wang; Lili Liu; Huijuan Li; Hua Zhu (Aquaculture, 2025)

Genomic and antimicrobial resistance profiles of Clostridium perfringens isolated from pets in China - Mingjin Fang; Yuan Yuan; Xin Tian; Ying Liu; Ke Wu; Yanyan Zhu; Likun Zhang; Edward M. Fox; Ruichao Li; Li Bai; Menghan Li; Guerrino Macori; et al. (Veterinary Microbiology, 2025)

Evaluating soil dissolved organic matter as a proxy for soil organic matter properties across diverse ecosystems - Shanyi Tian; Songbo Yao; Sihua Zhu; Peng Li; Tongwen Zhang; Xiaolei Su; Rong Huang; Yongguang Yin; Jitao Lv; Tao Jiang; Dingyong Wang (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Development of a novel fluorescent probe for the detection of glyphosate in food and water samples and the construction of a smartphone-assisted platform - Xiaodi Rong; Caiyun Liu; Fengli Hou; Xin Zhao; Zhongpeng Wang; Baocun Zhu (Food Chemistry, 2025)

BFRP bars reinforced geopolymer-based coral aggregate concrete beams with sustainable and high seawater erosion resistance: Flexural durability, economic, and ecological analysis - Bai Zhang; Hong Zhu; Zhiyuan Yang; Yao-Rong Dong (Engineering Structures, 2025)

Thermosensitive poly (NVCL-co-GelMA) nanogels as a delivery platform for rectal administration of 5-ASA in ulcerative colitis - Rongjiao Sun; Limei Zhu; Xianzhu You; Rong Chen; Jiante Li; Rongrong Pan; Yueqi Jin; Hua Zhou; Ying Tan; Jiajia Dong; Wanle Hu (Chemical Engineering Journal, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Two novel mitoviruses coinfecting the fungus Colletotrichum karstii - Wei Zhang; Jie Zhong; Jun Zi Zhu; Yi Chen; Ya Rong Wang (Archives of Virology, 2025)

Establishment of different artificial infection method models for grass carp reovirus - Hanyue Wang; Yongming Li; Qian Wang; Bin Gui; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang; Libo He (Aquaculture, 2025)

Development of a multiplex PCR assay for detection of Riemerella anatipestifer serotype 1 and serotype 2 strains - Mengsi Wu; Rong Guo; Meitong Chen; Min Zhu; Zongchao Chen; Chan Ding; Shengqing Yu (Veterinary Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Paleoproterozoic orogenic event in the western North China Craton: Insights from zircon U-Pb-Lu-Hf isotopes and geochemistry of meta-supracrustal rocks in the Beidashan complex, Alxa block - Yi-Wei Rong; Wen-Bin Zhu; Xi Wang; Jun-Yue Zhu; Xiao Hu (Precambrian Research, 2025)

Three new maaliane-type sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Sheng-Run Guo; Hou Zhu; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry Letters, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

The process, mechanisms and regulation of Cu electrolyte sulfidation based on spectroscopy direct determination towards high-purity Cu recovery - Guangbin Zhu; Linhua Jiang; Ning Duan; Yong Liu; Liye Bao; Rong Zhang; Xiaolu Sun; Shaoshuai Sheng; Hao Jin (Journal of Environmental Chemical Engineering, 2025)

Determination of the appropriate extraction method for bound aroma compounds from strawberry and analysis of aroma substances in strawberry fruits of different varieties and developmental stages - Li-Xia Sheng; Xiang-Rong Li; Xing-Ming Zhu; Hao Zhu; Jian-Qiang Yu (Food Chemistry, 2025)

Climate warming will significantly affect future restoration and level of ecosystem services in Lake Erhai - Bo Qin; Min Xu; Kexin Zhu; Yanjie Zhao; Enlou Zhang; Rong Wang (Ecological Modelling, 2025)

Archaeal and Bacterial Communities Within the Wetland Alkaline Har Lake of the Qinghai-Xizang Plateau - Yujie Tao; Bohan Shi; Minhaoxue Zou; Lijuan Qiao; Rong Wang; Derui Zhu; Rui Han (Current Microbiology, 2025)

Overexpressing IbHAK5 increases drought stress tolerance in transgenic sweetpotato - Rong Jin; Peng Zhao; Qiangqiang Zhang; Ming Liu; Xiaoya Zhu; Jing Wang; Yongchao Yu; Zhonghou Tang (Plant Biotechnology Reports, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Efficient uranium(VI) recovery from fluorinated wastewater via deferiprone ligand complexation - Juanlong Li; Yezi Hu; Zewen Shen; Huihui Jin; Rong He; Wenkun Zhu; Guixia Zhao; Zhuoyu Ji; Bin Ma; Xiangke Wang (Water Research, 2025)

Study on hydrocarbon retention and expulsion of kerogen based on centrifugal swelling method - Tian Liang; Feng Zhu; Zhao-Wen Zhan; Xiao-Hui Lin; Yan-Rong Zou; Ping’an Peng (Organic Geochemistry, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Electrochemical behavior and the mechanism of nickel ion removal during zinc sulfate electrolysis via ultrasonic purification - Jianqiang Ye; Shixing Wang; Rong Zhu; Likang Fu; Jian Liu; Genwei Zhang; Guo Lin (Journal of Water Process Engineering, 2025)

Regulation of ethanol production from anaerobic fermentation of food waste using aromatic alcohol-based quorum-sensing molecules - Rong Ma; Zhuoshen Huang; Yi Jiang; Anqi Zhao; Guangwei Yu; Changquan Lin; Langping Zhu; Xiaozhi Zhang; Xiaotian Li; Chunming Wang (Journal of Environmental Management, 2025)

Epigenetic nanoplatform for synergistic immune activation and immunogenicity restoration enhancing cancer radio-immunotherapy - Zhenhu He; Xiaopei Peng; Jiong Li; Yaning Zhu; Xuan Zhang; Junhong Duan; Jing Ni; Mengtian Ma; Juan Wang; Zhenguo Liu; Bin Feng; Wenbin Zeng; et al. (Chemical Engineering Journal, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Recent advancements in cation-intercalated vanadium oxide cathode materials for zinc-ion batteries - Kunxuan Li; Rong Li; Tiantian Guan; Lei Wang; Lingling Xie; Qing Han; Xuejing Qiu; Xiaoyu Cao; Limin Zhu (Chemical Engineering Journal, 2025)

Drivers and spatial distribution of soil organic carbon and total nitrogen in China’s drylands - Shihang Zhang; Yusen Chen; Bo Zhu; Yongxing Lu; Hao Guo; Xing Guo; Ye Tao; Jing Zhang; Xiaoying Rong; Benfeng Yin; Yongxin Zang; Xiaobing Zhou; et al. (CATENA, 2025)

Study on the pyrolysis kinetics of rice husk catalyzed by zinc-containing oxides in electric arc furnace dust - Chengjin Han; Guangsheng Wei; Qisheng Wang; Rong Zhu; Fuhai Liu (Biomass and Bioenergy, 2025)

Transcutaneous Auricular Vagus Stimulation Attenuates LPS-Induced Depression-Like Behavior by Regulating Central α7nAChR/JAK2 Signaling - Junying Wang; Yu Wang; Yu Chen; Jinling Zhang; Yue Zhang; Shaoyuan Li; Haohan Zhu; Xingke Song; Liwei Hou; Lei Wang; Yifei Wang; Zixuan Zhang; et al. (Molecular Neurobiology, 2025)

Foliar-Applied Carbon Dots Confer Enhanced Low Phosphorus Tolerance in Sweetpotato Seedling - Xiaoya Zhu; Jing Wang; Peng Zhao; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Journal of Soil Science and Plant Nutrition, 2025)

Effects of crop rotation on plant- and microbial-derived carbon within particulate and mineral fractions in paddy soils - Yalin Yu; Ningxuan Zhu; Ying Ren; Menghan Dong; Guofeng Sun; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Agriculture, Ecosystems & Environment, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

A NIR fluorescent probe based on carbamoyl oxime with high specificity for detecting ferrous ions in food and in vivo - Caiyun Liu; Tingyi Yan; Tingting Fu; Kun Wang; Xiaodi Rong; Xueting Liu; Yao Wang; Xinyu Cai; Wenlong Sheng; Baocun Zhu (Food Research International, 2025)

A sandwich-structured anisotropic conductive film with robust interfacial reliability and conductivity for functional electrical interconnections - Yang Liu; Yan Pan; Zeyu Zheng; Hebin Zhang; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

An HRP-integrated CRISPR/Cas12a biosensor towards chair-side diagnosis for Porphyromonas gingivalis - Ningning Pi; Rong Xiang; Lu Zhu; Yi Li; Xuan Wu (Biotechnology Letters, 2025)

Sweet spot prediction and technology application of coalbed methane development in Tiaohu-Malang depression of Santanghu Basin - Yue Chen; Haoran Zhu; Xinggang Wang; Gaoxiang Rong; Qiqi Lei; Chenlu Tang; Jinbo Shi; Zan Liu (Arabian Journal of Geosciences, 2025)

Analysis of extreme water levels on Feiyun River (Rui’an section) based on peaks-over-threshold (POT) model - Zipeng Qin; Yan Tian; Yanji Wei; Zhenglin Chen; Xiaoying Zhu; Qianfu Chen; Weixing Huang; Rong Yu; Xiang Cheng (Hydrological Sciences Journal, 2025)

Aphid-resistant alfalfa cultivar minimizes the survival of spotted alfalfa aphid through upregulating plant defense compounds - Kaihui Zhu; Neng Zhang; Daogang Zhang; Cai Ni; Rong Liu; Wunan Che; Ullah Hidayat; Xiongbing Tu (Crop Protection, 2025)

Migration and risk assessment of heavy metals from swine manure in an organic fertilizer - soil - ryegrass - rex rabbit system: Based on field trials - Xiaoxia Hao; Kai Liu; Li Zhu; Li Rong; Dongmei Jiang; Lin Bai (Science of The Total Environment, 2025)

Debaryomyces nepalensis enhances suberin deposition in citrus fruit wound by facilitating the synthesis of cinnamic acid and its derivatives - Jian Huang; Qi Chen; Ou Chen; Xiaoquan Gao; Rong Zhu; Rui Huang; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Selective recovery of Cu and efficient removal of As(V) from Cu electrolyte via four-stage continuous coupled sulfide precipitation - Hao Jin; Linhua Jiang; Ning Duan; Jinyu Wang; Xiaolu Sun; Yong Liu; Guangbin Zhu; Liye Bao; Rong Zhang (Journal of Cleaner Production, 2025)

Preparation and performance evaluation of an efficient microbial dust suppressant for dust control in disturbed areas of blast piles in open-pit coal mines - Jie Chen; Haoran Wang; Yi He; Rong Liu; Chuanhui Zeng; Kunyu Yan; Junpeng Zhu (Journal of Environmental Management, 2025)

Protecting anthocyanins of postharvest blueberries through konjac glucomannan/low-acyl gellan gum coatings contained thymol microcapsule during low-temperature storage - Jing Xie; Dur E. Sameen; Zhenkun Xiao; Huiyan Zhu; Yunya Lai; Tingting Tang; Xingyu Rong; Fengmei Fu; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Isolation, structural elucidation and biosynthetic pathway of bioactive prenyl quinone compounds from Panus lecomtei based on untargeted metabolomics combined with molecular networking - Si-Xian Wang; Bao-Song Chen; Zi-Juan Zhang; Shi-Rong Zhu; Xiao-Ling Wang; Gao-Qiang Liu (Food Chemistry, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

Energy absorption characteristics and auxetic effect of novel elliptic-arc re-entrant honeycomb structures - Tang Yuxin; Zhong Yifeng; Zhu Yilin; Liu Rong (Engineering Structures, 2025)

Enhanced performance and stability of sulfite/sulfide-assisted photocatalytic fuel cell with CdS@TNTs/Ti mesh photoanode - Yuxin Liu; Youxu Yu; Jinwang Li; Xun Zhu; Dingding Ye; Yang Yang; Zhefei Pan; Rong Chen; Qiang Liao (Chemical Engineering Journal, 2025)

MOFs meets wood: Renewable, self-supporting carbon-based composites for electromagnetic interference shielding with heat-resistant and electrothermal management - Yujun Rong; Xin Zhou; Shaohua Jiang; Wenkai Zhu; Hanwei Wang; Baokang Dang; Qingfeng Sun; Xiaofan Ma (Chemical Engineering Journal, 2025)

Enriching bottom acceptors for high-performance inkjet-printed organic solar cells - Xingze Chen; Lifeng Sang; Yuanyuan Jiang; Yiyu Chen; Qing Zhang; Rong Huang; Fengqi Guo; Guanghao Lu; Xiaozhang Zhu; Qi Chen; Chang-Qi Ma; Qun Luo (Chemical Engineering Journal, 2025)

Efficient preparation of cycloamylose from potato starch using recombinant 4-α-glucanotransferase - Yan Huang; Rong Zhu; Jiehu Liu; Xueyi Qiao; Bo Xu; Lei Wang; Lingqia Su (Systems Microbiology and Biomanufacturing, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Characterization of a Novel Tn7-like Transposon Carrying blaDHA-1 in Providencia stuartii MF1 Isolated from Swine Wastewater - Shijie Ou; Xinyi Tian; Zhen Zhang; Lingjia Zhu; Rong Wang; Guangxiang Cao; Jiafang Fu; Peipei Zhang (Current Microbiology, 2025)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part II: Madden–Julian oscillation - Zhen Fu; Yi Zhang; Xiaohan Li; Congwen Zhu; Hongbo Liu; Xinyao Rong; Chengming Li (Climate Dynamics, 2025)

Soil properties, climate, and topography jointly determine plant community characteristics in marsh wetlands - Lin Yuan; Jingzhi Wang; Rong Liu; Yuqi Tang; Di Wu; Ri Jin; Weihong Zhu (Journal of Plant Research, 2025)

A Meta‐Analysis of Bycatch Mitigation Methods for Sea Turtles Vulnerable to Swordfish and Tuna Longline Fisheries - Hao Yan; Cheng Zhou; Eric Gilman; Jie Cao; Rong Wan; Fan Zhang; Jiangfeng Zhu; Liuxiong Xu; Liming Song; Xiaojie Dai; Siquan Tian (Fish and Fisheries, 2025)
Fisheries bycatch poses one of the most significant threats to sea turtles. Although various methodologies have been developed to mitigate sea turtle bycatch in swordfish and tuna longline fisheries, the effectiveness and interactions remain uncertain. In this study, we conducted a comprehensive meta‐analysis, encompassing 41 studies focused on sea turtles and 36 studies on tunas, swordfish and sharks, all derived from well‐controlled experimental research in swordfish and tuna longline fisheries. The objective was to systematically evaluate the relative effectiveness of species‐specific mitigation strategies for sea turtles, particularly examining the impact of circle hooks and fish bait as alternatives to conventional longline fishing practices. While a nuanced hierarchy, characterised by species‐specific patterns, was observed among the mitigation measures, circle hooks demonstrated great promise in reducing bycatch of loggerhead, olive ridley and leatherback turtles, with minimal impact on the catch rates of tuna, swordfish and sharks. We highlighted the broader applicability of fish bait in minimising sea turtle bycatch, noting that the effectiveness of bait may overlap with that of hooks, potentially making the additional benefits of the hooks less evident. The study also revealed regional variations in the effectiveness of these methods, emphasising the need for more detailed data collection. Given current data limitations that restrict extensive meta‐analyses, a series of small‐sample studies with promising innovations, exemplified by circle hooks with a wire appendage and blue‐white lights, necessitates in‐depth investigation and field tests.

Amelioration impact of gut-brain communication on obesity control by regulating gut microbiota composition through the ingestion of animal-plant-derived peptides and dietary fiber: can food reward effect as a hidden regulator? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2024)

Spatial Sequential Matching Enhanced Underwater Single-Photon Lidar Imaging Algorithm - Qiguang Zhu; Yuhang Wang; Chenxu Wang; Tian Rong; Buxiao Li; Xiaotian Ying (Journal of Marine Science and Engineering, 2024)
Traditional LiDAR and air-medium-based single-photon LiDAR struggle to perform effectively in high-scattering environments. The laser beams are subject to severe medium absorption and multiple scattering phenomena in such conditions, greatly limiting the maximum operational range and imaging quality of the system. The high sensitivity and high temporal resolution of single-photon LiDAR enable high-resolution depth information acquisition under limited illumination power, making it highly suitable for operation in environments with extremely poor visibility. In this study, we focus on the data distribution characteristics of active single-photon LiDAR operating underwater, without relying on time-consuming deep learning frameworks. By leveraging the differences in time-domain distribution between noise and echo signals, as well as the hidden spatial information among echo signals from different pixels, we rapidly obtain imaging results across various distances and attenuation coefficients. We have experimentally verified that the proposed spatial sequential matching enhanced (SSME) algorithm can effectively enhance the reconstruction quality of reflection intensity maps and depth maps in strong scattering underwater environments. Through additional experiments, we demonstrated the algorithm’s reconstruction effect on different geometric shapes and the system’s resolution at different distances. This rapidly implementable reconstruction algorithm provides a convenient way for researchers to preview data during underwater single-photon LiDAR studies.

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Precipitation patterns strongly affect vertical migration and methylation of mercury in legacy contaminated sites - Xujun Liang; Zhi-Cheng Hu; Yu-Rong Liu; Cunbin Gao; Yi Zhang; Yun-Yun Hao; Lijie Zhang; Jiating Zhao; Lizhong Zhu (Water Research, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Cascading impacts of nitrogen deposition on soil microbiome and herbivore communities in desert steppes - Jingxi Liu; Mengmeng Zhu; Xiangfeng Shi; Cang Hui; Yurong Sun; Rong Zhang; Decai Jin; Zhihong Li; Honghao Chen; Zihua Zhao (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Transcription factor CcbHLH66 regulates mandarin fruit coloration via modulating the expression of chlorophyll degradation related genes CcRCCR and CcNYC - Huali Wang; Qian Liu; Shufang Deng; Jialin Chen; Jin Han; Rong Zhu; Kaifang Zeng; Lili Deng (Postharvest Biology and Technology, 2024)

Biological nitrogen fixation in paddy soils is driven by multiple edaphic factors and available phosphorus is the greatest contributor - Tianlong HU; Yanhui ZHANG; Hui WANG; Haiyang JIN; Benjuan LIU; Zhibin LIN; Jing MA; Xiaojie WANG; Qi LIU; Hongtao LIU; Zhe CHEN; Rong ZHOU; et al. (Pedosphere, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Effect of zero-valent iron and magnetite on mitigating sulfate and lincomycin stress in anaerobic digestion: microbial succession and antibiotic resistant genes removal - Jing Xie; Jiaxin Zhu; Bolin Min; Rong He; Wenbiao Wang; Li Xie (Journal of Water Process Engineering, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Applicability analysis of comprehensive drought index based on GRACE data in ten major river basins in China - Rong Wu; Zijun Wang; Chenfeng Cui; Yongxiang Li; Miao Tang; Jiangdong Chu; Renjie Xv; Chenrui Zhu; Shuo Wang; Yuli Li; Chengyuan Zhang; Zhannan Huang (Journal of Hydrology, 2024)

Integrative transcriptomic analysis reveals a broad range of toxic effects of triclosan on coral Porites lutea - Hao Liang; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Rong-Gui Zhu; Chao-Yang Zhou; Zhen-Zhu Liu; Kefu Yu (Journal of Hazardous Materials, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Mapping key areas to protect high-value and high-vulnerability groundwater from pollution load: Method for management - Guanhua Zhu; Pengwei Xue; Xiaofang Wu; Bing Zhang; Baocai Tong; Yuanzheng Zhai; Ganghui Zhu; Rong Ma (Journal of Environmental Management, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

A novel amidoxime-functionalized covalent organic framework adsorbent for efficient lead ion removal: Synthesis and adsorption mechanism - Yuefeng Chen; Shixing Wang; Dawei Xiang; Manying Zhu; Xiang Liu; Rong Zhu; Hongliang Liu; Likang Fu (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Effect of solution plasma process on microorganism sterilization, physicochemical properties and nutrients of milk - Haifeng Rong; Yang Yu; Baiqing Zhang; Dongbing Tao; Tingyu Zhu; Dongge Wu; Fengming Ma (Food Chemistry, 2024)

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Responses of yield, CH4 and N2O emissions to ratoon rice cropping and different management practices - Haiyang Yu; Rong Zhu; Xuechen Zhang; Xiangtian Meng; Chao Kong; Guangbin Zhang; Xinhui Liu; Yaying Li; Yongxiang Yu; Huaiying Yao (Field Crops Research, 2024)

Engineered multienzyme-mimicking 2D bismuthene catalytic nanotriggers enable cascade enzyodynamic-boosted and synergistic GPX4/FSP1-mediated ferroptosis amplification for cancer radiosensitization - Yipengchen Yin; Li Zhu; Tiaoyan Jiang; Rong Chai; Ya Zhang; Tianyu Li; Kai Wang; Sheng Wang; Qin Zhang (Chemical Engineering Journal, 2024)

Long-lasting Zn metal anode coated with an industrially available amorphous InGaZnO layer - Jiadong Wu; Linyu Yang; Shuang Zhou; Shuying Wang; Ablat Abliz; Rong Wu; Kunjie Zhu; Xiaolong Yao; Haibing Li; Jun Wang; Hongyu Mi; Jie Li; et al. (Chemical Engineering Journal, 2024)

A compound heterozygous mutation of ERCC8 is responsible for a family with Cockayne syndrome - Meng-Wei Liu; Cheng-Feng Hu; Jie-Yuan Jin; Rong Xiang; Liang-liang Fan; Ya-Li Li; Lei Zhu (Molecular Biology Reports, 2024)

A potentially New Early Ediacaran Glaciation - Zhongwu Lan; Magdalena H. Huyskens; Rong Ren; Qing-Zhu Yin (Journal of Earth Science, 2024)

Nitrifying and denitrifying microbes exhibit distinct community structure and activity responses to different crop rotation systems in subtropical paddy soils - Huifang Xu; Ke Li; Rong Sheng; Hongling Qin; Yi Liu; Anlei Chen; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Applied Soil Ecology, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Tibetan lake change linked to large-scale atmospheric oscillations via hydroclimatic trajectory - Rong Wang; Yuanbo Liu; Liping Zhu; Thabo Michael Bafitlhile; Ruonan Wang; Yongwei Liu (Science of The Total Environment, 2024)

The effect of mixed microbial agents on tobacco black shank disease - Fang Liang; Chai Yunxia; Li Yuanyuan; Geng Shaowu; Bu Yunhong; Hu Yang; Ai Kebiao; Shi Jianfei; Duan Jiyou; Yang Maosong; Zhu Rong (Physiological and Molecular Plant Pathology, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

A coupled regional-scale numerical model for hydrological processes and interactions between groundwater and surface water in a controlled drainage district - Xudong Han; Yan Zhu; Xiugui Wang; Youzhen Wang; Tao Shen; Rong Tang (Journal of Hydrology, 2024)

Accumulation and depuration of 4,5-dihydro-KmTx2 from Karlodinium veneficum in the bivalves, Mercenaria mercenaria and Sinonovacula constricta - Yanrong Li; Rong Chen; Zhujun Zhu; Tong Mu; Zhaoshou Ran; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2024)

Rhodamine and related substances in food: Recent updates on pretreatment and analysis methods - Rong-zhu Du; Yuan Zhang; Yu Bian; Chun-yu Yang; Xue-song Feng; Zhen-wei He (Food Chemistry, 2024)

Enhanced comprehensive energy storage properties of lead-free KNN based ceramics through composition optimization strategy - Tingting Gao; Mingyue Mo; Ning Chen; Qifan Chen; Rong Lang; Dong Wang; Zhi Tan; Jie Xing; Jianguo Zhu (Chemical Engineering Journal, 2024)

Diversified competitive sulfuration behaviors of concomitant heavy metal ions on copper recovery from copper smelting waste acid - Xiaolu Sun; Linhua Jiang; Ning Duan; Liye Bao; Hao Jin; Guangbin Zhu; Yong Liu; Zhiguo Song; Rong Zhang (Chemical Engineering Journal, 2024)

Long-term stationary fertilization decreased soil health in field-grown sweetpotato by increasing soil-borne diseases or allelochemicals - Xiaoya Zhu; Peng Zhao; Jing Wang; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2024)

Effects of weather parameters on the population dynamics of Megalurothrips usitatus in cowpea fields in Sanya, China - Yunchuan He; Jiamei Geng; Yang Gao; Qiulin Chen; Ying Zhou; Zeng-Rong Zhu (International Journal of Tropical Insect Science, 2024)

Application of the improved particle swarm optimization method in slope probability analysis - Yukuai Wan; Renhao Xu; Rong Yang; Lei Zhu (Marine Georesources & Geotechnology, 2024)

Ecotoxicological insights into the effects of triflumezopyrim on P. fuscipes fitness, detoxification pathways, and gene expression - Muhammad Musa Khan; Yuanzheng You; Dylan O'Neill Rothenberg; Pankaj Bhatt; Shah Fahad; Ying Zhou; Zeng-Rong Zhu (Chemosphere, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

The sulfurization precipitation and competition mechanisms of Cu(II) and As(V) in electrolyte towards efficient recovery of copper - Guangbin Zhu; Linhua Jiang; Ning Duan; Yong Liu; Rong Zhang; Xiaolu Sun; Hao Jin (Journal of Cleaner Production, 2024)

Visible-light responsive photocatalytic fuel cell with gas-diffusion g-C3N4/TiO2 heterojunction photoanode for simultaneously degrading VOCs and generating electricity - Xiaoling Xue; Chongyi Wang; Xun Zhu; Dingding Ye; Yang Yang; Hong Wang; Rong Chen; Qiang Liao (Journal of Environmental Chemical Engineering, 2024)

Modeling of activated carbon and multi-scale molecular simulation of its water vapor adsorption: A review - Zhongfan Mo; Ming Li; Shengnan Sun; Rong Zhu; Danya Zhan; Aimin Li; Yinning Li; Ying Zhang; Qiongfen Yu (Journal of Environmental Chemical Engineering, 2024)

Mitigation of malondialdehyde-induced protein lipoxidation by epicatechin in whey protein isolate - Wenhua Yao; Xingya Hao; Zhangjie Hu; Zhenghao Lian; Yue Cao; Rong Liu; Xiaoying Niu; Jun Xu; Qin Zhu (Food Chemistry, 2024)

Successful subduction of oceanic plate after failed attempts in the Late Archean: Petrological and geochemical constraints - Xi Wang; Rong-Feng Ge; Yong-Fei Zheng; Wen-Bin Zhu; San-Zhong Li; Rong-Song Tian; Yue Wang; Yi-Wei Rong (Earth and Planetary Science Letters, 2024)

Fe-doping accelerated magnesium storage kinetics in rutile TiO2 cathode materials - Qianwei Zhang; Xin Liu; Changliang Du; Mingwei Jin; Lifen Yang; Rong Jiang; Xilan Ma; Youqi Zhu; Chuanbao Cao; Meishuai Zou (Chemical Engineering Journal, 2024)

Development of an efficient pretreatment process and multi-functional acetate co-metabolism strategy for the treatment of high strength biogas slurry using a newly isolated Chlorella sorokiniana - Ning Jiao; Xiao Cheng; Yuan Sun; Yu-Rong Zhu; Zhong-Liang Sun; Shi-Kai Wang (Chemical Engineering Journal, 2024)

Tuning oxygen vacancies via photoinduced defect engineering in plasma pre-treated TiO2 for efficient solar-light-driven oxidation of trace methane - Qiyu Zhang; Jiakang Duan; Zhiping Zhu; Li Rong; Xiaochang Lin; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

TXNIP Regulates NLRP3 Inflammasome-Induced Pyroptosis Related to Aging via cAMP/PKA and PI3K/Akt Signaling Pathways - Xiaoshuang Xi; Rong Zhang; Yijia Chi; Ziman Zhu; Ruifeng Sun; Weijun Gong (Molecular Neurobiology, 2024)

SFRP1 reduces neutrophil infiltration and inhibits the Wnt/β-catenin pathway to alleviate oral submucous fibrosis - Rong Zhou; Lin Yin; Xin Zhang; Keke Zhu (In Vitro Cellular & Developmental Biology - Animal, 2024)

OsHRZ1 negatively regulates rice resistant to Magnaporthe oryzae infection by targeting OsVOZ2 - Jia-ying Sun; Zeng-ran Zhou; Yu-qi Wang; Dong-yu Zhu; Dian-rong Ma (Transgenic Research, 2024)

Management of zooplanktonic predations for efficient and sustainable production of Arthrospira - Xiaobin Wen; Rongxiang Lü; Junying Zhu; Du Cao; Junfeng Rong; Weichun Du; Yeguang Li (Algal Research, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Sequential Two-Mode Fusion Underwater Single-Photon Lidar Imaging Algorithm - Tian Rong; Yuhang Wang; Qiguang Zhu; Chenxu Wang; Yanchao Zhang; Jianfeng Li; Zhiquan Zhou; Qinghua Luo (Journal of Marine Science and Engineering, 2024)
Aiming at the demand for long-range and high-resolution imaging detection of small targets such as submerged submarine markers in shallow coastal waters, research on single-photon lidar imaging technology is carried out. This paper reports the sequential two-mode fusion imaging algorithm, which has a strong information extraction capability and can reconstruct scene target depth and reflection intensity images from complex signal photon counts. The algorithm consists of four steps: data preprocessing, extremely large group value estimation, noise sieving, and total variation smoothing constraints to image the target with high quality. Simulation and test results show that the imaging performance and imaging characteristics of the method are better than the current high-performance first-photon group imaging algorithm, indicating that the method has a great advantage in sparse photon counting imaging, and the method proposed in this paper constructs a clear depth and reflectance intensity image of the target scene, even in the 50,828 Lux ambient strong light and strong interference, the 0.1 Lux low-light environment, or the underwater high-attenuation environment.

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

Physicochemical properties dominating the behaviors of short/medium chain chlorinated paraffins in the atmosphere - Zhijie Zhang; Ningbo Geng; Cuiping Ning; Xiuhua Zhu; Haijun Zhang; Jiping Chen; Rong Cao (Journal of Hazardous Materials, 2024)

The design of high-efficient MOFs for selective Ag(I) capture: DFT calculations and practical applications - Manying Zhu; Xiang Liu; Dawei Xiang; Yuefeng Chen; Shixing Wang; Rong Zhu; Dekun Zhang; Zhengwu Peng; Likang Fu (Journal of Hazardous Materials, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Location-dependent occurrence and distribution of metal-based nanoparticles in bay environments - Siying Ying; Ziyi Liu; Yongrong Hu; Rong Peng; Xiaoshan Zhu; Shuofei Dong; Dong Yan; Yuxiong Huang (Journal of Hazardous Materials, 2024)

Preparation, characterization, and coating effect of bio-active nano-emulsion based on combined plant essential oils on quality of grass carp fillets - Mingtao Yang; Yunshan Zhu; Tianhao Ying; Jianhua Rong; Pengkai Wang; Yang Hu (Food Chemistry, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

Ti2TaC2: A novel out-of-plane ordered MXene towards flexible and cytocompatible supercapacitors - Yunfeng Guan; Lixian Jiang; Rong Zhao; Xuanke Li; Hui Zhu; Qin Zhang; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Constructing phonon transport bridges via low-temperature sintering in Diamond@Ag/EP composite to achieve efficient 3D networks structure - Zeyu Zheng; XiaoXin Lu; Liang Xu; Yang Liu; Jianhui Zeng; Hebin Zhang; Jialin Wen; Pengli Zhu; Rong Sun; Weijing Wu (Chemical Engineering Journal, 2024)

Rapid adsorptive removal of emerging and legacy per- and polyfluoroalkyl substances (PFASs) from water using zinc chloride-modified litchi seed-derived biochar - Zhen-Zhu Liu; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Hong-Ming Tan; Rong-Gui Zhu; Chao-Yang Zhou; Hao Liang; Kefu Yu (Bioresource Technology, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Altered Function and Structure of the Cerebellum Associated with Gut–Brain Regulation in Crohn’s Disease: a Structural and Functional MRI Study - Yunfei Li; Yanling Zheng; Lan Rong; Yan Zhou; Zhen Zhu; Qian Xie; Zonghui Liang; Xiaohu Zhao (The Cerebellum, 2024)

Microbial etch: A novel construction method of functionalized biochar for enhanced uranium extraction in radioactive wastewater - Yazhou Wang; Xudong Wu; Xiyang Liu; Chengkun Cai; Chenghu Liang; Lichun Dai; Xinsheng He; Rong He; Huanhuan Liu; Wenkun Zhu (Chemosphere, 2024)

Ultrasonically enhanced zinc powder replacement method for cobalt removal: Electrochemical behavior, numerical simulation - Jianqiang Ye; Rong Zhu; Dawei Xiang; Manying Zhu; Shixing Wang; Likang Fu; Genwei Zhang (Journal of Cleaner Production, 2024)

Adsorption and catalytic degradation of tetracycline hydrochloride by HCNTs /MnFe2O4 - Chunjie Ma; Aaron Albert Aryee; Keke Zhu; Rong Wang; Runping Han (Journal of Environmental Chemical Engineering, 2024)

In-situ electric swing adsorption enabling superior water vapor capture of salt-based carbon fibers - Rong Zhu; Yaowei Huang; Qiongfen Yu; Ming Li; Yunfeng Wang; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Phosphoric acid pre-swelling strategy constructing acid-doped fluoropoly(aryl pyridinium) membranes to enable high-performance vanadium flow batteries - Tao Ban; Zihui Wang; Yinfei Wang; Yifei Xu; Zhanpeng Jiang; Rong Zeng; Xiuling Zhu (Chemical Engineering Journal, 2024)

Superior energy storage properties with prominent thermal stability in lead-free KNN-based ceramics through multi-component optimization strategy - Qifan Chen; Hao Chen; Dong Wang; Tingting Gao; Qinyu Li; Rong Lang; Zhi Tan; Jie Xing; Jianguo Zhu (Chemical Engineering Journal, 2024)

Constructing Cu9S5@CuSe heterostructures under microwave irradiation for rechargeable magnesium batteries - Mingwei Jin; Zhaoyu Xue; Heng Cao; Qianwei Zhang; Rong Jiang; Changliang Du; Lifen Yang; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Degradation of wild fruit forests created less diverse and diffuse bacterial communities decreased bacterial diversity, enhanced fungal pathogens and altered microbial assembly in the Tianshan Mountain, China - Xiaoying Rong; Nan Wu; Benfeng Yin; Xiaobing Zhou; Bingjian Zhu; Yonggang Li; Zachary T. Aanderud; Yuanming Zhang (Plant and Soil, 2024)

FOXP4-AS1 promotes CD8+ T cell exhaustion and esophageal cancer immune escape through USP10-stabilized PD-L1 - Guo-yi Shen; Yi Zhang; Rong-zhi Huang; Zhi-yong Huang; Le-yi Yang; Ding-zhu Chen; Shao-bin Yang (Immunologic Research, 2024)

Phonological awareness and RAN contribute to Chinese reading and arithmetic for different reasons - Xiujie Yang; Jon R. Star; Xiangyi Zhu; Rong Wang; Yan Zhang; Jiajin Tong; Zhonghui He (Cognitive Processing, 2024)

Facilities pond aquaculture system construction and the ecological economy analyzed - Hao Zhu; Zhao-Jun Gu; Guo-Feng Cheng; Xing-Guo Liu; Rong Tang (Aquacultural Engineering, 2024)

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

Ecological response to global changes in Lake Genco, a remote alpine lake on the Southeast Tibetan Plateau, over the past two centuries - Yanjie Zhao; Rong Wang; Hengshuai Qiu; Jianan Zheng; Kexin Zhu; Wenxiu Zheng; Xiangdong Yang; Enlou Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Real-time ozonation monitoring and control in wastewater tertiary treatment: An ultraviolet-visible monitoring approach - Yunze Rong; Xiaodong Wang; Ming Zhu; Wei Chen; Zakhar Maletskyi; Harsha Ratnaweera; Xuejun Bi (Journal of Water Process Engineering, 2024)

Inactivation of Aeromonas hydrophila in water by dielectric barrier discharge plasma: Efficiency, mechanism, and application safety - Le Wang; Zhenfei Zhu; Pengcheng Yan; Rong Zhang; Min Zhang; Xiangyu Wang; Guangzhou Qu; Tiecheng Wang; Ronghua Li (Journal of Water Process Engineering, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Cratonic strike-slip fault systems in the central Sichuan Basin, China - Shuwei Guan; Yiqiong Zhang; Hua Jiang; Xuesong Lu; Han Liang; Shipeng Huang; Guangyou Zhu; Rong Ren; Nan Su (Earth-Science Reviews, 2024)

Effects of internal waves on bottom thermal structures and turbulent mixing in the Xisha Islands - Ming-Quan Zhu; Xian-Rong Cen; Sheng-Qi Zhou; Yuan-Zheng Lu; Shuang-Xi Guo; Peng-Qi Huang; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Preparation of amidoxime modified covalent organic framework for efficient adsorption of lead ions in aqueous solution - Dawei Xiang; Rong Zhu; Yuefeng Chen; Manying Zhu; Shixing Wang; Yihui Wu; Jiaxin Luo; Likang Fu (Chemical Engineering Journal, 2024)

A study on construction of a prognosis model for liver cancer based on analgesic targets and screening therapeutic drugs - Xueyan Jiang; Yaodong Ping; Yuan Chen; Benben Zhu; Rong Fu; Yiwei Hao; Lei Fan (Genes & Genomics, 2024)

Bidirectional biotic interchange between Taiwan Island and Mainland China via land bridges—A case study of Obeidia Walker (Geometridae, Lepidoptera) - Rui Cheng; Nan Jiang; A’rong Luo; Michael Orr; Qingsong Zhou; Xiaoyu Shi; Hongxiang Han; Chaodong Zhu (Zoologica Scripta, 2024)
Biotic exchanges between Taiwan and Mainland China have shaped the biodiversity and ecosystems of both regions. Exchanges from Mainland China to Taiwan have received more attention, mainly studied in terrestrial vertebrates, while the reverse direction and invertebrates have largely been overlooked. Here, we explore the dispersal events between these two regions based on the moths of three species groups of Obeidia , including Taiwan taxa and its relatives from mainland. We conducted mixed methods and analysis, including reconstructing a phylogenetic tree, estimating associated divergence times and inferring ancestral areas and source regions, to explore the phylogeographical structure and genetic pattern of three groups based on eight genes. Our results revealed a structure of three clades and every clade included at least one Taiwanese taxa and its closest relatives of mainland of China, and also served Taiwan as an important source region of two mainland taxa. Our study revealed various origin pattern and dispersal models on the basis of three species groups of Obeidia . Bi‐directional biotic exchange via a land bridge were found: four Taiwanese taxa originated from mainland, and two of them migrated back to mainland. Both eastern Himalayas and south China are important origin areas for Taiwan biota, and the dominant source region may need multiple insect cases to confirm. Our study also provided evidences for disjunct distribution from the perspective of insecta molecular phylogeny.

An appetite assessment method for fish in outdoor ponds with anti-shadow disturbance - Weiqiang Ni; Dan Wei; Zequn Peng; Zhen Ma; Songming Zhu; Rong Tang; Xuelei Tian; Jian Zhao; Zhangying Ye (Computers and Electronics in Agriculture, 2024)

Simultaneous determination of trace marine lipophilic and hydrophilic phycotoxins in various environmental and biota matrices - Chao-Yang Zhou; Chang-Gui Pan; Feng-Jiao Peng; Rong-Gui Zhu; Jun-Jie Hu; Kefu Yu (Marine Pollution Bulletin, 2024)

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Long-term chemical and organic fertilization induces distinct variations of microbial associations but unanimous elevation of soil multifunctionality - Ke Li; Anlei Chen; Rong Sheng; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Science of The Total Environment, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Two-step synthesis of coconut shell biochar-based ternary composite to efficiently remove organic pollutants by photocatalytic degradation - Shipeng Zhang; Rong Wang; Jinhua Zhu; Xiaoyan Xie; Mei Luo; Hailong Peng; Yude Liu; Fei Feng; Ronghui Shi; Wang Yin (Journal of Environmental Chemical Engineering, 2024)

Acid induced dispersive liquid–liquid microextraction based on in situ formation of hydrophobic deep eutectic solvents for the extraction of bisphenol A and alkylphenols in water and beverage samples - Kaige Zhang; Jing Wang; Rong Guo; Qiujun Nie; Guifen Zhu (Food Chemistry, 2024)

Ultrasound enhanced in-situ chemical oxidation for leaching Ag from zinc leaching residue and response surface optimization - Rong Zhu; Shixing Wang; Yuefeng Chen; Dawei Xiang; Libo Zhang; Jian Liu; Jianqiang Ye (Chemical Engineering Journal, 2024)

Mechanism and kinetics of ultrasound enhanced removal of arsenic from high alkali leaching solution for alkali recovery - Yuefeng Chen; Dawei Xiang; Manying Zhu; Shixing Wang; Rong Zhu; Xiang Liu; Likang Fu (Chemical Engineering Journal, 2024)

Polyoxovanadate Li7[V15O36(CO3)] and its derivative γ-LiV2O5 as superior performance cathode materials for aqueous zinc-ion batteries - Haoran Xiao; Xin Du; Rong Li; Hao Jin; Lingling Xie; Qing Han; Xuejing Qiu; Xinli Yang; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Experimental Investigation of Desiccation Cracking of Jilin Ball Clay Under Wet–Dry Cycles - Yucong Gao; Dongxue Hao; Yiming Zhu; Rong Chen; Xuejun Liu; Ruifeng Guo (Geotechnical and Geological Engineering, 2024)

Xylem adjustment and growth response of early- and late-successional tree species to rapid warming - Zihao Hu; Liangjun Zhu; Shuguang Liu; Pifeng Lei; Rong Zhang; Paolo Cherubini (European Journal of Forest Research, 2024)
Climate changes have dramatically affected forest succession. However, how trees at different successional stages respond to climate warming is unclear in the subtropics. Here, we compared the radial growth (RW) and xylem features of the early-successional stage Castanea mollissima and late-successional stage Quercus fabri in subtropical forests and assessed their response to climate changes. All parameters, including RW, number of vessels (VN), vessel density (VD), mean (MVA) and total (TVA) vessel area, percentage of conductive area within xylem (RCTA), theoretical (Kh) and xylem-specific (Ks) hydraulic conductivity, except for MVA of C. mollissima were significantly higher than those of Q. fabri . During the drought period, a notable adverse correlation between two cluster parameters of Q. fabri , associated with hydraulic safety and efficiency, suggested a pronounced hydraulic trade-off in Q. fabri under drought conditions. Castanea mollissima was more sensitive to climate and more prone to hydraulic failure than Q. fabri . Temperatures and moisture conditions positively and negatively affected the hydraulic efficiency-related parameters of C. mollissima . Moisture conditions in the previous summer and winter were significantly negatively and positively related to the radial growth of both species. The impact of generalized warming was not evident due to variations in hydraulic strategies and species characteristics, trade-offs between non-growing and growing season climates, and specific competition. If climate warming continues, C. mollissima growth will probably significantly decline due to the increasing risk of hydraulic failure. Warming may accelerate species replacement and forest succession in the study area by changing their lifespans and competitive relationships.

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

Structural elucidation a complex galactosyl and glucosyl-rich pectin from the pericarp of immature fruits of Juglans mandshurica Maxim. - Xi-Zhe Sun; Qing-Yu Zhang; Si-Liang Jiang; Rong-Jian Zhu; Jun-Hong Chai; Jun Liang; Hai-Xue Kuang; Yong-Gang Xia (Glycoconjugate Journal, 2024)

Histopathological analysis of the wall enhancement of the spinal dural arteriovenous fistulae’s draining veins - Xiaojun Hu; Yuhang Diao; Zhenghao Hao; Mingyu Hao; Minghao Xie; Hongtao Rong; Tao Zhu (Acta Neurologica Belgica, 2024)

Formation Mechanism of NW-Trending Faults and Their Significance on Basin Evolution in Zhu III Depression of the Pearl River Mouth Basin, SE China - Pengfei Zhu; Lintao Zhao; Jiantai Zhang; Dunling Mu; Yichun Chen; Pengfei Rong (Journal of Marine Science and Engineering, 2024)
The Zhu III Depression, situated in the northern Pearl River Mouth Basin, features a complex fault system composed of NE–SW-, nearly E–W-, and NW–SE-oriented faults. However, there is limited research on NW-trending faults, especially regarding their formation mechanisms. Through structural analysis of 3D seismic profiles, we have revealed the geometric and kinematic characteristics of NW-trending faults and categorized them into three types based on their formation mechanisms: extensional fault, dextral transtensional fault, and sinistral strike–slip fault. The extensional faults predominantly developed as boundary faults during the rifting I period, caused by tectonic inversion of the NW–NWW-trending basement faults since early Eocene. The transtensional fault resulted from the dextral strike–slip motion of the NE-trending basin-controlling faults since late Eocene, under the regional dextral extension stress setting. The sinistral strike–slip faults have been dominant during the post-rifting period since early Oligocene. This is due to the sinistral shearing action related to the southeastward lateral extrusion of the Indochina Block and slab pull southward by subduction of the proto-SCS. The NW-trending faults controlled the development of local tectonics and structures, the depocenter migration during the rifting period, and the trapping, migration, and preservation of oil and gas.

Corrigendum to “Development, verification, and simulation analysis of variable friction self-centering energy dissipative brace” [Soil Dynam. Earthq. Eng. 179 (2024) 108537] - Lihua Zhu; Tong Liu; Zijie Li; Yao-Rong Dong; Jinwu Luo (Soil Dynamics and Earthquake Engineering, 2024)

Pichia galeiformis-secreted protein PgSLP increases citrus fruit disease resistance by activating amino acid metabolism - Yao Xu; Ou Chen; Rong Zhu; Wenjun Wang; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Expression analysis and antiviral activity of koi carp (Cyprinus carpio) viperin against carp edema virus (CEV) - Xiao-wen Wang; Rong Zhang; Li-li Liu; Hui-juan Li; Hua Zhu (Fish & Shellfish Immunology, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

Microwave-induced defect-rich vanadium sulfide cathodes for highly reversible electrochemical magnesium storage - Rong Jiang; Bolin Liu; Changliang Du; Mingwei Jin; Xin Liu; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Efficient magnetic solid-phase extraction, UPLC-MS/MS detection, and consumption assessment of five trace psychoactive substances - Rong Zhu; Shurui Cao; Hongtao Su; Dewang Ming; Yao Tang; Zhiqiong Chen (Environmental Science and Pollution Research, 2024)

Terpenes based hydrophobic deep eutectic solvents for dispersive liquid-liquid microextraction of aliphatic aldehydes in drinking water and alcoholic beverages - Kaige Zhang; Rong Guo; Yunhe Wang; Jing Wang; Qiujun Nie; Guifen Zhu (Chemosphere, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Development, verification, and simulation analysis of variable friction self-centering energy dissipative brace - Lihua Zhu; Tong Liu; Zijie Li; Yao-Rong Dong; Jinwu Luo (Soil Dynamics and Earthquake Engineering, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Comparative analysis of process selection and carbon emissions assessment of innovative steelmaking routes - Botao Xue; Guangsheng Wei; Yanze Hou; Hang Hu; HongJin Zhang; Rong Zhu; Kai Dong; Chao Feng; Lingzhi Yang; Hongbin Wang (Journal of Cleaner Production, 2024)

Efficient recovery of copper resources from copper smelting waste acid based on Cu(Ⅱ)/As(Ⅲ) competitive sulfuration mechanism - Xiaolu Sun; Linhua Jiang; Ning Duan; Guangbin Zhu; Yanli Xu; Hao Jin; Yong Liu; Rong Zhang (Journal of Cleaner Production, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Soil carbon storage and accessibility drive microbial carbon use efficiency by regulating microbial diversity and key taxa in intercropping ecosystems - Ziyu Yang; Qirui Zhu; Yuping Zhang; Pan Jiang; Yizhe Wang; Jiangchi Fei; Xiangmin Rong; Jianwei Peng; Xiaomeng Wei; Gongwen Luo (Biology and Fertility of Soils, 2024)

Intercropping regulates plant- and microbe-derived carbon accumulation by influencing soil physicochemical and microbial physiological properties - Qirui Zhu; Ziyu Yang; Yuping Zhang; Yizhe Wang; Jiangchi Fei; Xiangmin Rong; Jianwei Peng; Xiaomeng Wei; Gongwen Luo (Agriculture, Ecosystems & Environment, 2024)

Copper-doped Lanthanide Coordination Polymers as Luminescent Nanoenzyme for Ratiometric Sensing of H2O2 and Glutathione - Xinru Wu; Chen Ruan; Xinyue Zhu; Lina Zou; Rong Wang; Gaiping Li (Journal of Fluorescence, 2024)

Generation of golden goldfish Carassius auratus via tyrosinase gene targeting by CRISPR/Cas9 - Huijuan Li; Xiaowen Wang; Rong Zhang; Lili Liu; Hua Zhu (Aquaculture, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Mulch film to plastic debris: A survey of agricultural soils of Hebei Province, North China - Rong Liang; Zhejiang Zhu; Cong Peng; Zijia Bian; Xiaomei Yang; Hong Wang; Xin-Xin Wang (Science of The Total Environment, 2024)

Adaptation mechanisms of leaf vein traits to drought in grassland plants - Xiaochun Wang; Shuang Chen; Xue Yang; Rong Zhu; Miao Liu; Ruili Wang; Nianpeng He (Science of The Total Environment, 2024)

Underlying the inhibition mechanisms of sulfate and lincomycin on long-term anaerobic digestion: Microbial response and antibiotic resistance genes distribution - Li Xie; Jiaxin Zhu; Jing Xie; Jun Xu; Rong He; Wenbiao Wang (Science of The Total Environment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Enhanced detection of acrylamide using a versatile solid-state upconversion sensor through spectral and visual analysis - Yawen Rong; Md Mehedi Hassan; Jizhong Wu; Shuo Chen; Wancheng Yang; Yunhao Li; Jiaji Zhu; Jun Huang; Quansheng Chen (Journal of Hazardous Materials, 2024)

Kinetics of fe-containing solid waste reduction by carbonaceous materials in CO2 atmosphere: The cause of reducing agent burnout during direct reduction treatment - Xin Li; Guangsheng Wei; Hongyang Wang; Bohan Tian; Rong Zhu; Yefeng Wang (Fuel, 2024)

The optimal ammonium-nitrate ratio for various crops : A Meta-analysis - Jiatao Chen; Jinghua Li; Weifang Li; Peng Li; Rong Zhu; Yuxiu Zhong; Weifeng Zhang; Tingyu Li (Field Crops Research, 2024)

Photo-enhanced nanozyme with self-cascade catalysis enhances peroxidase-like activity for alcohol discrimination - Rina Su; Yu Wu; Weiqing Xu; Rong Tan; Ying Qin; Runshi Xiao; Canglong Wang; Liuyong Hu; Wenling Gu; Hongcheng Sun; Chengzhou Zhu (Chemical Engineering Journal, 2024)

A layered sodium-ion host O3-NaFe0.5Ti0.5O2 enables Na-free cathodes through offering extractable Na-ions - Qingyang Song; Peng Shi; Zhiqiang Guo; Peng Zhang; Yuanhang Li; Xiaohui Rong; Xiaoyan Wu; Shuyin Xu; Huican Mao; Yingchun Lyu; Chengjun Zhu (Chemical Engineering Journal, 2024)

Design of a dual-responding genetic circuit for high-throughput identification of L-threonine-overproducing Escherichia coli - Buli Su; Peixuan Lai; Ming-Rong Deng; Honghui Zhu (Bioresource Technology, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

A nationwide investigation on the characteristics and health risk of trace elements in surface water across China - Fanyu Meng; Rong Cao; Xiuhua Zhu; Yuying Zhang; Manxue Liu; Jufang Wang; Jiping Chen; Ningbo Geng (Water Research, 2024)

Bridge substructure feature extraction based on the underwater sonar point cloud data - Shuaihui Zhang; Yanjie Zhu; Wen Xiong; Xueliang Rong; Jinquan Zhang (Ocean Engineering, 2024)

Revealing the release and migration mechanism of heavy metals in typical carbonate tailings, East China - Rong Zhao; Xiong Wu; Ge Zhu; Xiao Zhang; Fei Liu; Wenping Mu (Journal of Hazardous Materials, 2024)

Developing a highly efficient, environmentally friendly and cost-effective copper sulfide semiconductor sponge for nuclear wastewater treatment under one sun - Wencai Bai; Mengjiao Liu; Kaifu Yu; Xin Cao; Jie Lian; Zhibin Zhao; Yong Xiang; Baoliang Xu; Tao Chen; Rong He; Nan Sun; Wenkun Zhu (Journal of Environmental Chemical Engineering, 2024)

H2O2-enhanced alkaline pretreatment and separation of tobacco stems for biocellulose composite films with potential application in food preservation - Danya Zhan; Qiongfen Yu; Ming Li; Zhenhua Gu; Shengnan Sun; Yinning Li; Aimin Li; Rong Zhu; Zhongfan Mo; Runfang Ma (Journal of Environmental Chemical Engineering, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Preparation and properties of biofilm-states Bifidobacterium adolensentis Gr19 under dynamic culture system and its application on probiotic ice cream manufacture - Zekang Zhu; Haoxuan Sun; Kaisheng Shen; Yangshuo Liu; Rong Nie; Guorong Liu (Food Bioscience, 2024)

Fifty-year pollution history of microplastics and influencing factors in offshore sediments: A case study of Ningbo, China - Zhenhong Zhu; Xuexi Xiao; Rong Wu; Chong Jin; Tong Li; Weiping Liu (Environmental Pollution, 2024)

How hydrogen bonding and π–π interactions synergistically facilitate mephedrone adsorption by bio-sorbent: An in-depth microscopic scale interpretation - Shurui Cao; Rong Zhu; Duanhao Wu; Hongtao Su; Zhenghong Liu; Zhiqiong Chen (Environmental Pollution, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Nucleotide at position 66 of NS2A in Japanese encephalitis virus is associated with the virulence and proliferation of virus - Ning Tan; Chen Chen; Yang Ren; Rong Huang; Zhuang Zhu; Kui Xu; Xiaoyao Yang; Jian Yang; Lei Yuan (Virus Genes, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Metformin treatment of juvenile mice alters aging-related developmental and metabolic phenotypes in sex-dependent and sex-independent manners - Yun Zhu; Morgan Engmann; David Medina; Xiuqi Han; Pratyusa Das; Andrzej Bartke; Buffy S. Ellsworth; Rong Yuan (GeroScience, 2024)

Parabens and their metabolite in a marine benthic-dominated food web from the Beibu gulf, South China Sea: Occurrence, trophic transfer and health risk assessment - Rong-Gui Zhu; Chang-Gui Pan; Feng-Jiao Peng; Chao-Yang Zhou; Jun-Jie Hu; Kefu Yu (Water Research, 2024)

Industrialization of open- and closed-loop waste textile recycling towards sustainability: A review - Xinxin Huang; Yuhan Tan; Jiwei Huang; Guangzhou Zhu; Rong Yin; Xiaoming Tao; Xiao Tian (Journal of Cleaner Production, 2024)

An appropriate amount of straw replaced chemical fertilizers returning reduced net greenhouse gas emissions and improved net ecological economic benefits - Lian Zhang; Guoliang Jiang; Rusheng Xiao; Kun Hou; Xin Liu; Xinyu Liu; Pei Yuan; Feng Tian; Lichu Yin; Hongmei Zhu; Chang Tian; Lan Yang; et al. (Journal of Cleaner Production, 2024)

Effect of blending ratio on the compatibility and stability of konjac glucomannan/starch composite systems - Qian Zhang; Sicong Yan; Rong Zhou; Xu Yan; Peineng Zhu; Lingyun Chen; Fatang Jiang (Food Hydrocolloids, 2024)

Mechanistic insights into synergistic facilitation of copper/zinc ions and dewatered swine manure-derived biochar on anaerobic digestion of swine wastewater - Gaojun Wang; Changxi Sun; Peng Fu; Bo Zhang; Jinglin Zhu; Qian Li; Jianfeng Zhang; Rong Chen (Environmental Research, 2024)

Cryogenian–Cambrian tectono-sedimentary evolution, paleoclimate and environment effects, and formation of petroleum resources in the Tarim Block - Zhiyao Zhang; Guangyou Zhu; Weiyan Chen; Lin Wu; Rong Ren; Chuanlin Zhang (Earth-Science Reviews, 2024)

Two calcium-based metal organic frameworks with long afterglow as anticounterfeiting materials - Rong-Hui Shi; Zhi-Qiang Long; Fanan Wang; Ling-Zhu Gong; Xiao-Ying Lin; Gui-Lin Zhuang; Dong-Fei Lu (Chemical Engineering Journal, 2024)

Coconut husk-derived nanocellulose as reinforcing additives in thermal-responsive hydrogels - Yihao Leow; Yi Jian Boo; Ming Lin; Ying Chuan Tan; Rubayn Zhi Rong Goh; Qiang Zhu; Xian Jun Loh; Kun Xue; Dan Kai (Carbohydrate Polymers, 2024)

Stochastic and deterministic assembly processes of bacterial communities in different soil aggregates - Yan Wang; Kun Zhu; Xin Chen; Keyu Wei; Rong Wu; Gang Wang (Applied Soil Ecology, 2024)

Recognizing topological attributes and spatiotemporal patterns in spotted seals (Phoca largha) trophic networks based on eDNA metabarcoding - Yan Xu; Fei Huang; Mingliang Zhou; Rui Gu; Jie Zhu; Qiangqiang Rong; Yanpeng Cai (Frontiers in Marine Science, 2023)
Spotted seals, a protected species, face multifaceted threats to their habitat, which in turn impact the closely associated trophic networks. These threats will lead to irreversible structural variations within the ecosystem. Therefore, investigating the topological variability of trophic networks in spotted seals is important. Applying environmental DNA methods, field sample collection was conducted in 2021 during both the sea fishing moratorium period and the fishing period to decode fish diversity. Assessing the current status of fish resources by using the multivariate statistics approach. Applying dietary information establishes the spotted seals’ trophic network. Selecting 12 network indexes to analyze the spatiotemporal patterns of network topological attributes. As a result, about 51 families, and 76 genera species were identified. During the sea fishing moratorium and the fishing period, there are 12 and 18 different food resources available for spotted seals, respectively. The diversity index revealed that the FP had greater species richness and diversity than the SP. Comparatively, the Fishing period exhibited higher species richness and biodiversity, likely influenced by habitat heterogeneity and anthropogenic activities. Additionally, the topological features of networks reflected the high clustering coefficients (CC=0.35) and the proportion of omnivorous species (O≈60%), indicating that the network structure in this region tends to form higher trophic-level clustering patterns, which facilitate the formation of weaker interactions between clusters, enhancing the robustness of the network. The higher connectivity complexity index during the fishing period (SC=12.3) supported that the spotted seal’s trophic network was relatively more stable in this period. Thus, during the fishing period, it is crucial to pay more attention to the intensity of human fishing on mid-to-high trophic-level omnivorous fish resources to ensure the sustainability of these potential food resources for spotted seals. This comprehensive study achieved three key objectives: (a) utilizing eDNA to characterize fish diversity during distinct periods, (b) establishing trophic networks of spotted seals, and (c) discerning topological attributes and spatiotemporal patterns within the ecological network. Overall, this study can provide technical and data support for integrated ecological network management and propose suggestions for protecting and recovering spotted seals.

Authentication of Asini Corii Colla and Taurus Corii Colla based on UPLC-MS/MS and the discovery of antioxidant peptides associated with the PI3K-AKT pathway - Wei Wang; Lin Chu; Liqun Chen; Rong Yang; Shaoqing Zhu; Yuanbin Zhang; Huan Yang (Natural Product Research, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Characterization of the aerosol vertical distributions and their impacts on warm clouds based on multi-year ARM observations - Yun Lin; Yoshihide Takano; Yu Gu; Yuan Wang; Shujun Zhou; Tianhao Zhang; Kuilin Zhu; Jingyu Wang; Bin Zhao; Gang Chen; Damao Zhang; Rong Fu; et al. (Science of The Total Environment, 2023)

Three decades of shade trees improve soil organic carbon pools but not methane uptake in coffee systems - Hao Sun; Fulan Zhang; Syed Turab Raza; Yingmo Zhu; Tao Ye; Li Rong; Zhe Chen (Journal of Environmental Management, 2023)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Effects of iron additives on the removal of antibiotics and antibiotic resistance genes in anaerobic fermentation of food waste - Xiaotian Li; Langping Zhu; Rong Ma; Xiaozhi Zhang; Changquan Lin; Youqian Tang; Zhuoshen Huang; Chunming Wang (Journal of Environmental Management, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Exploring novel ANGICon-EIPs through ameliorated peptidomics techniques: Can deep learning strategies as a core breakthrough in peptide structure and function prediction? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Food Research International, 2023)

Effect of geographical origins and pile-fermentation on the multi-element profiles of ripen Pu-erh tea revealed by comprehensive elemental fingerprinting - Jiayi Zhu; Le Chen; Yue Chen; Yuting Rong; Yongwen Jiang; Fuqiao Liu; Qinghua Zhou; Xuehong Wei; Haibo Yuan; Junjie Zhang; Jia Li (Food Control, 2023)

Oligo (ethylene glycol) side chain engineering: An efficient way for boosting the development of green-solvent processable electrochromic devices - Shiyi Li; Qilin Wang; Yuehui Zhai; Zhen Xing; Jundong Zhong; Danming Chao; Xuanbo Zhu; Changru Rong; Zongquan Wu; Zheng Chen (Chemical Engineering Journal, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

The improvements of sea surface temperature simulation over China Offshore Sea in present climate from CMIP5 to CMIP6 models - Rong Deng; Shaobo Qiao; Xian Zhu; Tianyun Dong; Guolin Feng; Wenjie Dong (Climate Dynamics, 2023)

Exploring Environmental Nanoplastics Research: Networks and Evolutionary Trends - Qisheng Yu; Chia-Ying Anderin Chuang; Yuelu Jiang; Huan Zhong; Andrew Cundy; Raymond W. M. Kwong; Chao Min; Xiaoshan Zhu; Rong Ji (Reviews of Environmental Contamination and Toxicology, 2023)
Analyzing scientific advances and networks in NPs research can provide valuable insights into the evolving trends, research gaps, and priorities for future research efforts, highlighting the importance of scientific research in pollution control and risk management of uncontrolled and unknown nanoplastics (NPs) that pose a potential global threat, and have raised concerns in the scientific community and media. A total of 2055 nanoplastics (NPs) studies published from 1995 onwards were retrieved from the Web of Science Core Collection database. Bibliometric methods were applied to assess evolving scientific advances and networks. The general term, “nanoplastics,” was first introduced in 1995 as “intelligent” materials. Before 2009, defined as the ambiguous stage, NPs were produced and applied in many different manufacturing areas and processes. The first research referring to nano-scale plastic particles/debris as potential hazardous contaminants appeared in 2010. Thereafter, the number of annual publications on NPs has increased rapidly, particularly from 2018 onwards. Results showed China published 822 scientific papers, overtaking the United States’ 229 papers, whereas European researches, i.e., the Netherlands, Portugal, German, and the United Kingdom, led in quality and citation with extensive international collaborations. Furthermore, we concluded three main research themes from keyword cluster analysis: environmental monitoring (identification, quantification, fresh-water, marine-environment); environmental behaviors (fate, adsorption, aggregation, transport); and toxicology (toxicity, exposure, ingestion, oxidative stress). Toxicology and environmental behaviors of NPs were the leading themes. An overview of the current understanding of NPs in the above three major themes provides perspectives to identify future research directions based on knowledge gaps, e.g., advancing analytical methods, and exploring the mobility and fate of NPs in different ecosystems. Scientific research on NPs is a key fundamental requirement for their pollution control and risk management. To bridge the gap between research and reality, future efforts are required to promote the dissemination of scientific research findings and encourage actions in engineering, policy, education, etc., to support a sustainable society. Graphical Abstract

Effects of zero-valent iron and magnetite on ethanol and lactic acid production in the anaerobic fermentation of food waste - Xiaotian Li; Rong Ma; Langping Zhu; Xiaozhi Zhang; Changquan Lin; Youqian Tang; Zhuoshen Huang; Chunming Wang (Journal of Environmental Management, 2023)

Heavy metals transport patterns and risk evaluation in the pig manure- black soldier fly-tilapia food chain - Changquan Lin; Xiting Xia; Yuwei Li; Rong Ma; Langping Zhu; Xiaotian Li; Youqian Tang; Chunming Wang (Environmental Pollution, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Dual-functional application of a metal-organic framework in high-performance all-solid-state lithium metal batteries - Chengyi Lu; Yuchen Wu; Yi Rong; Haiye Zhu; Xin Chen; Tianyi Gu; Zhengyi Lu; Mark H. Rummeli; Ruizhi Yang (Chemical Engineering Journal, 2023)

Characteristics of labile organic carbon fractions under different types of subsidence waterlogging areas in a coal mining area: A case study in Xinglongzhuang Coal Mine, China - Yanhua Fu; Zhenqi Hu; Qi Zhu; Ying Rong (CATENA, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Effects of air environmental audit on reducing air pollutant emissions: evidence from China - Rong Ge; Yixuan Wang; Zhiyao Xu; Lu Yuan; Jiaxuan Zhu; Yizhe Su (Environmental Science and Pollution Research, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

The impact of crop residue return on the food–carbon–water–energy nexus in a rice–wheat rotation system under climate warming - Li-Yao Zhou; Yong-he Zhu; Zheng-Rong Kan; Feng-Min Li; Feng Zhang (Science of The Total Environment, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Genome-wide discovery of Pichia galeiformis-secreted proteins and their induction of green mold resistance in citrus fruit - Ou Chen; Rong Zhu; Yao Xu; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Composition and sources of suspended particles in the Pacific Arctic region - Xiaoguo Yu; Liming Ye; Yeping Bian; Yanguang Liu; Weiyan Zhang; Weiguo Wang; Xuying Yao; Jihao Zhu; Xiaobing Jin; Rong Wang (Marine Environmental Research, 2023)

In-situ constructing amidoxime groups on metal-free g-C3N4 to enhance chemisorption, light absorption, and carrier separation for efficient photo-assisted uranium(VI) extraction - Kaifu Yu; Yi Li; Xin Cao; Ruixiang Wang; Li Zhou; Linzhen Wu; Ningning He; Jia Lei; Dengjiang Fu; Tao Chen; Rong He; Wenkun Zhu (Journal of Hazardous Materials, 2023)

Tree-ring data reveal trees are suffering from severe drought stress in the humid subtropical forest - Rong Zhang; Zihao Hu; Paolo Cherubini; David J. Cooper; Liangjun Zhu; Pifeng Lei (Forest Ecology and Management, 2023)

Widely targeted metabolomics and HPLC analysis elaborated the quality formation of Yunnan pickled tea during the whole process at an industrial scale - Yan Hou; Honglin Mao; Fengmei Lu; Cunqiang Ma; Shaoxian Zhu; Guoyou Li; Siqi Huang; Yi Zhang; Caiyou Lv; Rong Xiao (Food Chemistry, 2023)

Soil microbial diversity and network complexity sustain ecosystem multifunctionality following afforestation in a dry-hot valley savanna - Shuaifeng Li; Xiaobo Huang; Rong Tang; Jing Li; Biao Zhu; Jianrong Su (CATENA, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Ultrasensitive detection and efficient removal of mercury ions based on covalent organic framework spheres with double active sites - Ke Xiao; Rong Zhu; Xiaohua Zhang; Cuicui Du; Jinhua Chen (Analytica Chimica Acta, 2023)

Balanced phosphorus fertilization enhances soil bacterial network complexity to maintain multifunctionality and plant production in dryland agricultural systems - Lei Liu; Rong Yan; Li Zhu; Yu Yang; Zhiyuan Gao; Wenjie Yang; Jinshan Liu (Agriculture, Ecosystems & Environment, 2023)

Hypervirulent Klebsiella pneumoniae detection methods: a minireview - Qi-bin Zhang; Peng Zhu; Shun Zhang; Yan-jing Rong; Zuo-an Huang; Li-wan Sun; Ting Cai (Archives of Microbiology, 2023)

Coupling and coordinated development of low-carbon economy and green finance: an empirical study of the Yangtze River Delta region in China - Shujie Sun; Peixiu Chen; Zehui Guo; Ling Miao; Rong Zhu; Xuepeng Qian; Weisheng Zhou (Environmental Science and Pollution Research, 2023)

Effects of size and surface charge on the sedimentation of nanoplastics in freshwater - Honglu Zhu; Xiaolei Fan; Hua Zou; Rong-Bo Guo; Shan-Fei Fu (Chemosphere, 2023)

A self-assembled nanoparticle vaccine based on pseudorabies virus glycoprotein D induces potent protective immunity against pseudorabies virus infection - Xujiao Ren; Nan Cao; Linxing Tian; Wenqiang Liu; Hechao Zhu; Zhenxiang Rong; Manman Yao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

ML based approach for inverting penetration depth of SAR signals over large desert areas - Jun Zhu; Guanxin Liu; Rong Zhao; Xiaoli Ding; Haiqiang Fu (Remote Sensing of Environment, 2023)

A GC/C/IRMS-based method for position-specific carbon isotopic analysis of saturated long chain fatty acids - Yu Zhao; Ran Ma; Yaoting Qi; Rong He; Zhenyu Zhu; Bo Wang; Ying Wang; Qiulin Yan; Maxime Julien; Youping Zhou (Organic Geochemistry, 2023)

Mechanism of arsenic distribution and migration during iron extraction by copper slag-steel slag combined reforming: A potential solution to refractory wastes - Yun Zhou; Hongyang Wang; Haichuan Wang; Kai Dong; Rong Zhu; Zhenqiang Jiang; Guangsheng Wei (Journal of Cleaner Production, 2023)

Structural characterization of a novel fucosylated trisaccharide prepared from bacterial exopolysaccharides and evaluation of its prebiotic activity - Mengshi Xiao; Xinmiao Ren; Jiaying Cheng; Xiaodan Fu; Rong Li; Changliang Zhu; Qing Kong; Haijin Mou (Food Chemistry, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Progress and perspective in enrichment and separation of radionuclide uranium by biomass functional materials - Jia Lei; Huanhuan Liu; Li Zhou; Yazhou Wang; Kaifu Yu; Hui Zhu; Bo Wang; Mengxuan Zang; Jian Zhou; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Effects of Long-term Non-application of Phosphorus Fertilizer on Bacterial Community Structure and Metabolite Profiles of Sweetpotato Rhizosphere - Xiaoya Zhu; Jing Wang; Qiangqiang Zhang; Peng Zhao; Ming Liu; Rong Jin; Yongchao Yu; Aijun Zhang; Zhonghou Tang (Journal of Soil Science and Plant Nutrition, 2023)

Hyperglycemia symptom amelioration by Ascophyllum nodosum polysaccharides in mice with type 2 diabetes - Ligen Chen; Liang Shen; Lingyun Zhu; Fengwei Li; Xiaodong Ge; Xiujuan Xia; Hongwei Yan; Tingting Liu; Wei Xu; Rong Shao (Algal Research, 2023)

The elements identification and model construction of rural tourism experience based on user-generated content - Zhongyuan Zhu; Rong Wang; Jing Hu (Environment, Development and Sustainability, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Insights into the roles of humic acids in facilitating the anaerobic digestion process - Rong Zhu; Miao Yan; Yun Zhang; Hua Zou; Yi Zheng; Rongbo Guo; Shanfei Fu (Waste Management, 2023)

Design, synthesis, and antibacterial activity of quinazolinone derivatives containing amides - Wenjuan Zhang; Yunying Zhu; Miaohe Zhang; Honglan Mou; Rong Wu; Shouying Tang; Han Zhou; Jianlin Luo; Xian Wei; Shuang Feng; Song Bai (Phytochemistry Letters, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

New insights into sulfur input induced methylmercury production and accumulation in paddy soil and rice - Yunyun Li; Nali Zhu; Wenjun Hu; Yu-rong Liu; Wen Jia; Guoming Lin; Hong Li; Yufeng Li; Yuxi Gao; Jiating Zhao (Journal of Hazardous Materials, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

Adsorption and catalytic degradation of bisphenol A and p-chlorophenol by magnetic carbon nanotubes - Huihui Gao; Xiaoyu Han; Rong Wang; Keke Zhu; Runping Han (Environmental Research, 2023)

Endocrine-disrupting chemicals and autoimmune diseases - Rong-Gui Huang; Xian-Bao Li; Yi-Yu Wang; Hong Wu; Kai-Di Li; Xue Jin; Yu-Jie Du; Hua Wang; Fang-Yi Qian; Bao-Zhu Li (Environmental Research, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

The rational utilization of organelle microenvironment for imaging of lysosomal SO2 with high fidelity - Caiyun Liu; Xiwei Li; Xiaodi Rong; Mingzhu Li; Miaohui Yu; Wenlong Sheng; Baocun Zhu (Analytica Chimica Acta, 2023)

Dauer larva-derived extracellular vesicles extend the life of Caenorhabditis elegans - Jing Ma; Yi-ting Wang; Ling-hui Chen; Bang-ya Yang; Yong-zhu Jiang; Lan-xi Wang; Zhi-qi Chen; Guan-rong Ma; Liao-qiong Fang; Zhi-biao Wang (Biogerontology, 2023)
There is growing evidence that extracellular vesicles (EVs) play a functional role in tissue repair and anti-aging by transferring the contents of donor cells to recipient cells. We hypothesized that Dauer ( C. elegans ), known as “ageless” nematodes, can also secrete extracellular vesicles and influence the lifespan of C. elegans . Here, we isolated EVs of dauer larvae (dauer EVs). Dauer EVs were characterized using transmission electron microscopy, nanoparticle tracking analysis (NTA), and Western blot analysis. Wild-type C. elegans were fed in the presence or absence of dauer EVs and tested for a range of phenotypes, including longevity, mobility and reproductive capacity. Results showed that dauer EVs increased the average lifespan of nematodes by 15.74%, improved mobility, slowed age-related pigmentation as well as body length, and reduced the accumulation of reactive oxygen species and lipids, while not impairing nematode reproductive capacity. These findings suggest that dauer EVs can extend the lifespan of C. elegans as well as the healthy lifespan by reducing ROS accumulation, with potential anti-aging capacity.

COVID-19 related antiviral drugs are less adsorbable on sediment under alkaline and high cation conditions - Xin Xu; Rong Zhu; Yun Zhang; Shannon L. Bartelt-Hunt; Hua Zou; Chen Chen (Science of The Total Environment, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

Label-free detection of trace level zearalenone in corn oil by surface-enhanced Raman spectroscopy (SERS) coupled with deep learning models - Jiaji Zhu; Xin Jiang; Yawen Rong; Wenya Wei; Shengde Wu; Tianhui Jiao; Quansheng Chen (Food Chemistry, 2023)

Determination of partial denitrification kinetic model parameters based on batch tests and metagenomic sequencing - Xinwei Su; Xiao-rong Zhu; Jianwei Li; Lei Wu; Xiyao Li; Qiong Zhang; Yongzhen Peng (Bioresource Technology, 2023)

Transformation of cognition from mechanical to biological aqueous outflow pump may be a breakthrough in solving the problem of intraocular pressure regulation in glaucoma - Shen Wu; Chen Xin; Wei Zhu; Yue Wan; Qing Sang; Rong Du; Jian Wu; Jin Wang; Ningli Wang (Science China Life Sciences, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

The synergistic hydration mechanism and environmental safety of multiple solid wastes in red mud-based cementitious materials - Junge Zhu; Hongzhi Yue; Laijun Ma; Zichao Li; Rong Bai (Environmental Science and Pollution Research, 2023)
Red mud (RM) is a solid waste material with high alkalinity and low cementing activity component. The low activity of RM makes it difficult to prepare high-performance cementitious materials from RM alone. Five groups of RM-based cementitious samples were prepared by adding steel slag (SS), grade 42.5 ordinary Portland cement (OPC), blast furnace slag cement (BFSC), flue gas desulfurization gypsum (FGDG), and fly ash (FA). The effects of different solid waste additives on the hydration mechanisms, mechanical properties, and environmental safety of RM-based cementitious materials were discussed and analyzed. The results showed that the samples prepared from different solid waste materials and RM formed similar hydration products, and the main products were C–S–H, tobermorite, and Ca(OH) 2 . The mechanical properties of the samples met the single flexural strength criterion (≥ 3.0 MPa) for first-grade pavement brick in the Industry Standard of Building Materials of the People's Republic of China-Concrete Pavement Brick . The alkali substances in the samples existed stably, and the leaching concentrations of the heavy metals reached class III of the surface water environmental quality standards. The radioactivity level was in the unrestricted range for main building materials and decorative materials. The results manifest that RM-based cementitious materials have the characteristics of environmentally friendly materials and possess the potential to partially or fully replace traditional cement in the development of engineering and construction applications and it provides innovative guidance for combined utilization of multi-solid waste materials and RM resources.

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

In-depth profiling of di(2-ethylhexyl) phthalate metabolic footprints in rats using click chemistry-mass spectrometry probes - Yu-Ning Hu; Jin-Tao Zhan; Pei-Rong Bai; Na An; Jun-Jie Tan; Yan-Zhen Wang; Quan-Fei Zhu; Yu-Qi Feng (Journal of Hazardous Materials, 2023)

Effects of fuel injection and energy efficiency on the production and environmental parameters of electric arc furnace -heat recovery systems - Bohan Tian; Guangsheng Wei; Hang Hu; Rong Zhu; Hao Bai; Ziming Wang; Lingzhi Yang (Journal of Cleaner Production, 2023)

Inactivation of Salmonella enteritidis on the surface of eggs by air activated with gliding arc discharge plasma - Li Guo; Pengyu Zhao; Zhiqian Yao; Tianhui Li; Mengying Zhu; Zifeng Wang; Lingling Huang; Gulimire Niyazi; Dingxin Liu; Mingzhe Rong (Food Control, 2023)

BPA exposure enhances the metastatic aggression of ovarian cancer through the ERα/AKT/mTOR/HIF-1α signaling axis - Xin Xie; Yan Zhu; Huimin Cheng; Haili Li; Yadi Zhang; Rong Wang; Wenyong Li; Fengrui Wu (Food and Chemical Toxicology, 2023)

Effects of saline immersion on the physiological alterations of grass goldfish (Carassius auratus) during subsequent recovery in freshwater - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Hua Zhu (Fish Physiology and Biochemistry, 2023)

Lithium extraction from salt lake brines with high magnesium/lithium ratio: a review - Rong Zhu; Shixin Wang; C. Srinivasakannan; Shiwei Li; Shaohua Yin; Libo Zhang; Xiaobin Jiang; Guoli Zhou; Ning Zhang (Environmental Chemistry Letters, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

Abundant bacterial subcommunity is structured by a stochastic process in an agricultural system with P fertilizer inputs - Lei Liu; Li Zhu; Rong Yan; Yu Yang; Jonathan M. Adams; Jinshan Liu (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Elevated CO2 alleviated the dissemination of antibiotic resistance genes in sulfadiazine-contaminated soil: A free-air CO2 enrichment study - Meiling Xu; Qian Xiang; Fen Xu; Lei Guo; Laura J. Carter; Wenchao Du; Chunwu Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Journal of Hazardous Materials, 2023)

Deciphering the distinct successional patterns and potential roles of abundant and rare microbial taxa of urban riverine plastisphere - Minghan Zhu; Xin Qi; Yibo Yuan; Heyang Zhou; Xufa Rong; Zhi Dang; Hua Yin (Journal of Hazardous Materials, 2023)

Screening of pesticides in serum, urine and cerebrospinal fluid collected from an urban population in China - Ke-Xin Zhao; Ming-Yan Zhang; Dan Yang; Rong-Shu Zhu; Zi-Feng Zhang; Ying-Hua Hu; Kurunthachalam Kannan (Journal of Hazardous Materials, 2023)

Computational design of deep eutectic solvent functionalized ZIF-8/biochar with high selectivity for mephedrone: Experimental validation and microscopic mechanism - Rong Zhu; Shurui Cao; Jie Tian; Mengni Luo; Jiade You; Zhiqiong Chen (Journal of Cleaner Production, 2023)

Linear and nonlinear interface rheological behaviors and structural properties of pea protein (vicilin, legumin, albumin) - Qian Shen; Jing Li; Xiaojun Shen; Xinyu Zhu; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

“Sandwich-like” electrospinning fiber-based molecularly imprinted membrane constructed with electrospun polyethyleneimine as the multifunction interlayer for the selective separation of shikimic acid - Yao Zhu; Yuting Dai; Jian Rong; Tao Zhang; Songlin Xue; Dongya Yang; Jianming Pan; Fengxian Qiu (Chemical Engineering Journal, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

CRISPR/Cas9-based point-of-care lateral flow biosensor with improved performance for rapid and robust detection of Mycoplasma pneumonia - Rong Zhu; Han Jiang; Chaoyou Li; Yan Li; Min Peng; Junfeng Wang; Qian Wu; Chao Yan; Qingli Bo; Jie Wang; Chenlin Shen; Panzhu Qin (Analytica Chimica Acta, 2023)

Molecular identification of a flavone synthase I/flavanone 3β-hydroxylase bifunctional enzyme from fern species Psilotum nudum - Jie Fu; Piao-Yi Wang; Rong Ni; Jiao-Zhen Zhang; Ting-Ting Zhu; Hui Tan; Jing Zhang; Hong-Xiang Lou; Ai-Xia Cheng (Plant Science, 2023)

TiO2/g-C3N4 photoanode prepared with polydopamine inspiration for photocatalytic fuel cells towards simultaneous wastewater treatment and electricity generation - Yuxin Liu; Lin Chen; Jinwang Li; Rong Chen; Xun Zhu; Dingding Ye; Yang Yang; Qiang Liao (Journal of Water Process Engineering, 2023)

Gas diffusion TiO2 photoanode for photocatalytic fuel cell towards simultaneous VOCs degradation and electricity generation - Chongyi Wang; Yuxin Liu; Rong Chen; Xun Zhu; Dingding Ye; Yang Yang; Qiang Liao (Journal of Hazardous Materials, 2023)

Purple red rice bran anthocyanins reduce the digestibility of rice starch by forming V-type inclusion complexes - Weidong Zhang; Haibin Zhu; Liyuan Rong; Yi Chen; Qiang Yu; Mingyue Shen; Jianhua Xie (Food Research International, 2023)

Photocatalysis-self-Fenton system over edge covalently modified g-C3N4 with high mineralization of persistent organic pollutants - Tongbin Lu; Hui Zhao; Liang Jian; Rong Ji; Chengsi Pan; Guangli Wang; Yuming Dong; Yongfa Zhu (Environmental Research, 2023)

IL-17A inhibits the degradation of RANKL in osteoblasts by inhibiting BCL2-Beclin1-autophagy signaling - Xia-xia Chen; Hao-jie Wu; Dian-shan Ke; Yun-rong Zhu (In Vitro Cellular & Developmental Biology - Animal, 2023)

Adult lumbosacral spina bifida with giant myelomeningocele: a case report - Yuhang Diao; Hongtao Rong; Tao Zhu (Acta Neurologica Belgica, 2023)

Experimental evaluation of a hybrid solar dryer with flexible open sorption thermal energy storage unit on demand for burdock root drying - Rong Zhu; Qiongfen Yu; Ming Li; Yiping Xia; Aimin Li; Danya Zhan; Yinning Li; Yunfeng Wang (Environmental Science and Pollution Research, 2023)

Study on hydration mechanism and environmental safety of thermal activated red mud-based cementitious materials - Junge Zhu; Hongzhi Yue; Laijun Ma; Zichao Li; Rong Bai (Environmental Science and Pollution Research, 2023)
Red mud (RM) cementitious materials were prepared with the thermally, thermoalkali- or thermocalcium-activated RM, steel slag (SS), and other additives. The effects of different thermal RM activation methods on the cementitious material hydration mechanisms, mechanical properties, and environmental risks were discussed and analyzed. The results showed that the hydration products of different thermally activated RM samples were similar with the main products being C-S–H, tobermorite, and Ca(OH) 2 . Ca(OH) 2 was mainly present in thermally activated RM samples, and the tobermorite was mainly produced by samples prepared with thermoalkali- and the thermocalcium-activated RM. The mechanical properties of the samples prepared by thermally and thermocalcium-activated RM had early-strength properties, while the thermoalkali-activated RM samples were similar to the late-strength type of cement properties. The average flexural strength of thermally and the thermocalcium-activated RM samples at 14 days were 3.75 MPa and 3.87 MPa respectively, whereas, the 1000 °C thermoalkali-activated RM samples only at 28 days was 3.26 MPa; the above data could reach the single flexural strength (3.0 MPa) of the first-grade pavement blocks of the building materials industry standard of the People’s Republic of China-concrete pavement blocks (JC/T446-2000). The optimal preactivated temperature for different thermally activated RM was different; the optimal preactivated temperature for both thermally and thermocalcium-activated RM was 900 °C, and the flexural strength was 4.46 MPa and 4.35 MPa, respectively. However, the optimal preactivated temperature of thermoalkali activated RM at 1000 °C. The 900 °C thermally activated RM samples had better solidified effects for heavy metal elements and alkali substances. 600~800℃ thermoalkali activated RM samples had better solidified effects for heavy metal elements. Different temperatures of thermocalcium-activated RM samples showed different solidified effects on different heavy metal elements, which may be due to the influence of thermocalcium activation temperature on the structural changes of the hydration products of the cementitious samples. In this study, three thermal RM activation methods were proposed, and the co-hydration mechanism and environmental risk study of different thermally activated RM and SS were further elucidated. This not only provides an effective method for the pretreatment and safe utilization of RM, but also facilitates the synergistic resource treatment of solid waste and further promotes the research process of replacing part of traditional cement with solid waste.

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Effect of super-absorbent polymer on swelling pressure of compacted bentonite infiltrated by alkaline solutions - Zhang-Rong Liu; Wei-Min Ye; He-Hua Zhu; Qiong Wang; Yong-Gui Chen (Applied Clay Science, 2023)

Synthetic strategies and applications towards carbon nanorings and carbon nanobelts - Rong Zhang; Jiangyu Zhu; Dongyue An; Xuefeng Lu; Yunqi Liu (Science Bulletin, 2023)

Successive choline addition enhancing the methanogenesis of waste activated sludge anaerobic digestion: Insight from hydrophilicity, electrochemical performance and microbial community - Rong Jin; Jiajia Xu; Zhuoqin Wang; Nanwen Zhu; Ziyang Lou; Haiping Yuan (Journal of Environmental Management, 2023)

Integrated toxicology, metabolomics, and transcriptomics analyses reveal the biodegradation and adaptation mechanisms to BDE-47 in Pseudomonas plecoglossicida - Xin Qi; Minghan Zhu; Yibo Yuan; Xufa Rong; Zhi Dang; Hua Yin (Chemical Engineering Journal, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Directional introduction of pyridine nitrogen functional groups in activated carbon catalysts for the catalytic production of hydrogen: An experimental and DFT calculation - Sida Rong; Liqiang Zhang; Ziyi Yue; Zhanlong Song; Wenjing Tang; Xiao Zhu; Tao Wang; Xiaohan Zhou; Shanjie Cheng; Xiao Xia (Chemical Engineering Journal, 2023)

An integrated process for co-producing fermentable sugars and xylonate from sugarcane bagasse based on xylonic acid assisted pretreatment - Zhen Zhu; Rong Huang; Shuangquan Yao; Yiruo Liu; Qibo Zhang; Xin Zhou; Kankan Jiang (Bioresource Technology, 2023)

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Multicopper oxidases GbAO and GbSKS are involved in the Verticillium dahliae resistance in Gossypium barbadense - Fei Wang; Tianxin Lu; Liping Zhu; Aiping Cao; Shuangquan Xie; Xifeng Chen; Haitao Shen; Quanliang Xie; Rong Li; Jianbo Zhu; Xiang Jin; Hongbin Li (Journal of Plant Physiology, 2023)

Strengthen the purification of eutrophic water and improve the characteristics of sediment by functional ecological floating bed suspended calcium peroxide and sponge iron jointly - Zheng Zhu; Yi Wang; Xue-Yi Han; Wen-Huai Wang; Hao-Min Li; Zi-Qi Yue; Wei Chen; Fu-Rong Xue (Journal of Environmental Management, 2023)

Effects of substituting municipal waste incineration fly ash for lime on generating a bonding phase during the sintering process - Zhenqiang Jiang; Kai Dong; Hongyang Wang; Yun Zhou; Bohan Tian; Xin Li; Rong Zhu (Journal of Cleaner Production, 2023)

Elevated CO2 aggravated polystyrene microplastics effects on the rice-soil system under field conditions - Meiling Xu; Qiao Xu; Guobing Wang; Wenchao Du; Jianguo Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Environmental Pollution, 2023)

Galvanic replacement reaction-regulated photoelectric response and enzyme-mimicking property of ionic liquid functionalized Cu@Cu2O aerogels for dual-mode immunoassay - Jinli Li; Hengjia Wang; Mingwang Liu; Ying Qin; Rong Tan; Liuyong Hu; Wenling Gu; Chengzhou Zhu (Chemical Engineering Journal, 2023)

Construction of modified MXene with “organic–inorganic” structure to enhance the interfacial and mechanical properties of UHMWPE fiber-reinforced epoxy composite - Kui Wang; Lu Shen; Qixuan Zhu; Rouyu Bo; Rong Lu; Xiaoshu Lu; Zixuan Fu (Chemical Engineering Journal, 2023)

Carbonate nanophase guided by terminally functionalized polyisoprene leading to a super tough, recyclable and transparent rubber - Mo-Kun Chen; Yi-Hai Zhao; Rong Zhang; Ying Yang; Jian Cao; Mao-Zhu Tang; Guangsu Huang; Yun-Xiang Xu (Chemical Engineering Journal, 2023)

Ultra-thin and highly flexible silver fractal dendrite/polyvinylidene fluoride composite film for efficient electromagnetic interference shielding - Zuomin Lei; Jianhong Wei; Zhiqiang Lin; Tao Zhao; Yougen Hu; Pengli Zhu; Rong Sun (Chemical Engineering Journal, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

A strategy for screening and identification of new amino acid-conjugated bile acids with high coverage by liquid chromatography-mass spectrometry - Yan-Zhen Wang; Peng-Cheng Mei; Pei-Rong Bai; Na An; Jin-Gang He; Jie Wang; Quan-Fei Zhu; Yu-Qi Feng (Analytica Chimica Acta, 2023)

Dibenzofurans from Crataegus oresbia and their lipid-lowering activity - Ying Wang; Li-Juan Lang; Qi-Jie Zhu; Xiu-Rong Wu; Lei Shen; Bei Jiang; Chao-Jiang Xiao (Natural Product Research, 2022)

QNE1 is a key flowering regulator determining the length of the vegetative period in soybean cultivars - Zhengjun Xia; Hong Zhai; Yanfeng Zhang; Yaying Wang; Lu Wang; Kun Xu; Hongyan Wu; Jinglong Zhu; Shuang Jiao; Zhao Wan; Xiaobin Zhu; Yi Gao; et al. (Science China Life Sciences, 2022)

Concentrations, distribution, and risk assessment of endosulfan residues in the cotton fields of northern Xinjiang, China - Yang Zhang; Rong Guo; Yang Li; Mingyu Qin; Jingquan Zhu; Zhihong Ma; Yong Ren (Environmental Geochemistry and Health, 2022)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Neural Stem Cells Therapy for Ischemic Stroke: Progress and Challenges - Tong Zhao; Tongming Zhu; Liqian Xie; Yao Li; Rong Xie; Feng Xu; Hailiang Tang; Jianhong Zhu (Translational Stroke Research, 2022)

Hsa_circ_0070194 targets the miR-384/HDAC2 axis to enhance proliferation, cell cycle, migration and invasion of trophoblast cells - Huan Chen; Cheng Gao; Wenhui Zhu; Rong Wan; Mei Xiong (Molecular & Cellular Toxicology, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Occurrence, distribution, and ecological risk of organophosphorus flame retardants and their degradation products in water and upper sediment of two urban rivers in Shenzhen, China - Yunlang Liu; Zuoming Xie; Tingting Zhu; Chen Deng; XiuJuan Qi; Rong Hu; Jinglin Wang; Jianyi Chen (Environmental Science and Pollution Research, 2022)

Correction to: Genome-wide identifcation and characterization of the C2 domain family in Sorghum bicolor (L.) and expression profles in response to saline–alkali stress - Jiangshuai Niu; Zhijiang Li; Jiarui Zhu; Rong Wu; Lingxin Kong; Tingli Niu; Xueying Li; Xinran Cheng; Jianying Li; Lingyan Dai (Physiology and Molecular Biology of Plants, 2022)

Genome-wide identification and characterization of the C2 domain family in Sorghum bicolor (L.) and expression profiles in response to saline–alkali stress - Jiangshuai Niu; Zhijiang Li; Jiarui Zhu; Rong Wu; Lingxin Kong; Tingli Niu; Xueying Li; Xinran Cheng; Jianying Li; Lingyan Dai (Physiology and Molecular Biology of Plants, 2022)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

MicroRNA-339-5p inhibits lipopolysaccharide-induced rat mesangial cells by regulating the Syk/Ras/c-Fos pathway - Jia Rong Gao; Miao Miao Shi; Hui Jiang; Xiao Li Zhu; Liang Bing Wei; Xiu Juan Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Fast forward modeling of muon transmission tomography based on model voxelization ray energy loss projection - Rong-Qing Zhang; Zhen-Zhu Xi; Wei Liu; He Wang; Zi-Yan Yang (Applied Geophysics, 2022)

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Comparative analysis of the structure and function of rhizosphere microbiome of the Chinese medicinal herb Alisma in different regions - Chenbin Wei; Wei Gu; Rong Tian; Fei Xu; Yun Han; Yuanyuan Ji; Tao Li; Yu Zhu; Peilei Lang; Wenqing Wu (Archives of Microbiology, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Numerical and Experimental Investigations on Hydrodynamic Performance of a Newly Designed Deep Bottom Trawl - Qinglong Guan; Wenbin Zhu; Aizhong Zhou; Yongjin Wang; Weiyao Tang; Rong Wan (Frontiers in Marine Science, 2022)
In this paper, a new type of bottom trawl was designed for target fishing vessels to use in deep-water fishing grounds. The trawl’s hydrodynamic performance was investigated using numerical simulation and physical modeling methods, and a numerical model based on the finite element method was proposed for estimating hydrodynamic forces and predicting performances. A series of physical model tests based on Tauti’s law were carried out in a towing tank to explore the hydrodynamic performance of the trawl and to assess the applicability of the numerical simulation method. The results showed that the working towing speed of the trawl was 3.5 kn. The drag force and the height of net opening were 50 kN and 5.62 m, respectively, and the swept area was 128 m 2 at that speed. The simulated result was close to the experimental result, with a maximum relative error less than 20%, and an average relative error of 10%. The net shape and tension distribution of the trawl were analyzed using the numerical simulation method, and the hanging ratio in T-direction of the mesh of the codend was 0.25 at the working towing speed. The newly designed deep bottom trawl had a superior hydrodynamic performance for high catch efficiency and selectivity and may be applied to commercial fishing operations.

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

First report of Botryosphaeria dothidea causing leaf blotch of Mahonia bealei in China - Yi-Jia Cao; Rong-Han Chen; Yuan-Zhi Si; Li-Hua Zhu (Journal of Plant Pathology, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Experimental Study on Mechanical Properties of Highly Swelling Soft Rocks in the Yanji Basin, Northern China - Rong Zhao; Xiong Wu; Ge Zhu; Xiaolei Wang; Aoshuang Mei; Xiao Zhang (Rock Mechanics and Rock Engineering, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Effect of Fertilization Regimes and Seasonal Change on nosZ-Denitrifying Bacterial Community in a Double-Rice Paddy Field - Jiangwen Nie; Yong Zhou; Wei Yang; Shaoqiu Li; Haoxuan Li; Jianwei Wu; Chengwei Li; Xiaoyuan Yan; Rong Zhu; Bo Zhu; Zhangyong Liu (Journal of Soil Science and Plant Nutrition, 2022)

Consequences of elevated temperature on the biology, predation, and competitiveness of two mirid predators in the rice ecosystem - Yueliang Bai; Md. Khairul Quais; Wenwu Zhou; Zeng-Rong Zhu (Journal of Pest Science, 2022)

Comparison of nominal and standardized catch per unit effort data in quantifying habitat suitability of skipjack tuna in the equatorial Pacific Ocean - Cheng Zhou; Yuanyuan Hu; Jie Cao; Liuxiong Xu; Xuefang Wang; Rong Wan; Yu Xiao; Jiangfeng Zhu; Hao Tang (Acta Oceanologica Sinica, 2022)

Metabolism in the Midwest: research from the Midwest Aging Consortium at the 49th Annual Meeting of the American Aging Association - Michaela E. Murphy; Akilavalli Narasimhan; Alexis Adrian; Ankur Kumar; Cara L. Green; Carolina Soto-Palma; Chathurika Henpita; Christina Camell; Christopher S. Morrow; Chung-Yang Yeh; Claire E. Richardson; Cristal M. Hill; et al. (GeroScience, 2022)

Analysis of Ground Settlement Caused by Double-line TBM Tunnelling Under Existing Building - Dongxue Hao; Renjun Zhu; Ke Wu; Rong Chen (Geotechnical and Geological Engineering, 2022)

An ocean modeling study to quantify wind forcing and oceanic mixing effects on the tropical North Pacific subsurface warm bias in CMIP and OMIP simulations - Yuchao Zhu; Rong-Hua Zhang; Delei Li (Climate Dynamics, 2022)

Flavobacterium proteolyticum sp. nov., isolated from aquaculture water - Juan Du; Yang Liu; Tao Pei; Anzhang Li; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

Croceicoccus gelatinilyticus sp. nov., isolated from a tidal flat sediment - Tao Pei; Yang Liu; Juan Du; Kunpeng Huang; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

Dielectric constants of organic pollutants determine their strength for enhancing microbial iron reduction - Shan Liu; Hui Liu; Yao Huang; Jie Ma; Zhu Wang; Rong Chen (Environmental Science and Pollution Research, 2021)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

Isolation of two sesquiterpene glycosides from Sapindus mukorossi Gaertn. with cytotoxic properties and analysis of their mechanism based on network pharmacology - Min-ping Wei; Xiao-wen Zhu; Hang Yu; Yun-fei Xie; Ya-hui Guo; Yu-liang Cheng; He Qian; Wei-rong Yao (Natural Product Research, 2021)

One new α , β -unsaturated 7-ketone sterol from the mangrove-derived fungus Phomopsis sp.MGF222 - Xiao-Chen Zhu; Guo-Lei Huang; Rong-Qing Mei; Bin Wang; Xue-Ping Sun; You-Ping Luo; Jing Xu; Cai-Juan Zheng (Natural Product Research, 2021)

Responses of the ecological characteristics and antioxidant enzyme activities in Rotaria rotatoria to UV-B radiation - Lingyun Zhu; Rong Huang; Libin Zhou; Yilong Xi; Xianling Xiang (Hydrobiologia, 2021)

CARMA1 is required for Notch1-induced NF-κB activation in SIL-TAL1-negative T cell acute lymphoblastic leukemia - Ninghan Zhang; Jiawen Xu; Rong Wang; Ting Pan; Huanxin Zhang; Lingling Yin; Yao Yao; Linyan Xu; Shengyun Zhu; Qingyun Wu; Zhenyu Li; Xuejiao Liu; et al. (Journal of Molecular Medicine, 2021)

Circular RNA circ_Cabin1 promotes DNA damage in multiple mouse organs via inhibition of non-homologous end-joining repair upon PM2.5 exposure - Huixian Zeng; Meizhen Li; Qiuhan Hua; Yufei Liu; Yueting Shao; Qinqin Diao; Yihui Ling; Han Zhang; Miaoyun Qiu; Jialu Zhu; Xun Li; Rong Zhang; et al. (Archives of Toxicology, 2021)

Mystery of methamphetamine-induced autophagosome accumulation in hippocampal neurons: loss of syntaxin 17 in defects of dynein–dynactin driving and autophagosome–late endosome/lysosome fusion - Huaisha Xu; Yuanhui Zhu; Xufeng Chen; Tingyu Yang; Xi Wang; Xu Song; Xuexue Xie; Miaoyang Hu; Lei Jiang; Jie Cheng; Rong Gao; Jun Wang (Archives of Toxicology, 2021)

A new atypical short‐chain dehydrogenase is required for interfungal combat and conidiation in Trichoderma guizhouense - Hong Zhu; Jian Zhang; Qi Gao; Guan Pang; Tingting Sun; Rong Li; Zhenzhong Yu; Qirong Shen (Environmental Microbiology, 2021)
Summary Hypocrealean Trichoderma are the most extensively studied facultative mycoparasites against phytopathogenic fungi. Aerial hyphae of Trichoderma guizhouense can rapidly proliferate over Fusarium oxysporum hyphae, cause sporadic cell death and arrest the growth of the host. The results of the present study demonstrated that a unique short‐chain dehydrogenase/reductase (SDR), designated as TgSDR1, was expressed at a high level in T . guizhouense challenged by the hosts. Similar to other SDRs family members, the TgSDR1 protein contains a cofactor‐binding motif and a catalytic site. The subcellular localization assay revealed that the TgSDR1::GFP fusion protein translocated to lipid droplets in mycelia and conidia. The data obtained using reverse genetic approach indicated that TgSDR1 is associated with antifungal ability, plays an important role in providing reducing equivalents in the form of NADPH and regulates the amino sugar and nucleotide sugar metabolism in T . guizhouense upon encountering a host. Moreover, the TgSDR1 deletion mutant was defective in conidiation. Thus, TgSDR1 functions as a key metabolic enzyme in T . guizhouense to regulate mycotrophic interactions, defence against other fungi, such as F . oxysporum , and conidiation.

Toxicity of disinfection byproducts formed during the chlorination of sulfamethoxazole, norfloxacin, and 17β-estradiol in the presence of bromide - Yuanyuan Zhang; Yunjie Zhu; Yanan Shao; Chuan Rong; Zihan Pan; Jie Deng (Environmental Science and Pollution Research, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Deletion of Nrip1 delays skin aging by reducing adipose-derived mesenchymal stem cells (ADMSCs) senescence, and maintaining ADMSCs quiescence - Yu Hu; Yun Zhu; Skyler D. Gerber; Jared M. Osland; Min Chen; Krishna A. Rao; Heng Gu; Rong Yuan (GeroScience, 2021)

Exposure to antibiotics and mental disorders in children: a community-based cross-sectional study - Jingjing Zhang; Kaiyong Liu; Liang Sun; Linsheng Yang; Xinji Liu; Yitian Zhu; Rong Wei; Zhongxiu Jin; Li Wang; Ying Ma; Sufang Wang; Annuo Liu; et al. (Environmental Geochemistry and Health, 2021)

Inhella proteolytica sp. nov. and Inhella gelatinilytica sp. nov., two novel species of the genus Inhella isolated from aquaculture water - Yang Liu; Tao Pei; Juan Du; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Exposure to outdoor air pollution at different periods and the risk of leukemia: a meta-analysis - Tong Wei; Rong Jiao; Rena Nakyeyune; Zhaoping Zang; Yi Shao; Yi Shen; Chen Niu; Lingyan Zhu; Xiaoli Ruan; Fen Liu (Environmental Science and Pollution Research, 2021)

Qipengyuania soli sp. nov., Isolated from Mangrove Soil - Yang Liu; Tao Pei; Ming-Rong Deng; Honghui Zhu (Current Microbiology, 2021)

Distinctive distributions of halophilic Archaea across hypersaline environments within the Qaidam Basin of China - Derui Zhu; Guoping Shen; Zhibo Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Yongzhen Li; Rong Wang (Archives of Microbiology, 2021)

Technology and Concept of Wastewater Treatment: Differences Between the Rhine Basin and the Yangtze Basin - Chenyu Zhu; Boyang Zhu; Xueyuan Gu; Mei Li; Rong Ji; Qing Zhou (Bulletin of Environmental Contamination and Toxicology, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

The dynamics and release characteristics of microcystins in the plateau Lake Erhai, Southwest China - Rong Zhu; Huan Wang; Hong Shen; Xuwei Deng; Jun Chen (Environmental Science and Pollution Research, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Variation in rare earth element (REE), aluminium (Al) and silicon (Si) accumulation among populations of the hyperaccumulator Dicranopteris linearis in southern China - Wen-Shen Liu; Hong-Xiang Zheng; Chang Liu; Mei-Na Guo; Shi-Chen Zhu; Yue Cao; Rong-Liang Qiu; Jean Louis Morel; Antony van der Ent; Ye-Tao Tang (Plant and Soil, 2021)

Late Cretaceous granitic magmatism and Sn mineralization in the giant Yinyan porphyry tin deposit, South China: constraints from zircon and cassiterite U–Pb and molybdenite Re–Os geochronology - Peng-Cheng Hu; Wei-Guang Zhu; Hong Zhong; Rong-Qing Zhang; Xiao-Yu Zhao; Wei Mao (Mineralium Deposita, 2021)

Chlamydia trachomatis induces autophagy by p62 in HeLa cell - Fuyan Wang; Hongbo Zhang; Xiaofang Lu; Quan Zhu; Tingting Shi; Rong Lu; Ping Yu; Lei Zhang; Yong Wang (World Journal of Microbiology and Biotechnology, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

Identification of genetic variants in m6A modification genes associated with pancreatic cancer risk in the Chinese population - Pingting Ying; Yao Li; Nan Yang; Xiaoyang Wang; Haoxue Wang; Heng He; Bin Li; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Xiaoping Miao; et al. (Archives of Toxicology, 2021)

A New Record of Oxytricha granulifera granulifera Foissner and Adam, 1983 (Protozoa, Ciliophora, Oxytrichidae) From a Hot Spring in Iceland, With Notes on Its Abnormal Form During Cultivation - Rong Zhu; Zhishuai Qu; Qi Zhang; Sabine Filker; Thorsten Stoeck; Fengchao Li; Xiaozhong Hu (Frontiers in Marine Science, 2021)
We isolated a population of Oxytricha granulifera granulifera Foissner and Adam (1983) from a hot spring in Iceland. The pure culture of this isolate was established at room temperature in the laboratory. This allowed for a detailed investigation, informed by integrated approaches, of the isolate’s morphology and morphogenesis, as well as molecular phylogeny. Results showed that the morphological and morphogenetic characteristics of the Iceland population are consistent with those of other populations. During the 3-year long period of laboratory cultivation, some abnormal individuals appeared repeatedly in the culture system. Interestingly, the morphological characteristics of these abnormal cells were rather stable, and were as follows: 1) body slender and elliptical-shaped; 2) remarkably shortened adoral zone and significantly reduced number of adoral membranelles; and 3) loss of undulating membranes. Resting cysts, binary fission and conjugate reproduction were not found in abnormal specimens. Although the morphology of abnormal individuals changed significantly, the sequences of the SSU rDNA of the normal and abnormal morphotypes were the same. Phylogenetic analyses showed that the two morphotypes clustered in a clade with other populations of O. granulifera granulifera .

Prenatal Stress Leads to the Altered Maturation of Corticostriatal Synaptic Plasticity and Related Behavioral Impairments Through Epigenetic Modifications of Dopamine D2 Receptor in Mice - Yingchun Li; Jing Rong; Haiquan Zhong; Min Liang; Chunting Zhu; Fei Chang; Rong Zhou (Molecular Neurobiology, 2021)

Risk of congenital heart disease due to exposure to common electrical appliances during early pregnancy: a case-control study - Doudou Zhao; Leqian Guo; Ruo Zhang; Qixia Zhu; Hongli Wang; Rong Liu; Hong Yan; Shaonong Dang (Environmental Science and Pollution Research, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Red elemental selenium (Se 0 ) improves the immunoactivities of EPC cells, crucian carp and zebrafish against spring viraemia of carp virus - Jinbao Tian; Yong Zhang; Rong Zhu; Yeqing Wu; Xiaoxiao Liu; Xingguo Wang (Journal of Fish Biology, 2021)
Selenium, as an essential trace element, interferes through selenoproteins in many physiological processes of plants and mammals. Its antiviral activity has recently attracted much attention because selenium improves the antiviral capacity of animal cells against a few viruses relevant to human diseases. In this study, the red elemental selenium was purified from the fermentative culture of Herbaspirillum camelliae WT00C and then used to culture epithelioma papulosum cyprinid (EPC) cells or feed crucian carp and zebrafish. Finally, its antiviral effects were investigated at the cell level and living fishes after spring viraemia of carp virus infection. At the cell level, 5, 10 and 20 μg ml –1 red elemental selenium significantly induced the expression of interferon ( IFN ) and ISG 15 genes in EPC cells. The viral TCID 50 (50% tissue culture infective dose) values in the EPC cells incubated with 5, 10 and 20 μg ml –1 red elemental selenium were significantly less than those of the control. More expression of IFN and ISG 15 genes and less TCID 50 values indicate that red elemental selenium indeed improves the antiviral capability of EPC cells. In the crucian carp fed with the food containing 5 and 10 μg g –1 red elemental selenium, IFN expressions showed 13‐ and 39‐fold increases at the 16th day of post‐injection, and its expression was dependent on selenium concentrations. Meanwhile, no fish death occurred in all the experimental groups. In the zebrafish fed with the red worm containing 5 μg g –1 red elemental selenium, IFN and Mx expressions and survival rate were significantly higher than those of the control. The results of this study show that red elemental selenium indeed improves the antiviral activity of fish. The antiviral effects of selenium mainly come from its immune regulation through its incorporation into selenoproteins. The optimum level of selenium contributes to improving fish immunity, whereas excess selenium causes excessive immune and inflammatory responses.

Spatial variability of bigeye tuna habitat in the Pacific Ocean: Hindcast from a refined ecological niche model - Cheng Zhou; Rong Wan; Jie Cao; Liuxiong Xu; Xuefang Wang; Jiangfeng Zhu (Fisheries Oceanography, 2021)
Habitat distribution is critically informative for stock assessment, since incorporating its variabilities can have important implications for the estimation of stock biomass or the relative abundance index. A refined ecological niche model with habitat characteristic parameterization was developed to reconstitute a 3‐D ecological map of bigeye tuna in the Pacific Ocean. We determined the boundaries and hierarchies of oceanographic features and hydrological conditions at horizontal and vertical scales to define the habitat preference of bigeye tuna associated with their feeding and physiological requirements. Ecogeographic projections underlined the depth‐ and region‐specific habitat distribution of bigeye tuna, with noticeable dynamic variations in the response to climate variability. Depths from 300 to 400 m represented layers of the most productive habitat, which was widespread through the equatorial Pacific Ocean and extended to the north‐central Pacific Ocean. The proportion of high‐quality habitat size in the north Pacific had a strictly regular intra‐annual cycle with peaks during the winter. Climate variability appeared to disturb the balance of the regular fluctuations in habitat size in the equatorial Pacific. Habitat hotspots during an El Niño period were characterized by their expansion to the north of the Hawaiian islands, shrinkage in the west for the hotspot band north of the Equator, and an eastern shift for the band south of the Equator. This variability may be the consequence of the incorporated fluctuations of the oxygen minimum zones (OMZ), current systems, and stratification in the open ocean.

Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Tectochrysin increases stress resistance and extends the lifespan of Caenorhabditis elegans via FOXO/DAF-16 - Min Lu; Lin Tan; Xiao-Gang Zhou; Zhong-Lin Yang; Qing Zhu; Jian-Ning Chen; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

Bacterial and Archaeal Communities within an Ultraoligotrophic, High-altitude Lake in the Pre-Himalayas of the Qinghai-Tibet Plateau - Rong Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Derui Zhu (Indian Journal of Microbiology, 2020)

A Review of Co3O4-based Catalysts for Formaldehyde Oxidation at Low Temperature: Effect Parameters and Reaction Mechanism - Rong Li; Yu Huang; Dandan Zhu; Wingkei Ho; Shuncheng Lee; Junji Cao (Aerosol Science and Engineering, 2020)

Climate-related risks in the construction of Xiongan New Area, China - Yujie Wang; Lianchun Song; Zhenyu Han; Yaoming Liao; Hongmei Xu; Jianqing Zhai; Rong Zhu (Theoretical and Applied Climatology, 2020)
In the paper, we analyze the climate-related risks of rainstorm floods, droughts and water shortages, high temperatures, and heavy hazes in the Xiongan New Area. A warming and drying trend was seen in Xiongan New Area during 1961–2018, as evidenced by the increase in the number of high-temperature days and the maximum rainfall intensity per hour, a decrease in surface water resources and groundwater levels, a reduction in wind speeds, and weakening of the self-purification capacity of the atmosphere. It is estimated that the areas at high risk of floods and heats will increase by 15.7 and 15.6% in around 2035 relative to 1986–2005, respectively. Although the runoff in the Daqing River Basin will increase, the construction of Xiongan New Area means that the imbalance between the supply and demand of water resources will remain. Climate change adaptation measures should therefore be improved in the planning and construction of Xiongan New Area. Finally, we discuss the approaches to address climate-related risks in this new area.

Comparison of the effects of deep and moderate neuromuscular block on respiratory system compliance and surgical space conditions during robot-assisted laparoscopic radical prostatectomy: a randomized clinical study - Shao-jun Zhu; Xiao-lin Zhang; Qing Xie; Yan-feng Zhou; Kui-rong Wang (Journal of Zhejiang University-SCIENCE B, 2020)

An update of the Worldwide Integrated Assessment (WIA) on systemic pesticides. Part 4: Alternatives in major cropping systems - Andrea Veres; Kris A. G. Wyckhuys; Jozsef Kiss; Ferenc Tóth; Giovanni Burgio; Xavier Pons; Carlos Avilla; Stefan Vidal; Jaka Razinger; Renata Bazok; Ewa Matyjaszczyk; Ivan Milosavljević; et al. (Environmental Science and Pollution Research, 2020)
We present a synthetic review and expert consultation that assesses the actual risks posed by arthropod pests in four major crops, identifies targets for integrated pest management (IPM) in terms of cultivated land needing pest control and gauges the implementation “readiness” of non-chemical alternatives. Our assessment focuses on the world’s primary target pests for neonicotinoid-based management: western corn rootworm (WCR, Diabrotica virgifera virgifera ) in maize; wireworms ( Agriotes spp.) in maize and winter wheat; bird cherry-oat aphid ( Rhopalosiphum padi ) in winter wheat; brown planthopper (BPH, Nilaparvata lugens ) in rice; cotton aphid ( Aphis gossypii ) and silver-leaf whitefly (SLW, Bemisia tabaci ) in cotton. First, we queried scientific literature databases and consulted experts from different countries in Europe, North America, and Asia about available IPM tools for each crop-pest system. Next, using an online survey, we quantitatively assessed the economic relevance of target pests by compiling country-level records of crop damage, yield impacts, extent of insecticide usage, and “readiness” status of various pest management alternatives (i.e., research, plot-scale validation, grower-uptake). Biological control received considerable scientific attention, while agronomic strategies (e.g., crop rotation), insurance schemes, decision support systems (DSS), and innovative pesticide application modes were listed as key alternatives. Our study identifies opportunities to advance applied research, IPM technology validation, and grower education to halt or drastically reduce our over-reliance on systemic insecticides globally.

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

A Novel Eyes Topical Drug Delivery System: CsA-LNC for the Treatment of DED - Anan Zhang; Rong Sun; Meixin Ran; Yaxin Deng; Ying Ge; Yunjing Zhu; Xiumei Tao; Lixia Shang; Jingxin Gou; Haibing He; Tian Yin; Yanjiao Wang; et al. (Pharmaceutical Research, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Translocator protein 18 kDa: a potential therapeutic biomarker for post traumatic stress disorder - Zhi-Kun Qiu; Xu Liu; Yong Chen; Rong-Jia Wu; Shi-Feng Guan; Yun-yun Pan; Qian-Bo Wang; Dan Tang; Tao Zhu; Ji-Sheng Chen (Metabolic Brain Disease, 2020)

Central autonomic network functional connectivity: correlation with baroreflex function and cardiovascular variability in older adults - Kan Ding; Takashi Tarumi; Ciwen Wang; Steven Vernino; Rong Zhang; David C. Zhu (Brain Structure and Function, 2020)

Interaction between Translocation-associated membrane protein 1 and σC protein of novel duck reovirus controls virus infectivity - Rong Xiao; Xiaoyun Mi; Jiahui Sun; Mingyang Ding; Chuanfeng Li; Jie Zhu; Guangqing Liu; Wenge Ma; Hailong Zhou; Zongyan Chen (Virus Genes, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Functional characterization of a low-frequency V1937I variant in FASN associated with susceptibility to esophageal squamous cell carcinoma - Xiaoyang Wang; Jianbo Tian; Qianyu Zhao; Nan Yang; Pingting Ying; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Ying Gao; Jiang Chang; Xiaoping Miao (Archives of Toxicology, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Preparation, characterization, and antifungal evaluation of a new type of aminourea chitooligosaccharide derivatives - Jun Zhu; Song Liu; Yukun Qin; Rong’e Xing; Huahua Yu; Xiaolin Chen; Pengcheng Li (Journal of Oceanology and Limnology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Evidence of compliance with and effectiveness of guidelines for noninvasive prenatal testing in China: a retrospective study of 189,809 cases - Chan Tian; Tao Deng; Xiuhuang Zhu; Chen Gong; Yangyu Zhao; Yuan Wei; Rong Li; Xiufeng Xu; Miaonan He; Zhiwei Zhang; Jing Cheng; Mol BenWillem; et al. (Science China Life Sciences, 2020)

Genome-wide identification, characterisation and expression profile analysis of DEAD-box family genes in sweet potato wild ancestor Ipomoea trifida under abiotic stresses - Rong Wan; Jingran Liu; Zhengmei Yang; Panpan Zhu; Qinghe Cao; Tao Xu (Genes & Genomics, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Three functional variants were identified to affect RPS24 expression and significantly associated with risk of colorectal cancer - Danyi Zou; Hongli Zhang; Juntao Ke; Jiaoyuan Li; Ying Zhu; Yajie Gong; Yang Yang; Jianbo Tian; Yi Zhang; Xiating Peng; Kailin Cai; Rong Zhong; et al. (Archives of Toxicology, 2020)

Silicon can improve seed germination and ameliorate oxidative damage of bud seedlings in cucumber under salt stress - Tianyun Gou; Xinhang Chen; Rong Han; Jiaqi Liu; Yongxing Zhu; Haijun Gong (Acta Physiologiae Plantarum, 2020)

Zizania aquatica–duck ecosystem with recycled biogas slurry maintained crop yield - Guiliang Wang; Jianghong Zhang; Xiangming Kou; Shouhong Wang; Jianfeng Liu; Rong Xu; Guangming Han; Leiming Wu; Lingyu Zhu (Nutrient Cycling in Agroecosystems, 2019)

Interaction Between Planetary Boundary Layer and PM2.5 Pollution in Megacities in China: a Review - Yucong Miao; Jing Li; Shiguang Miao; Huizheng Che; Yaqiang Wang; Xiaoye Zhang; Rong Zhu; Shuhua Liu (Current Pollution Reports, 2019)
Purpose of Review During the past decades, the number and size of megacities have been growing dramatically in China. Most of Chinese megacities are suffering from heavy PM 2.5 pollution. In the pollution formation, the planetary boundary layer (PBL) plays an important role. This review is aimed at presenting the current state of understanding of the PBL-PM 2.5 interaction in megacities, as well as to identify the main gaps in current knowledge and further research needs. Recent Findings The PBL is critical to the formation of urban PM 2.5 pollution at multiple temporal scales, ranging from diurnal change to seasonal variation. For the essential PBL structure/process in pollution, the coastal megacities have different concerns from the mountainous or land-locked megacities. In the coastal cities, the recirculation induced by sea-land breeze can accumulate pollutants, whereas in the valley/basin, the blocking effects of terrains can lead to stagnant conditions and thermal inversion. Within a megacity, although the urbanization-induced land use change can cause thermodynamic perturbations and facilitate the development of PBL, the increases in emissions outweigh this impact, resulting in a net increase of aerosol concentration. Moreover, the aerosol radiative effects can modify the PBL by heating the upper layers and reducing the surface heat flux, suppressing the PBL and exacerbating the pollution. Summary This review presented the PBL-PM 2.5 interaction in 13 Chinese megacities with various geographic conditions and elucidated the critical influencing processes. To further understand the complicated interactions, long-term observations of meteorology and aerosol properties with multi-layers in the PBL need to be implemented.

Multi-scale effect of acoustic emission characteristics of 3D rock damage - Wan-rong Liu; Jian-kang Liu; Chun Zhu (Arabian Journal of Geosciences, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Evaluation of Whole Blood Trace Element Levels in Chinese Children with Autism Spectrum Disorder - Ling-ling Wu; Shan-shan Mao; Xu Lin; Rong-wang Yang; Zhi-wei Zhu (Biological Trace Element Research, 2019)

Critical regulation of atherosclerosis by the KCa3.1 channel and the retargeting of this therapeutic target in in-stent neoatherosclerosis - Yan-Rong Zhu; Xiao-Xin Jiang; Dai-Min Zhang (Journal of Molecular Medicine, 2019)

An integrated prevention strategy to address problems associated with continuous cropping of watermelon caused by Fusarium oxysporum - Fu-Yan Liu; Qiang Zhu; Hu-Rong Yang; Jun Zhou; Chuan-Chao Dai; Xing-Xiang Wang (European Journal of Plant Pathology, 2019)

Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China - Hong Zhu; Xian-GUI Yi; Yong-Fu Li; Shu-Xia Zhu; Meng Li; Yi-Fan Duan; Xian-Rong Wang (Systematics and Biodiversity, 2019)

Molecular cloning and functional characterization of a seed-specific VvβVPE gene promoter from Vitis vinifera - Peijie Gong; Rong Wei; Yan Li; Ruipu Wang; Yujin Tang; Ling Wang; Huijun Zhu; Yuejin Wang; Chaohong Zhang (Planta, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Relationship between genetic variation in the α2A-adrenergic receptor and the cardiovascular effects of dexmedetomidine in the Chinese Han population - Shao-jun Zhu; Kui-rong Wang; Xiong-xin Zhang; Sheng-mei Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Pre-colonization of PGPR triggers rhizosphere microbiota succession associated with crop yield enhancement - Yang Zhang; Xu Gao; Zongzhuan Shen; Chengzhi Zhu; Zixuan Jiao; Rong Li; Qirong Shen (Plant and Soil, 2019)

Distinct evolutionary origins of common multi-drug resistance phenotypes in Salmonella typhimurium DT104: a convergent process for adaptation under stress - Le Tang; Song-Ling Zhu; Xin Fang; Yong-Guo Li; Cornelis Poppe; Randal N. Johnston; Gui-Rong Liu; Shu-Lin Liu (Molecular Genetics and Genomics, 2019)

EEG-based mild depression recognition using convolutional neural network - Xiaowei Li; Rong La; Ying Wang; Junhong Niu; Shuai Zeng; Shuting Sun; Jing Zhu (Medical & Biological Engineering & Computing, 2019)

Pericarp and seed of litchi and longan fruits: constituent, extraction, bioactive activity, and potential utilization - Xiang-rong Zhu; Hui Wang; Jian Sun; Bao Yang; Xue-wu Duan; Yue-ming Jiang (Journal of Zhejiang University-SCIENCE B, 2019)

Effects of dietary Sargassum horneri on growth performance, serum biochemical parameters, hepatic antioxidant status, and immune responses of juvenile black sea bream Acanthopagrus schlegelii - Qingchao Shi; Hua Rong; Meilin Hao; Dashi Zhu; Jude Juventus Aweya; Shengkang Li; Xiaobo Wen (Journal of Applied Phycology, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

A special issue to mark the 90th Anniversary of College of Life Sciences, Zhejiang University - Jin-rong Peng; Kun-liang Guan; De-yuan Hong; Xin-hua Lin; Huan-ming Yang; Yu-xian Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

First report of lettuce big-vein associated varicosavirus infecting lettuce in China - Guo-Hua Zheng; Ting Ye; Fu-Rong Liao; Wen-Zhu Zhang; Yan-Lin Ming (Journal of Plant Pathology, 2019)

Aerial scene classification via an ensemble extreme learning machine classifier based on discriminative hybrid convolutional neural networks features - Lihua Ye; Lei Wang; Yaxin Sun; Rong Zhu; Yuanwang Wei (International Journal of Remote Sensing, 2019)

Presurgical localization and spatial shift of resting state networks in patients with brain metastases - Ju-Rong Ding; Fangmei Zhu; Bo Hua; Xingzhong Xiong; Yuqiao Wen; Zhongxiang Ding; Paul M. Thompson (Brain Imaging and Behavior, 2019)

Characteristics of Near Surface Winds over Different Underlying Surfaces in China: Implications for Wind Power Development - Xi Gong; Rong Zhu; Lianshou Chen (Journal of Meteorological Research, 2019)

Quantitative Vulnerability Model of Earth Dam Overtopping and its Application - Chong-Xun Mo; Gui-Yan Mo; Liu Peng; Qing Yang; Xin-Rong Zhu; Qing-Ling Jiang; Ju-Liang Jin (Water Resources Management, 2019)

Temporal and spatial distributions of carbonyl sulfide, dimethyl sulfide, and carbon disulfide in seawater and marine atmosphere of the Changjiang Estuary and its adjacent East China Sea - Rong Zhu; Gui‐Peng Yang; Hong‐Hai Zhang (Limnology and Oceanography, 2019)
Carbonyl sulfide (COS), dimethyl sulfide (DMS), and carbon disulfide (CS 2 ) concentrations were determined in seawater and the overlying atmosphere of the Changjiang Estuary and the adjacent area during two cruises from 22 February 2016 to 15 March 2016 and from 03 July 2016 to 25 July 2016. The concentration ranges of COS, DMS, and CS 2 in seawater during winter were 121–388 pmol L −1 , 0.321–1.59 nmol L −1 , and 10.3–46.8 pmol L −1 , respectively, and those during summer were 98–346 pmol L −1 , 0.397–9.13 nmol L −1 , and 13.3–65.4 pmol L −1 . The DMS concentration in surface seawater varied seasonally, whereas the COS and CS 2 concentrations varied little. The atmospheric mixing ratios of COS, DMS, and CS 2 were 459–777 pptv, 5.2–96.8 pptv, and 96.9–164 pptv during winter and 417–644 pptv, 133–365 pptv, and 15.8–89.8 pptv during summer, respectively. A correlation analysis revealed that COS concentration was related to the concentrations of DMS and CS 2 . The estimated fluxes of COS, DMS, and CS 2 were in the range of 1.19–2.06 μ g m −2 d −1 , 15.11–164.81 μ g m −2 d −1 , and 0.27‐1.32 μ g m −2 d −1 during winter and 0.61–0.97 μ g m −2 d −1 , 71.76–2511 μ g m −2 d −1 , and 0.38–1.47 μ g m −2 d −1 during summer, respectively. These results indicate that the study area is a sink for COS, but served as a source of atmospheric DMS and CS 2 during the study period.

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

Application of Bacillus velezensis NJAU-Z9 Enhanced Plant Growth Associated with Efficient Rhizospheric Colonization Monitored by qPCR with Primers Designed from the Whole Genome Sequence - Yang Zhang; Xu Gao; Shuai Wang; Chengzhi Zhu; Rong Li; Qirong Shen (Current Microbiology, 2018)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Changes in gene and genotype frequencies during the development of the grass carp Ctenopharyngodon idella - LiB. He; Lv Xiong; AiD. Zhang; YongM. Li; Rong Huang; LanJ. Liao; ZuoY. Zhu; YaP. Wang (Journal of Fish Biology, 2018)
In this study, a full‐sib population of Ctenopharyngodon idella was constructed and approximately 500 C. idella individuals were sampled at four early developmental stages (hatching, first feeding, juvenile fish and young fish). Four DNA pools were constructed and subjected to next‐generation sequencing. On the basis of the identification of single nucleotide polymorphisms (SNP), changes in gene and genotype frequencies during the developmental progress of C. idella were revealed, which indicates that death during the early developmental stage is not a random process. These findings will establish the basis for further studies performed for identifying superior alleles or genotypes as target markers for molecular breeding.

Plant-mediated competition facilitates a phoretic association between a gall mite and a psyllid vector - Jianling Li; Sai Liu; Kun Guo; Fan Zhang; Haili Qiao; Jianmin Chen; Mengke Yang; Xiu Zhu; Rong Xu; Changqing Xu; Jun Chen (Experimental and Applied Acarology, 2018)

Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island - Sai-Jun Sun; Li-Peng Zhang; Rong-Qing Zhang; Xing Ding; Hong-Li Zhu; Zhao-Feng Zhang; Wei-Dong Sun (International Geology Review, 2018)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

Scaling wind stirring effects in an oceanic bulk mixed layer model with application to an OGCM of the tropical Pacific - Yuchao Zhu; Rong-Hua Zhang (Climate Dynamics, 2018)

Upper Paleozoic Marine Shale Characteristics and Exploration Prospects in the Northwestern Guizhong Depression, South China - Zhenhong Zhu; Genshun Yao; Zhanghua Lou; Aimin Jin; Rong Zhu; Chong Jin; Chao Chen (Journal of Ocean University of China, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

The influence of the carotid baroreflex on dynamic regulation of cerebral blood flow and cerebral tissue oxygenation in humans at rest and during exercise - Sushmita Purkayastha; Kaitlyn Maffuid; Xiaojie Zhu; Rong Zhang; Peter B. Raven (European Journal of Applied Physiology, 2018)

Anti-oral common pathogenic bacterial active acetylenic acids from Thesium chinense Turcz - Chang Liu; Xiao-Tian Li; Rong-Rong Cheng; Zhu-Zhen Han; Li Yang; Zhong-Chen Song; Zheng-Tao Wang (Journal of Natural Medicines, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Design, synthesis and biological evaluation of phenylpicolinamide sorafenib derivatives as antitumor agents - Chunjiang Wu; Shan Xu; Yuping Guo; Jielian Wu; Rong Luo; Wenhui Wang; Yuanbiao Tu; Le Chen; Wufu Zhu; Pengwu Zheng (Medicinal Chemistry Research, 2018)

Atmospheric environmental capacity and urban atmospheric load in mainland China - DaHai Xu; Yu Wang; Rong Zhu (Science China Earth Sciences, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Use the predictive models to explore the key factors affecting phytoplankton succession in Lake Erhai, China - Rong Zhu; Huan Wang; Jun Chen; Hong Shen; Xuwei Deng (Environmental Science and Pollution Research, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Characterization and Cu sorption properties of humic acid from the decomposition of rice straw - Yongbo Qi; Jun Zhu; Qingling Fu; Hongqing Hu; Xingmin Rong; Qiaoyun Huang (Environmental Science and Pollution Research, 2017)

Asymmetric evolution of El Niño and La Niña: the recharge/discharge processes and role of the off-equatorial sea surface height anomaly - Zeng-Zhen Hu; Arun Kumar; Bohua Huang; Jieshun Zhu; Rong-Hua Zhang; Fei-Fei Jin (Climate Dynamics, 2017)

Erratum to: The Extent of Heavy Metal Pollution and Their Potential Health Risk in Topsoils of the Massively Urbanized District of Shanghai - Syed Taseer Abbas Jaffar; Fan Luo; Rong Ye; Hassan Younas; Xue-feng Hu; Long-zhu Chen (Archives of Environmental Contamination and Toxicology, 2017)

The Extent of Heavy Metal Pollution and Their Potential Health Risk in Topsoils of the Massively Urbanized District of Shanghai - Syed Taseer Abbas Jaffar; Fan Luo; Rong Ye; Hassan Younas; Xue-feng Hu; Long-zhu Chen (Archives of Environmental Contamination and Toxicology, 2017)

Geochronology and geochemistry of volcanic rocks in the Arbasay Formation, Xinjiang Province (Northwest China): implications for the tectonic evolution of the North Tianshan - Jialin Wang; Chaodong Wu; Zhuang Li; Wen Zhu; Yiwen Chen; Qingyun Li; Jun Wu; Langjiang Deng; Rong Chen (International Geology Review, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Effect of Co-overexpression of Nisin Key Genes on Nisin Production Improvement in Lactococcus lactis LS01 - Zhi-Jian Ni; Xiao-yuan Zhang; Fei Liu; Miao Wang; Rong-hua Hao; Pei-xue Ling; Xi-Qiang Zhu (Probiotics and Antimicrobial Proteins, 2017)

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

Characterizing land displacement in complex hydrogeological and geological settings: a case study in the Beijing Plain, China - Yongyong Li; Huili Gong; Lin Zhu; Xiaojuan Li; Rong Wang; Gaoxuan Guo (Natural Hazards, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Regional ecological security and diagnosis of obstacle factors in underdeveloped regions: a case study in Yunnan Province, China - Zhao-rong Ou; Qing-ke Zhu; Yong-yu Sun (Journal of Mountain Science, 2017)

Microglia activation contributes to quinolinic acid-induced neuronal excitotoxicity through TNF-α - Wei Feng; Yan Wang; Zi-Qi Liu; Xuan Zhang; Rong Han; You-Zhu Miao; Zheng-Hong Qin (Apoptosis, 2017)

Eudragit S100-Coated Chitosan Nanoparticles Co-loading Tat for Enhanced Oral Colon Absorption of Insulin - Shuangxi Chen; Feng Guo; Tiantian Deng; Siqi Zhu; Wenyu Liu; Haijun Zhong; Hua Yu; Rong Luo; Zeyuan Deng (AAPS PharmSciTech, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Chlorophyll fluorescence lifetime imaging provides new insight into the chlorosis induced by plant virus infection - Rong Lei; Hongshan Jiang; Fan Hu; Jin Yan; Shuifang Zhu (Plant Cell Reports, 2017)

Benzimidazole derivative M084 extends the lifespan of Caenorhabditis elegans in a DAF-16/FOXO-dependent way - Ai-Jun Ding; Gui-Sheng Wu; Bin Tang; Xuechuan Hong; Michael X. Zhu; Huai-Rong Luo (Molecular and Cellular Biochemistry, 2017)

Molecular characterization of HOXC8 gene and methylation status analysis of its exon 1 associated with the length of cashmere fiber in Liaoning cashmere goat - Wen L. Bai; Jiao J. Wang; Rong H. Yin; Yun L. Dang; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang; Hui L. Xue (Genetica, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Performance improvement of raw water pretreatment process with pre-inoculation biofilm: feasibility and limiting factors - Guang-feng Yang; Li-juan Feng; Cai-rong Guo; Tian Xia; Xiang-yang Xu; Liang Zhu (Biodegradation, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Antioxidant and hyaluronidase inhibitory activities of diverse phenolics in Phyllanthus emblica - Min Xu; Hong-Tao Zhu; Rong-Rong Cheng; Dong Wang; Chong-Ren Yang; Takashi Tanaka; Isao Kouno; Ying-Jun Zhang (Natural Product Research, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

MiR-449a regulates autophagy to inhibit silica-induced pulmonary fibrosis through targeting Bcl2 - Ruhui Han; Xiaoming Ji; Rong Rong; Yan Li; Wenxi Yao; Jiali Yuan; Qiuyun Wu; Jingjin Yang; Weiwen Yan; Lei Han; Baoli Zhu; Chunhui Ni (Journal of Molecular Medicine, 2016)

Cloning and characterization of Bax1 and Bax2 genes of Ctenopharyngodon idellus and evaluation of transcript expression in response to grass carp reovirus infection - Hao Wang; Libo He; Yongyan Pei; Pengfei Chu; Rong Huang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Fish Physiology and Biochemistry, 2016)

Erratum to: The intracellular carboxyl tail of the PAR-2 receptor controls intracellular signaling and cell death - Zhihui Zhu; Rolf Stricker; Rong yu Li; Gregor Zündorf; Georg Reiser (Cell and Tissue Research, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Molecular characterization, expression and methylation status analysis of BMP4 gene in skin tissue of Liaoning cashmere goat during hair follicle cycle - Wen L. Bai; Yun L. Dang; Jiao J. Wang; Rong H. Yin; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Hui L. Xue; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang (Genetica, 2016)

Pseudomonas syringae pv. Actinidiae isolated from non-kiwifruit plant species in China - Pu Liu; Shizhou Xue; Rong He; Jiayong Hu; Xiaojie Wang; Bing Jia; Lorenzo Gallipoli; Angelo Mazzaglia; Giorgio M. Balestra; Liwu Zhu (European Journal of Plant Pathology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Composition of phosphorus in wetland soils determined by SMT and solution 31P-NMR analyses - Wenqiang Zhang; Xin Jin; Yuekui Ding; Xiaolei Zhu; Nan Rong; Jie Li; Baoqing Shan (Environmental Science and Pollution Research, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

Comparison of skeletal muscle miRNA and mRNA profiles among three pig breeds - Xinhua Hou; Yalan Yang; Shiyun Zhu; Chaoju Hua; Rong Zhou; Yulian Mu; Zhonglin Tang; Kui Li (Molecular Genetics and Genomics, 2016)

Evaluation of a water-soluble adjuvant for the development of monoclonal antibodies against small-molecule compounds - Rui Liu; Ying Liu; Mei-jing Lan; Niusha Taheri; Jing-li Cheng; Yi-rong Guo; Guo-nian Zhu (Journal of Zhejiang University-SCIENCE B, 2016)

Epigenetic mechanisms of salt tolerance and heterosis in Upland cotton (Gossypium hirsutum L.) revealed by methylation-sensitive amplified polymorphism analysis - Baohua Wang; Mi Zhang; Rong Fu; Xiaowei Qian; Ping Rong; Yan Zhang; Peng Jiang; Junjuan Wang; Xuke Lu; Delong Wang; Wuwei Ye; Xinyu Zhu (Euphytica, 2016)

Phosphorus speciation of sediments from lakes of different tropic status in Eastern China - Wenqiang Zhang; Nan Rong; Xin Jin; Jie Li; Yuekui Ding; Xiaolei Zhu; Baoqing Shan (Environmental Science and Pollution Research, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Distributions, fluxes, and toxicities of heavy metals in sediment pore water from tributaries of the Ziya River system, northern China - Xiaolei Zhu; Baoqing Shan; Wenzhong Tang; Shanshan Li; Nan Rong (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Downregulation of ubiquitin-specific protease 14 (USP14) inhibits breast cancer cell proliferation and metastasis, but promotes apoptosis - Lianxin Zhu; Shuyun Yang; Song He; Fulin Qiang; Jing Cai; Rong Liu; Changjiang Gu; Zengya Guo; Chen Wang; Wei Zhang; Chunhui Zhang; Yingying Wang (Journal of Molecular Histology, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

EGCG induces G-CSF expression and neutrophilia in experimental sepsis - Wei Li; Andrew H. Wu; Shu Zhu; Jianhua Li; Rong Wu; John D’Angelo; Haichao Wang (Immunologic Research, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Dysfunction of autophagy as the pathological mechanism of motor neuron disease based on a patient-specific disease model - Dan-Jing Yang; Liang Zhu; Jie Ren; Rong-Jie Ma; Hongwen Zhu; Jun Xu (Neuroscience Bulletin, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

Analysis of methylation-sensitive amplified polymorphism in different cotton accessions under salt stress based on capillary electrophoresis - Baohua Wang; Rong Fu; Mi Zhang; Zhenqian Ding; Lei Chang; Xinyu Zhu; Yafeng Wang; Baoxiang Fan; Wuwei Ye; Youlu Yuan (Genes & Genomics, 2015)

High immune activation and abnormal expression of cytokines contribute to death of SHIV89.6-infected Chinese rhesus macaques - Ren-Rong Tian; Ming-Xu Zhang; Lin-Tao Zhang; Xiao-Liang Zhang; Hong-Yi Zheng; Lin Zhu; Wei Pang; Gao-Hong Zhang; Yong-Tang Zheng (Archives of Virology, 2015)

Inversion of vegetation height from PolInSAR using complex least squares adjustment method - HaiQiang Fu; ChangCheng Wang; JianJun Zhu; QingHua Xie; Rong Zhao (Science China Earth Sciences, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Immunosuppressive Effect of Hypodermin C on Complement Component 3 In Vitro - An-Kang Hu; Ren-Jin Chen; Xiao-Rong Zhu; Jian-Hong Gu; Zong-Ping Liu (Cell Biochemistry and Biophysics, 2015)

Effects of Plant Stress Signal Molecules on the Production of Wilforgine in an Endophytic Actinomycete Isolated from Tripterygium wilfordii Hook.f. - Guo-peng Miao; Chuan-shu Zhu; Jun-tao Feng; Li-rong Han; Xing Zhang (Current Microbiology, 2015)

The intracellular carboxyl tail of the PAR-2 receptor controls intracellular signaling and cell death - Zhihui Zhu; Rolf Stricker; Rong yu Li; Gregor Zündorf; Georg Reiser (Cell and Tissue Research, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Rainfall and tillage impacts on soil erosion of sloping cropland with subtropical monsoon climate — A case study in hilly purple soil area, China - Jia-liang Tang; Xun-qiang Cheng; Bo Zhu; Mei-rong Gao; Tao Wang; Xi-feng Zhang; Pei Zhao; Xiang You (Journal of Mountain Science, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Litter mass loss and nutrient dynamics of four emergent macrophytes during aerial decomposition in freshwater marshes of the Sanjiang plain, Northeast China - Xinhou Zhang; Changchun Song; Rong Mao; Guisheng Yang; Baoxian Tao; Fuxi Shi; Xiaoyan Zhu; Aixin Hou (Plant and Soil, 2014)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Calreticulin is localized at mitochondria of rat cardiomyocytes and affected by furazolidone - Hu Shan; Jin Wei; Ming Zhang; Lin Lin; Rui Yan; Yanhe Zhu; Rong Zhang (Molecular and Cellular Biochemistry, 2014)

An improved SCGM(1,m) model for multi-point deformation analysis - Qi-jie Wang; Chang-cheng Wang; Rong-an Xie; Xin-qing Zhang; Jian-jun Zhu (Geosciences Journal, 2014)

Isolation and characterization of 10 polymorphic microsatellite loci from the Chinese ratsnake (Zaocys dhumnades) - Rong-Fang Wang; Chao-Nan Zhu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

TNF-α, IL-6, and Leptin Increase the Expression of miR-378, an Adipogenesis-Related microRNA in Human Adipocytes - Lu-lian Xu; Chun-mei Shi; Guang-feng Xu; Ling Chen; Ling-ling Zhu; Lu Zhu; Xi-rong Guo; Mei-yu Xu; Chen-bo Ji (Cell Biochemistry and Biophysics, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Inverse associations of outdoor activity and vitamin D intake with the risk of Parkinson’s disease - Dan Zhu; Gui-you Liu; Zheng Lv; Shi-rong Wen; Sheng Bi; Wei-zhi Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Comparison of the replication characteristics of vaccinia virus strains Guang 9 and Tian Tan in vivo and in vitro - Rong Zhu; Qiang Liu; Weijin Huang; Yongxin Yu; Youchun Wang (Archives of Virology, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Systemic Evaluation of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Ai-Hua Zhu; Yan-Rong Hu; Wei Liu; Feng Gao; Jian-Xin Li; Li-Hui Zhao; Gang Chen (Cell Biochemistry and Biophysics, 2014)

Distribution and geochemical characteristics of fluids in Ordovician marine carbonate reservoirs of the Tahe Oilfield - Mei Li; Zhanghua Lou; Rong Zhu; Aimin Jin; Ying Ye (Journal of Earth Science, 2014)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

High-level soluble expression of the hemA gene from Rhodobacter capsulatus and comparative study of its enzymatic properties - Jia-wei Lou; Li Zhu; Mian-bin Wu; Li-rong Yang; Jian-ping Lin; Pei-lin Cen (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of interannual salinity variability on the barrier layer in the western-central equatorial Pacific: A diagnostic analysis from Argo - Fei Zheng; Rong-Hua Zhang; Jiang Zhu (Advances in Atmospheric Sciences, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

MiR-335, an Adipogenesis-Related MicroRNA, is Involved in Adipose Tissue Inflammation - Lu Zhu; Ling Chen; Chun-Mei Shi; Guang-Feng Xu; Lu-Lian Xu; Ling-Ling Zhu; Xi-Rong Guo; Yuhui Ni; Yan Cui; Chenbo Ji (Cell Biochemistry and Biophysics, 2014)

Paludibacter jiangxiensis sp. nov., a strictly anaerobic, propionate-producing bacterium isolated from rice paddy field - Yan-Ling Qiu; Xiao-Zhu Kuang; Xiao-Shuang Shi; Xian-Zheng Yuan; Rong-Bo Guo (Archives of Microbiology, 2014)

Environmental Investigations and Molecular Typing of Aspergillus in a Chinese Hospital - Jun-hong Ao; Zhen-feng Hao; He Zhu; liang Wen; Rong-ya Yang (Mycopathologia, 2014)

The newly established human liver cell line: a potential cell source for the bioartificial liver in the future - Hongling Liu; Shaoli You; Yihui Rong; Yichen Wu; Bing Zhu; Zhihong Wan; Wanshu Liu; Panyong Mao; Shaojie Xin (Human Cell, 2013)

Aneuploidy and chromosomal instability: a vicious cycle driving cellular evolution and cancer genome chaos - Tamara A. Potapova; Jin Zhu; Rong Li (Cancer and Metastasis Reviews, 2013)

Overexpression of the AtSTK gene increases salt, PEG and ABA tolerance in Arabidopsis - Lei Bing; Cui-Cui Feng; Jing-Lan Li; Xiao-Xu Li; Bao-Cun Zhao; Yin-Zhu Shen; Zhan-Jing Huang; Rong-Chao Ge (Journal of Plant Biology, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Are habitat fragmentation, local adaptation and isolation‐by‐distance driving population divergence in wild rice O ryza rufipogon ? - Yao Zhao; Klaas Vrieling; Hui Liao; Manqiu Xiao; Yongqing Zhu; Jun Rong; Wenju Zhang; Yuguo Wang; Ji Yang; Jiakuan Chen; Zhiping Song (Molecular Ecology, 2013)
Habitat fragmentation weakens the connection between populations and is accompanied with isolation by distance ( IBD ) and local adaptation (isolation by adaptation, IBA ), both leading to genetic divergence between populations. To understand the evolutionary potential of a population and to formulate proper conservation strategies, information on the roles of IBD and IBA in driving population divergence is critical. The putative ancestor of A sian cultivated rice ( O ryza sativa ) is endangered in C hina due to habitat loss and fragmentation. We investigated the genetic variation in 11 C hinese O ryza rufipogon populations using 79 microsatellite loci to infer the effects of habitat fragmentation, IBD and IBA on genetic structure. Historical and current gene flows were found to be rare ( m h = 0.0002–0.0013, m c = 0.007–0.029), indicating IBD and resulting in a high level of population divergence ( F ST = 0.343). High within‐population genetic variation ( H E = 0.377–0.515), relatively large effective population sizes ( N e = 96–158), absence of bottlenecks and limited gene flow were found, demonstrating little impact of recent habitat fragmentation on these populations. Eleven gene‐linked microsatellite loci were identified as outliers, indicating local adaptation. Hierarchical AMOVA and partial M antel tests indicated that population divergence of C hinese O . rufipogon was significantly correlated with environmental factors, especially habitat temperature. Common garden trials detected a significant adaptive population divergence associated with latitude. Collectively, these findings imply that IBD due to historical rather than recent fragmentation, followed by local adaptation, has driven population divergence in O . rufipogon .

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Genome-Wide Phylogenetic Analysis of Stress-Activated Protein Kinase Genes in Rice (OsSAPKs) and Expression Profiling in Response to Xanthomonas oryzae pv. oryzicola Infection - Mei-Rong Xu; Li-Yu Huang; Fan Zhang; Ling-Hua Zhu; Yong-Li Zhou; Zhi-Kang Li (Plant Molecular Biology Reporter, 2013)

A new species of Scolecobasidium associated with the sooty blotch and flyspeck complex on banana from China - Lu Hao; Chen Chen; Rong Zhang; Mingqi Zhu; Guangyu Sun; Mark L. Gleason (Mycological Progress, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Exome Sequencing Identified NRG3 as a Novel Susceptible Gene of Hirschsprung’s Disease in a Chinese Population - Jun Yang; Shengyu Duan; Rong Zhong; Jieyun Yin; Jiarui Pu; Juntao Ke; Xuzai Lu; Li Zou; Hongmei Zhang; Zhidong Zhu; Depeng Wang; Huasheng Xiao; et al. (Molecular Neurobiology, 2013)

Induction of annexin by heavy metals and jasmonic acid in Zea mays - Mei-Liang Zhou; Xiong-Bang Yang; Qian Zhang; Ming Zhou; En-Ze Zhao; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Nicotianamine synthase gene family as central components in heavy metal and phytohormone response in maize - Mei-Liang Zhou; Lei-Peng Qi; Jun-Feng Pang; Qian Zhang; Zhi Lei; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Halomonas nanhaiensis sp. nov., a halophilic bacterium isolated from a sediment sample from the South China Sea - Mei-Rong Long; Dao-Feng Zhang; Xin-Yi Yang; Xiao-Mei Zhang; Yong-Guang Zhang; Yuan-Ming Zhang; Honghui Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Decreased PADI4 mRNA Association with Global Hypomethylation in Hepatocellular Carcinoma During HBV Exposure - Changsong Zhang; Lieying Fan; Tingting Fan; Dong Wu; Lu Gao; Yang Ling; Jing Zhu; Rong Li; Lixin Wei (Cell Biochemistry and Biophysics, 2013)

Meta-analysis of the Association Between DCDC2 Polymorphisms and Risk of Dyslexia - Rong Zhong; Beifang Yang; Hui Tang; Li Zou; Ranran Song; Ling-Qiang Zhu; Xiaoping Miao (Molecular Neurobiology, 2013)

The Neuroprotective Effect of Overexpression of Calbindin-D28k in an Animal Model of Parkinson’s Disease - Hong-Hua Yuan; Ren-Jin Chen; Yu-Hua Zhu; Chang-Ling Peng; Xiao-Rong Zhu (Molecular Neurobiology, 2013)

Improving ENSO prediction in a hybrid coupled model with an embedded entrainment temperature parameterisation - Jieshun Zhu; Guang‐Qing Zhou; Rong‐Hua Zhang; Zhaobo Sun (International Journal of Climatology, 2013)
Improving El Niño/Southern Oscillation (ENSO) forecast remains a great challenge in the climate‐predicting community. Previously, an improved solution to sea surface temperature (SST) anomaly simulations in the tropical Pacific was obtained by explicitly embedding into an ocean general circulation model (OGCM) a separate SST anomaly submodel with an empirical parameterisation for the temperature of subsurface water entrained into the ocean mixed layer ( T e ). In the present work, the benefit of the approach is explored and demonstrated in terms of ENSO prediction. A hybrid coupled ocean‐atmosphere model (HCM) is utilized to perform two retrospective ENSO forecasts, differing in the way SST anomaly fields are taken for their coupling to the atmosphere, one directly from the OGCM (referred to as a standard coupling, HCM std ), and another from the embedded SST anomaly submodel with optimized T e parameterisation (referred to as an embedded coupling, HCM embed ). The results indicate that ENSO forecasts can be effectively improved using the embedded approach; the predicted Niño‐3.4 SST anomaly correlation is higher by 0.1–0.2 at a 12‐month lead time in the HCM embed than in the HCM std , and the corresponding root‐mean‐square (RMS) error is lower by 0.1–0.2 °C. Further improvements and applications are discussed. Copyright © 2012 Royal Meteorological Society

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Cathepsin L in the orange-spotted grouper, Epinephelus coioides: molecular cloning and gene expression after a Vibrio anguillarum challenge - Jing-Zhen Liang; Ying-Zhu Rao; Zhao-Rong Lun; Ting-Bao Yang (Fish Physiology and Biochemistry, 2012)

Mapping of quantitative trait loci for oil content in cottonseed kernel - QUAMPAH ALFRED†; HAI YING LIU†; HAI MING XU; JIN RONG LI; JIAN GUO WU; SHUI JIN ZHU; CHUN HAI SHI (Journal of Genetics, 2012)

Aldehyde dehydrogenase protein superfamily in maize - Mei-Liang Zhou; Qian Zhang; Ming Zhou; Lei-Peng Qi; Xiong-Bang Yang; Kai-Xuan Zhang; Jun-Feng Pang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Functional & Integrative Genomics, 2012)

Cloning and characterization of a thermostable carboxylesterase from inshore hot spring thermophile Geobacillus sp. ZH1 - Yanbing Zhu; Guangming Liu; Hebin Li; Jingwen Liu; Xiaoming Bai; Rong Guan; Huinong Cai (Acta Oceanologica Sinica, 2012)

Determination of the geographical origin of Chinese teas based on stable carbon and nitrogen isotope ratios - Long Zhang; Jia-rong Pan; Cheng Zhu (Journal of Zhejiang University-SCIENCE B, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Modulation of El Niño-Southern Oscillation by freshwater flux and salinity variability in the tropical Pacific - Rong-Hua Zhang; Fei Zheng; Jieshun Zhu; Yuhua Pei; Quanan Zheng; Zhanggui Wang (Advances in Atmospheric Sciences, 2012)

Bivariate genome-wide association study suggests that the DARC gene influences lean body mass and age at menarche - Rong Hai; Lei Zhang; YuFang Pei; LanJuan Zhao; Shu Ran; YingYing Han; XueZhen Zhu; Hui Shen; Qing Tian; HongWen Deng (Science China Life Sciences, 2012)

Interactions between CYP1A1 polymorphisms and cigarette smoking are associated with the risk of hepatocellular carcinoma: evidence from epidemiological studies - Lei Yu; Lei Sun; Yang-Fang Jiang; Bao-Ling Lu; De-Rong Sun; Li-Ying Zhu (Molecular Biology Reports, 2012)

Study on the effect of IRE1α on cell growth and apoptosis via modulation PLK1 in ER stress response - Xiangzhu Li; Huifang Zhu; Huizhe Huang; Rong Jiang; Wenjun Zhao; Yanna Liu; Jinghua Zhou; Feng-Jin Guo (Molecular and Cellular Biochemistry, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Genetic diversity of four new species related to southwestern Sichuan buckwheats as revealed by karyotype, ISSR and allozyme characterization - Mei-Liang Zhou; Da-Quan Bai; Yu Tang; Xue-Mei Zhu; Ji-Rong Shao (Plant Systematics and Evolution, 2012)

Characterization of the expression profile of calpain-3 (CAPN3) gene in chicken - Zeng-Rong Zhang; Qing Zhu; Yong-Gang Yao; Xiao-Song Jiang; Hua-Rui Du; Yi-Ping Liu (Molecular Biology Reports, 2012)

Genetic Overlap in the Quantitative Resistance of Rice at the Seedling and Adult Stages to Xanthomonas oryzae pv. oryzae - Yong-Li Zhou; Xue-Wen Xie; Mei-Rong Xu; Jin-Ping Zang; Ling-Hua Zhu; Jian-Long Xu; Zhi-Kang Li (Journal of Plant Biology, 2012)

HIV-infection resistance in PMBC-derived dendritic cells modified with recombinant virus - Cheng-lai Xia; Ping Zhu; Yan-tao Cai; Guang-bin Zhu; Zheng-rong Mei; Hanhui Huang; Di-xian Luo; Peng-ke Yan (Archives of Virology, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Imprinting analysis of porcine MAGEL2 gene in two fetal stages and association analysis with carcass traits - Ling Guo; Mu Qiao; Chao Wang; Rong Zheng; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2012)

Induced pluripotent stem cell-related genes influence biological behavior and 5-fluorouracil sensitivity of colorectal cancer cells - Zhong Shi; Rui Bai; Zhi-xuan Fu; Yong-liang Zhu; Rong-fu Wang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

The mediating and moderating role of personal strain and coping resource in the relationship between work stressor and quality of life among Chinese nurses - Si-Ying Wu; Huang-Yuan Li; Shu-Juan Yang; Wei Zhu; Xiao-Rong Wang (International Archives of Occupational and Environmental Health, 2012)

Cordyceps cicadae extracts ameliorate renal malfunction in a remnant kidney model - Rong Zhu; Yi-ping Chen; Yue-yi Deng; Rong Zheng; Yi-fei Zhong; Lin Wang; Lan-ping Du (Journal of Zhejiang University-SCIENCE B, 2011)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Granaticins and their biosynthetic gene cluster from Streptomyces vietnamensis: evidence of horizontal gene transfer - Ming-Rong Deng; Jun Guo; Xiang Li; Chun-Hua Zhu; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2011)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Single cysteine substitution in Bacillus thuringiensis Cry7Ba1 improves the crystal solubility and produces toxicity to Plutella xylostella larvae - Donghai Peng; Fenshan Wang; Nisha Li; Zhenyu Zhang; Rong Song; Zimin Zhu; Lifang Ruan; Ming Sun (Environmental Microbiology, 2011)
Summary Many Bacillus thuringiensis isolates have no demonstrated toxicity against insects. In this study, a novel holotype crystal protein gene cry7Ba1 was isolated from a ‘non‐insecticidal’ B. thuringiensis strain YBT‐978. The Cry7Ba1 protein showed high toxicity against Plutella xylostella larvae after the crystals were dissolved at pH 12.5, suggesting that the ‘non‐insecticidal’ properties of this protein were due to insolubility in the normal insect midgut pH environment. After the C‐terminal half of Cry7Ba1 was replaced by that of Cry1Ac or Cry1C proteins, the recombinant protein inclusions could be dissolved at pH 9.5, and exhibited high toxicity against P. xylostella larvae. This result proved the insolubility of Cry7Ba1 crystal was determined by the structure of its C‐terminal half. Further, six mutations were constructed by substituting cysteine residues with serine. Solubility studies showed that the crystals from mutants C697S, C834S and C854S could be dissolved at lower pH (10.5, 9.5 and 11.5 respectively). Bioassays showed that crystals from mutant C834S were toxic to P. xylostella larvae. Our discoveries suggest that a single cysteine residue located in the C‐terminal half of the protein determines the solubility and toxicity of some nontoxic crystal proteins. This study provides a strategy to isolate novel insecticidal crystal protein genes from ‘non‐insecticidal’ B. thuringiensis strains.

Fluorescence in situ hybridization on plant extended chromatin DNA fibers for single-copy and repetitive DNA sequences - Kun Yang; Hecui Zhang; Richard Converse; Yong Wang; Xiaoying Rong; Zhigang Wu; Bing Luo; Liyan Xue; Li Jian; Liquan Zhu; Xiaojia Wang (Plant Cell Reports, 2011)

The Electrostatic Interactions Between Nano-TiO2 and Trypsin Inhibit the Enzyme Activity and Change the Secondary Structure of Trypsin - Wen-Rui Wang; Rong-Rong Zhu; Rong Xiao; Hui Liu; Shi-Long Wang (Biological Trace Element Research, 2011)

Molecular characterization and expression patterns of Lbx1 in porcine skeletal muscle - Zhe Chao; Jian Wu; Rong Zheng; Feng-E. Li; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2011)

The complete mitochondrial genome of Spilonota lechriaspis Meyrick (Lepidoptera: Tortricidae) - Jin-Liang Zhao; Yan-Yan Zhang; A-Rong Luo; Guo-Fang Jiang; Stephen L. Cameron; Chao-Dong Zhu (Molecular Biology Reports, 2011)

Molecular phylogenetic reconstruction of Osmanthus Lour. (Oleaceae) and related genera based on three chloroplast intergenic spacers - Shi-Quan Guo; Min Xiong; Chun-Feng Ji; Zhi-Rong Zhang; De-Zhu Li; Zhi-Yong Zhang (Plant Systematics and Evolution, 2011)

Predominance of Precipitation and Temperature Controls on Ecosystem CO2 Exchange in Zoige Alpine Wetlands of Southwest China - Yan Bin Hao; Xiao Yong Cui; Yan Fen Wang; Xu Rong Mei; Xiao Ming Kang; Ning Wu; Peng Luo; Dan Zhu (Wetlands, 2011)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

Knockdown of ribonuclease inhibitor expression with siRNA in non-invasive bladder cancer cell line BIU-87 promotes growth and metastasis potentials - Junxia Chen; Xi Ou-Yang; Juan Gao; Jun Zhu; Xiaoyan He; Jiang Rong (Molecular and Cellular Biochemistry, 2011)

Modelling temporal and spatial changes of PCBs in fish tissue from Lake Huron - Abdel H. El-Shaarawi; Sean Backus; Rong Zhu; Yalin Chen (Environmental Monitoring and Assessment, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Gene expression profiles of adipose tissue of high-fat diet-induced obese rats by cDNA microarrays - Jie Qiu; Rui Cheng; Xiao-yu Zhou; Jin-gai Zhu; Chun Zhu; Da-ni Qin; Chun-zhao Kou; Xi-rong Guo (Molecular Biology Reports, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Tissue-specific distribution of uncoupling proteins in normal rats and rats with high-fat-diet-induced obesity - Chun-Mei Zhang; Ying Gu; Da-ni Qing; Jin-gai Zhu; Chun Zhu; Min Zhang; Xi-Rong Guo (Molecular Biology Reports, 2010)

The effects of ox-LDL in human atherosclerosis may be mediated in part via the toll-like receptor 4 pathway - Honglian Geng; Aihua Wang; Guanghua Rong; Bei Zhu; Yan Deng; Jun Chen; Renqian Zhong (Molecular and Cellular Biochemistry, 2010)

Wound repair and anti-oxidative capacity is regulated by ITGB4 in airway epithelial cells - Chi Liu; Hui-jun Liu; Yang Xiang; Yu-rong Tan; Xiao-lin Zhu; Xiao-qun Qin (Molecular and Cellular Biochemistry, 2010)

cDNA cloning and expression of ghrelin in giant panda (Ailuropoda melanoleuca) - Qinggang Xu; Hongwu Bian; Ning Han; Rong Hou; Zhihe Zhang; Muyuan Zhu (Molecular Biology Reports, 2010)

Phenotypic and Genetic Characteristics of Macrolide and Lincosamide Resistant Ureaplasma urealyticum Isolated in Guangzhou, China - Chun Lu; Ting lu Ye; Guo xing Zhu; Pei ying Feng; Han Ma; Rong biao Lu; Wei Lai (Current Microbiology, 2010)

Sequencing and Utilization of the Gossypium Genomes - Andrew H. Paterson; Jun-kang Rong; Alan R. Gingle; Peng W. Chee; Elizabeth S. Dennis; Danny Llewellyn; Leon S. Dure; Candace Haigler; Gerald O. Myers; Daniel G. Peterson; Mehboob ur Rahman; Yusuf Zafar; et al. (Tropical Plant Biology, 2010)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

A new species of Zygophiala associated with the flyspeck complex on apple from China - Yongqiang Ma; Rong Zhang; Guangyu Sun; Haixia Zhu; Ming Tang; Jean C. Batzer; Mark L. Gleason (Mycological Progress, 2010)

Molecular characterization, expression profile and association analysis with fat deposition traits of the porcine APOM gene - Gang Pan; Yayuan Fu; Bo Zuo; Zhuqing Ren; Dequan Xu; Minggang Lei; Rong Zheng; Yuan-Zhu Xiong (Molecular Biology Reports, 2010)

Immunosuppressive effects of mesenchymal stem cells in collagen-induced mouse arthritis - Fei Mao; Wen-Rong Xu; Hui Qian; Wei Zhu; Yong-Min Yan; Qi-Xiang Shao; Hua-Xi Xu (Inflammation Research, 2010)

Over-expression of ThpI from Choristoneura fumiferana enhances tolerance to cold in Arabidopsis - Bo Zhu; Ai-Sheng Xiong; Ri-He Peng; Jing Xu; Xiao-Fen Jin; Xiu-Rong Meng; Quan-Hong Yao (Molecular Biology Reports, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

Liquid-based cytology aids in primary fallopian tube cancer diagnosis - Zhuo Ren; Yun-ping Zhang; Hui-xia Yang; Li-rong Zhu (Journal of Zhejiang University-SCIENCE B, 2009)

Laboratory Characterization of Permeability and Its Anisotropy of Chelungpu Fault Rocks - Tzu-Mo N. Chen; Wenlu Zhu; Teng-fong Wong; Sheng-Rong Song (Pure and Applied Geophysics, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wen-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wun-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Ensemble hindcasts of ENSO events over the past 120 years using a large number of ensembles - Fei Zheng; Jiang Zhu; Hui Wang; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2009)

Cistanche deserticola Ma cultivated as a new crop in China - Rong Xu; Jun Chen; Shi-Lin Chen; Tong-Ning Liu; Wei-Cheng Zhu; Jiang Xu (Genetic Resources and Crop Evolution, 2009)

Cloning and functional analysis of wheat V-H+-ATPase subunit genes - Qian Zhao; Yan-Jun Zhao; Bao-Cun Zhao; Rong-Chao Ge; Ming Li; Yin-Zhu Shen; Zhan-Jing Huang (Plant Molecular Biology, 2009)

15-HETE suppresses K+ channel activity and inhibits apoptosis in pulmonary artery smooth muscle cells - Yumei Li; Qian Li; Zhigang Wang; Di Liang; Shujun Liang; Xiaobo Tang; Lei Guo; Rong Zhang; Daling Zhu (Apoptosis, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Effect of tramadol on immune responses and nociceptive thresholds in a rat model of incisional pain - Yong-min Liu; Sheng-mei Zhu; Kui-rong Wang; Zhi-ying Feng; Qing-lian Chen (Journal of Zhejiang University-SCIENCE B, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Effects of P2Y1 receptor on glial fibrillary acidic protein and glial cell line-derived neurotrophic factor production of astrocytes under ischemic condition and the related signaling pathways - Jing-Jun Sun; Ying Liu; Zhu-Rong Ye (Neuroscience Bulletin, 2008)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Effect of fungal fusaric acid on the root and leaf physiology of watermelon (Citrullus lanatus) seedlings - Hong-sheng Wu; Xiao-ming Yin; Dong-yang Liu; Ning Ling; Wei Bao; Rong-rong Ying; Yi-yong Zhu; Shi-wei Guo; Qi-rong Shen (Plant and Soil, 2008)

Effect of siRNA on HSV-1 plaque formation and relative expression levels of UL39 mRNA - Ren Zhe; Zhang Mei-Ying; Kaio Kitazato; Nobuyuki Kobayash; Zhu Qin-Chang; Zhang Pei-Zhuo; Yang Zhi-Rong; Wang Yi-Fei (Archives of Virology, 2008)

Secretion of malate and citrate from roots is related to high Al-resistance in Lespedeza bicolor - Xiao Ying Dong; Ren Fang Shen; Rong Fu Chen; Zhao Liang Zhu; Jian Feng Ma (Plant and Soil, 2008)

Characterization of impurities in the bulk drug lisinopril by liquid chromatography/ion trap spectrometry - Pei-xi Zhu; Dan-hua Wang; Cui-rong Sun; Zhi-quan Shen (Journal of Zhejiang University-SCIENCE B, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Increased expression of hLRH-1 in human gastric cancer and its implication in tumorigenesis - Shui-Liang Wang; De-Zhu Zheng; Feng-Hua Lan; Xiao-Jun Deng; Jian Zeng; Cheng-Jin Li; Rong Wang; Zhong-Yong Zhu (Molecular and Cellular Biochemistry, 2008)

Abundant Within-varietal Genetic Diversity in Rice Germplasm from Yunnan Province of China Revealed by SSR Fingerprints - Min Tu; Bao-Rong Lu; Youyong Zhu; Yunyue Wang (Biochemical Genetics, 2007)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

ARC contributes to the inhibitory effect of preconditioning on cardiomyocyte apoptosis - Yu Zhen Li; Xiu Hua Liu; Xiao Mei Zhu; Li Rong Cai (Apoptosis, 2007)

Involvement of MAPK/ERK kinase-ERK pathway in exogenous bFGF-induced Egr-1 binding activity enhancement in anoxia-reoxygenation injured astrocytes - Ying Liu; Jin-Biao Lu; Qi Chen; Zhu-Rong Ye (Neuroscience Bulletin, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Family history of hematopoietic and non-hematopoietic malignancies and risk of non-Hodgkin lymphoma - Yawei Zhang; Rong Wang; Theodore R. Holford; Brian Leaderer; Shelia Hoar Zahm; Peter Boyle; Yong Zhu; Qin Qin; Tongzhang Zheng (Cancer Causes & Control, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Proteomic analysis of the serum in patients with idiopathic pulmonary arterial hypertension - Min Yu; Xing-xiang Wang; Fu-rong Zhang; Yun-peng Shang; Yu-xi Du; Hong-juan Chen; Jun-zhu Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Phenolic constituents from the rhizomes of Gastrodia elata - Xiao-Dong Yang; Jie Zhu; Rong Yang; Jing-Ping Liu; Liang Li; Hong-Bin Zhang (Natural Product Research, 2007)

Improved ENSO forecasts by assimilating sea surface temperature observations into an intermediate coupled model - Fei Zheng; Jiang Zhu; Rong-Hua Zhang; Guangqing Zhou (Advances in Atmospheric Sciences, 2006)

Evidences of introgression from cultivated rice to Oryza rufipogon (Poaceae) populations based on SSR fingerprinting: implications for wild rice differentiation and conservation - Zhiping Song; Weiyue Zhu; Jun Rong; Xian Xu; Jiakuan Chen; Bao-Rong Lu (Evolutionary Ecology, 2006)

Adaptor FADD is recruited by RTN3/HAP in ER-bound signaling complexes - Rong Xiang; Yingle Liu; Lei Zhu; Wei Dong; Yipeng Qi (Apoptosis, 2006)

Dissociation (Ds) constructs, mapped Ds launch pads and a transiently-expressed transposase system suitable for localized insertional mutagenesis in rice - Narayana M. Upadhyaya; Qian-Hao Zhu; Xue-Rong Zhou; Andrew L. Eamens; Mohammad S. Hoque; Kerrie Ramm; Ramannee Shivakkumar; Kathryn F. Smith; Shu-Ting Pan; Suzhi Li; Kefan Peng; Song J. Kim; et al. (Theoretical and Applied Genetics, 2006)

Ovipositor length of threeApocrypta species: Effect on oviposition behavior and correlation with syconial thickness - Wen-Quan Zhen; Da-Wei Huang; Jin-Hua Xiao; Da-Rong Yang; Chao-Dong Zhu; Hui Xiao (Phytoparasitica, 2005)

Isolation and characterization of a Ds-tagged rice (Oryza sativa L.) GA-responsive dwarf mutant defective in an early step of the gibberellin biosynthesis pathway - Marcia Margis-Pinheiro; Xue-Rong Zhou; Qian-Hao Zhu; Elizabeth S. Dennis; Narayana M. Upadhyaya (Plant Cell Reports, 2005)

Optimization of technological conditions for one-pot synthesis of (S)-α-cyano-3-phenoxybenzyl acetate in organic media - Ting-zhou Zhang; Li-rong Yang; Zi-qiang Zhu (Journal of Zhejiang University-SCIENCE B, 2005)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

Complex influence of rice variety, fertilization timing, and insecticide on population dynamics of Sogatella furcifera (Horvath) , Nilaparvata lugens (Stl) (Homoptera: Delphacidae) and their natural enemies in rice in Hangzhou, China - Zeng-Rong Zhu; Jiaan Cheng; Ming-Xing Jiang; Xiao-Xi Zhang (Journal of Pest Science, 2004)

A comparative study of genetic relationships among the AA-genome Oryza species using RAPD and SSR markers - Fugang Ren; Bao-Rong Lu; Shaoqing Li; Jingyu Huang; Yingguo Zhu (Theoretical and Applied Genetics, 2003)

Phenotypic polymorphism of CYP2A6 activity in a Chinese population - Ping Xu; Song-Lin Huang; Rong-Hua Zhu; Xing-Mei Han; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Autotoxic potential of cucurbit crops - Jing Quan Yu; Sen Yan Shou; Ya Rong Qian; Zhu Jun Zhu; Wen Hai Hu (Plant and Soil, 2000)